Screening optimum reference genes for quantitative real-time polymerase chain reaction analysis in invasive apple snail, Pomacea canaliculata under different conditions - Ya-Wen Chang; Han-Di Long; Ran Wei; Zhen-Jun Sun; Guo-Xian Zha; Cheng-Dong Wu; Hong-Fang Xie; Jie Hu; Yu-Zhou Du (Molecular Biology Reports, 2026)

Tirzepatide improves neutrophilic inflammation in obese asthmatic mice by downregulating Th17 cell differentiation - Lu Sun; Su-Yan Yao; Zhong-Fu Zuo; Sheng-Xue Yu; Hong-Dan Yu; Qing-Lin Sun; Han-Song Zheng; Yang Hou; Si-Jing Lu; Tie-Feng Yao (Molecular Biology Reports, 2026)

Response patterns of soil protist communities to long-term nitrogen addition and increased precipitation - Yaru Nie; Jiajia Zhang; Binghai Lei; Zhongjie Sun; Junqiang Zheng; Yanyan Yu; Shiqiang Wan; Shijie Han (Soil Ecology Letters, 2026)

Molecular bridging stabilizes halide perovskites for durable photocatalytic H2 production in pure water - Xiwen Ma; Na Han; Wanying Cheng; Guiqiang Diao; Ming Sun; Shaomin Peng; Guichuan Xing; Lin Yu (Chemical Engineering Journal, 2026)

Highly selective CO2/H2 separation by isomeric CALF-20-based porous slurry - Han Tang; Jin Cai; Zi-Ying Zhao; Long-Long Xie; Ping-Xiang Wang; Yang Meng; Hai-Hang Qin; Peng Xiao; Bei Liu; Yun-Lei Peng; Chang-Yu Sun; Zhi Li; et al. (Chemical Engineering Journal, 2026)

Minute-scale observations reveal hydrothermal coupling dynamics of soil freeze–thaw processes in the alpine source region of the Yellow River - Zicheng Yu; Wenyi Sun; Fengpeng Han; Wenying Zeng; Xingmin Mu (CATENA, 2026)

Facilitating the commercialization of germinated foods: Integrated process and optimization for whole grain germination - Minyue Sun; Qianqian Yu; Wanda Xu; Yajuan Wang; Yanqin Zhao; Xiaobo Xi; Anqi Li; Yanlong Han; Xiangyi Meng; Yawen Xiao (Trends in Food Science & Technology, 2026)

Thermal evolution process and accelerated refreezing method of cast-in-place pile in warm permafrost regions - Zhaohui Sun; Jiankun Liu; Yuanming Lai; Linfeng Wang; Zhenyu Zhang; Fenglei Han; Wenbing Yu (Transportation Geotechnics, 2026)

Modal analysis of propeller wake destabilization and energy transport via Tomo-PIV - Chun-yu Guo; Ming-chen Gao; Yang Han; Yi-jie Sun; Wen-xuan Huang; Deng-wei Du (Ocean Engineering, 2026)

Thermochemical coupling of CO2 release and transient cooling for regulating early-age behavior of alkali-activated slag - Yi Han; Qingliang Yu; Feng Sun; Hongzhi Zhang; Gui-Yu Zhang; Xiao-Yong Wang (Journal of Environmental Chemical Engineering, 2026)

Milk exosomal miRNA cargo is remodeled during dietary trans-10, cis-12 CLA-induced milk fat depression in Holstein cows - Jingna Yang; Mingyue Hu; Yifan Fang; Yingqian Han; Yanbin Yang; Yu Sun; Kun Pang; Liqiang Han (International Dairy Journal, 2026)

Strain-dependent metabolic remodelling by indigenous yeasts from fermented sausages enhances saltiness responses in a low-NaCl meat slurry model - Han Li; Yuan Li; Yiwen Zhao; Mengqi Wu; Qianqian Yu; Chengfeng Sun; Zhenjun Zhao; Rongxin Wen (Food Research International, 2026)

Heterogeneous dual-enzyme cascade platform based on COF and MOF for targeted valorization of rice protein - Li-Xia Yan; Liu-Feng Yu; Jie Zhou; Li-Zhi Xu; Yu-Han Sun; Yu-Han Jin; Yi Zhang; Hui-Hui Liu (Food Chemistry, 2026)

Dietary microalgae modulate milk quality and volatile flavor profiles in dairy cows - Han Zhang; Yingqun Nian; Jinchi Yu; Tao Sun; Weiyun Zhu; Shengyong Mao; Junshi Shen (Food Chemistry, 2026)

Ultrasound-induced modifications in egg-milk yogurt: a comprehensive study on physicochemical stability, lipidomic restructuring, and flavor profile enhancement - Danrong Yu; Yaogui Sun; Ni Zhang; Yutong Han; Bohan Wang; Shurong Wang; Ling Ma; Zhihui Yu (Food Chemistry, 2026)

Efficient production of ammonia from atmospheric nitrogen and water via tandem plasma-electrocatalysis - Mingzhu Han; Zejun Gao; Chuyun Ma; Mengxiang Han; Peinuo Yang; Mengmeng Du; Rongyue Sun; Yu Zhang; Tao Sun; Jian Shang; Chunyu Zhou; Bocheng Qiu (Chemical Engineering Journal, 2026)

Deferoxamine alleviates T-2 toxin-induced articular chondrocyte ferroptosis via the Nrf2/xCT/GPX4 axis: Implications for Kashin-Beck disease pathology - Yi-Ming Ren; Wei-Yu Hou; Yuan Pan; Chimey Rigzin; Champa Tutob; Khe Drup; Yuan-Hui Duan; Yun-Bo Sun; Tao Yang; Han-Ji Zhang; Yuan-Hong Hao; Xue-Qiang Wang; et al. (Toxicon, 2026)

Transfer of antibiotic resistance genes in ESBL-producing Escherichia coli from raw milk and dairy farm environments under heavy metal stress - Wenyi Ma; Yu Duan; Shudi Huang; Tianshuai Yuan; Yue Xu; Saihui Sui; Han Sun; Yifei Yin; Hua Ji (International Journal of Food Microbiology, 2026)

Moist-heat induced interfacial co-assembly of κ-carrageenan and soy lecithin: A chemical-crosslinker-free paradigm for physically stable Pickering emulsion - Han Liu; Chengbin Sun; Xiaoyan Wu; Guimei Liu; Bin Yu; Xuemin Kang; Zisong Li; Zhengmin Li; Haiteng Tao; Bo Cui (Food Hydrocolloids, 2026)

Targeting the phenolic A-ring unifies the toxicology and remediation of environmental estrogens in aquatic environments - Liu-Feng Yu; Yi-Lin Ye; Jie Zhou; Yu-Han Jin; Yu-Han Sun; Li-Xia Yan; Chen-Man Li; Jia-Yi Chang; Wei-Jie Chen; Feng Liu; Yong-Wei Feng; Xiao-Dong Huang; et al. (Environmental Research, 2026)

Mesozoic continental crustal growth: A comprehensive review of the accretion-arc system in the Jilin-Heilongjiang high-pressure belt - Zhong-Hua Xin; Jian-Bo Zhou; Wen-Jiao Xiao; Jiang-Tao Han; Gong-Yu Li; Xiao-Miao Tan; Hong-Da Liang; Zhuo Chen; Hong-Yan Wang; Ning-Chen Sun; Rui Gao (Earth-Science Reviews, 2026)

Role of boron doping in bulk and surface structural regulation of cobalt-free high-nickel layered cathodes - Seung U. Chun; Jae Hyeon Choi; Eun-Jung Shin; Kyoung Sun Kim; Han-Koo Lee; Won Gi Hong; Hyungsub Kim; Young-Sang Yu; Gi Dae Park; Sang Mun Jeong (Chemical Engineering Journal, 2026)

Machine learning-based meat freshness evaluation: principle, pipeline and application - Yahong Han; Xiaoxue Jia; Lei Yu; Peihua Ma; Shuyuan Zong; Jiaxin Sun; Wenfu Hou; Yang Yi; Xueting Zhang; Shuai Chen (Critical Reviews in Food Science and Nutrition, 2026)

Retraction notice to “PBAT/PLA humic acid biodegradable film applied on solar greenhouse tomato plants increased lycopene and decreased total acid contents” [Sci. Total Environ. 871 (2023) 162077] - Lu Lu; Ying Han; Jiayin Wang; Jing Xu; Yansu Li; Mintao Sun; Fujian Zhao; Chaoxing He; Yujun Sun; Yijia Wang; Pengfei Huang; Xianchang Yu; et al. (Science of The Total Environment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

A sustainable strategy for complex wastewater treatment: Sequential capture and facile regeneration of Cu(II) and tetracycline using C-A-S-H - Yunbo Sun; Mingyu Han; Xiaoyi Shen; Yu'an Huo; Huaqing Zhang; Yan Liu; Yuchun Zhai (Journal of Water Process Engineering, 2026)

Comparative study of the flavor profile of raw and stir-fried Ziziphi Spinosae semen - Zijun Xue; Falin Sun; Nuo Wang; Xiaolin Yu; Weitao Han; Jin Li; Bin Li; Jinlong Tian (Food Research International, 2026)

Whole-genome analysis and probiotic-related phenotypic characterization of the antifungal Lactiplantibacillus plantarum L6 isolated from traditional Chinese paocai - Saihui Sui; Yu Gao; Tianshuai Yuan; Yu Duan; Han Sun; Baokun Li; Juan Dong; Hua Ji; Cailan Wu (Food Bioscience, 2026)

Tensile strain engineering of LSCF@SDC heterointerfaces for synergistically boosting catalytic activity and suppressing Sr segregation in solid oxide cells - Miao Zhang; Hengbo Yin; Bozheng Yu; Jiakun Sun; Wei Han; Liuzhen Bian; Linzhi Wang; Chaoyi Wang; Jun Peng; Shengli An (Chemical Engineering Journal, 2026)

Erratum to “Simultaneous enhanced nitrogen removal and energy recovery in sediment microbial fuel cells using pyrite as anode filler for low C/N ratio wastewater treatment” [Bioresour. Technol. 451 (2026) 134515] - Yun Zheng; An-Qi Wang; Ming-Kun Yu; Xin Sun; Han-Qi Xiang; Chao Wang; Xiao-Yu Ding; Qiu-Jun Wang; Jun Zhou; Ping Wei; Xiao-Yu Yong (Bioresource Technology, 2026)

Effects of Antioxidant DI-3-N-Butylphthalide on Hemorrhagic Transformation Assessed by Propensity Score Matching in a Real-World Thrombolyzed Ischemic Stroke Patient Setting - Ziqi Han; He Liang; Tieping Fan; Mario Minor Murakami Junior; Shumin Li; Ruikang Sun; Daoyong Peng; Shiwei Du; Yu Hasegawa; Haojie Gao; Dong Chen; Dirk M. Hermann; et al. (Translational Stroke Research, 2026)

Genetic dissection of a key dynamic growth period QTL for source–sink-related traits and its breeding application potential in wheat - Meng Yuan; Hongke Ding; Yunkai Yue; Chuanliang Zhang; Yuze Wang; Dandan Zhang; Shipeng Li; Ruiqi Nie; Jia Liu; Yanchuan Huang; Jinyu Han; Sufu Deng; et al. (Theoretical and Applied Genetics, 2026)

Primer-programmed circular template generation enables padlock-free rolling circle amplification for low-background CRISPR-based pathogen detection - Yemin Han; Haotian Yu; Manman Lv; Mengqing Cheng; Weihao Li; Houyang Ge; Song Gao; Lu Yin; Qinyu Ge; Xinping Xu; Yan Huang; Longhua Sun; et al. (Analytica Chimica Acta, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

A digital PCR-based platform for rapid assessment of chloroplast stress adaptation in microalgal metabolic engineering - Jinuk Jeong; Seohyun Park; Kornsorn Srikulnath; Byung Sun Yu; Kyudong Han (Genes & Genomics, 2026)

Cell-Type-Specific Calibration of Mitochondrial Ubiquitination in Stem Cell Fate Decisions - Hao-Cheng Liu; Si-Yuan Chen; Nan-Nan Yu; Mei-Hua Jin; Hu-Nan Sun; Ying-Hao Han (Stem Cell Reviews and Reports, 2026)

Neuro-symbolic framework for multi-USV coordination: COLREGs-compliant and energy-efficient smart navigation - Shuai Huang; Yi-Feng Chen; Mao-Yuan Sun; Jia-Ning Gao; Yu-Han Zhou; Jing-Wen Zeng; Cheng-Chen Wang; Ya-Ze Han; Yang Xiong (Frontiers in Marine Science, 2026)
Introduction Coordinating multiple unmanned surface vehicles (USVs) in coastal waters requires simultaneous consideration of COLREGs compliance, real-time response, energy efficiency, fault tolerance, and semantic scene understanding. Existing approaches typically address only part of this problem and provide limited support for integrated fleet-level coordination. Methods This paper proposes NSC-Marine, a neuro-symbolic framework that conceptually addresses these coupled constraints. It combines multimodal causal perception, LLM-based rule reasoning, energy-aware motion planning, and distributed fault reconfiguration within a dual-rate control architecture. To improve deployment safety, semantic reasoning is used to generate structured constraints, while low-level motion execution remains under deterministic planning and control. Results The framework is evaluated strictly within a physics-based simulation environment with approximately 70% overall fidelity, involving 1,000 trials of 20–100 USVs under Beaufort Scale 3–5 conditions. Under these simulated conditions, NSC-Marine achieves 88.7% ± 2.3% COLREGs compliance, 82.3% mission success under compound faults, and 13.6% energy reduction relative to the RLCA baseline, while maintaining a 320 ms critical-path latency. Discussion These metrics reflect an idealized simulation baseline and must not be generalized to physical deployment readiness. Real-world performance remains unvalidated, and staged hardware-in-the-loop testing and field trials are required to characterize the system’s actual behavior under physical disturbances.

Sulfur-based mixotrophic denitrification with PCL/corncob for low C/N mariculture wastewater: Kinetics, microbial mechanism, machine learning optimization and continuous-flow validation - Liwei Wang; Haowei Wen; Xiefa Song; Weimin Yu; Teng Ma; Zuoliang Sun; Zheng Zhou; Huilin Wang; Dengpan Dong; Xueshu Han; Meng Li (Aquaculture, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

High-resolution profiling of C10-C20 chlorinated paraffins in seawater and marine organisms: Optimized orbitrap mass spectrometry strategy and bioaccumulation insights from Laizhou Bay, China - Qingkui Cui; Jinzhao Hou; Jia Liu; Deyan Hu; Xiang Yu; Wei Chen; Yuzhu Ding; Yanqing Sun; Mingfang Liu; Yingjiang Xu; Xiaojing Liu; Dianfeng Han (Regional Studies in Marine Science, 2026)

Centrifuge model test of bearing capacity of anchor piles in hydrate-bearing silty sand - Qing Yang; Qiangsheng Yu; Zhongtao Wang; Anyuan Sun; Yunrui Han; Long Li (Ocean Engineering, 2026)

Tectonically driven erosion with climatic modulation across the southern Tibetan Plateau: Insights from 10Be erosion rates - Jia-Qi Sun; Jin-Gen Dai; Xu Han; Matthew Fox; Guang-Sheng Ren; Zhi-Cheng Yu; Bo-Rong Liu; Xiang-Rui Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The sugar-sensing kinase OSK3-mediated destabilization of OsbZIP58 promotes pre-harvest sprouting in rice under high temperature - Heng Xu; Yuhong Tan; Fudeng Huang; Zhiping Deng; Ningning Zhang; Meihao Sun; Hua Zhang; Heng Zhang; Tao Song; Fulin Wang; Yu Han; Junmin Wang; et al. (Molecular Plant, 2026)

The critical role of extraction-decolorization sequence in governing the structural and functional evolution of Auxenochlorella protein - Yuxuan Huang; Xin Wen; Han Wang; Yu Sun; Zhanmei Jiang; Zhibiao Feng (Innovative Food Science & Emerging Technologies, 2026)

A cross-building few-shot energy load forecasting framework via transferable temporal learning and residual correction - Qian Liu; Dehu Yu; Yibing Xue; Honglei Sun; Shujuan Yang; Fei Han (Energy and Buildings, 2026)

Risk-informed multi-objective techno-economic assessment of air-to-liquid retrofits with heat recovery in legacy air-cooling data centers - Runchen Zhao; Jinpeng Hu; Yingtao Sun; Han Yang; Hao Yu; Cunlu Zhao; Qiuwang Wang; Zhigang Li; Fei Duan; Chun Yang; Yanmei Jiao; Dongxu Ji; et al. (Energy and Buildings, 2026)

Detachable TMSD-CRISPR for programmable and highly specific discrimination of DNA/RNA mutations - Yiqi Zhang; Wang Luo; Yaoyi Zhang; Yu He; Li Zhang; You Wu; Kejia Wu; Hongyan Yu; Xiaole Han; Na Yin; Jiu Pu; Dan Bai; et al. (Chemical Engineering Journal, 2026)

Synergizing macroscopic lateral anchoring with microscopic pore topology: A dual-optimization strategy for large bone defect reconstruction - Hao Chen; Xingzhen Li; Wenbo Yang; Yu Sun; Jinbo Zhang; Aobo Zhang; Meng Xu; Qian Wan; Xingchen Guo; Qing Han; Luquan Ren; Jincheng Wang (Chemical Engineering Journal, 2026)

Characterizing above- and below-ground biomass of alpine basin-scale grassland on Qinghai-Tibet Plateau through climate, soil and topography drivers - Xuyang Sun; Jintao Liu; Zhenghong Yu; Zhen Cheng; Ping Huang; Xiaole Han; Hu Liu (CATENA, 2026)

Simultaneous enhanced nitrogen removal and energy recovery in sediment microbial fuel cells using pyrite as anode filler for low C/N ratio wastewater treatment - Yun Zheng; An-Qi Wang; Ming-Kun Yu; Xin Sun; Han-Qi Xiang; Chao Wang; Xiao-Yu Ding; Qiu-Jun Wang; Jun Zhou; Ping Wei; Xiao-Yu Yong (Bioresource Technology, 2026)

Eeg-based analysis of cognitive load under 2D/3D visual stimuli - Yu Liu; Chen Song; Yunpeng Yin; Herui Shi; Jinglin Sun; Han Wang; Minpeng Xu (Experimental Brain Research, 2026)

Host-derived Bacillus velezensis enhances intestinal structure, antioxidant capacity, and pathogen resistance in the American bullfrog (Aquarana catesbeiana) - Yueming Hu; Han Lin; Mengzhen Jiang; Changyi Lin; Hua Li; Jingyang Sun; Kesong Chen; Yebing Yu; Chun Liu (Archives of Microbiology, 2026)

Targeting the fibrosis-inflammation-oxidative stress axis: multifaceted mechanisms of salidroside in chronic organ fibrosis - Ai-Qian Liu; Jongwon Byun; Nan Nan Yu; Mei-Hua Jin; Ying-Hao Han; Dong Seok Lee; Dong-Hun Lee; Hu-Nan Sun (Apoptosis, 2026)

In-depth analysis of the thermal environment and adaptive thermal mitigation strategies in arid-hot tourist attractions - Yu Han; Yuan Su; Le Xuan; Qiao Yan; Yongxin Wang; Jingyi Sun; Wanjiang Wang; Qinglin Meng; Zhiwen Luo; Adili Saimaiti (Urban Climate, 2026)

A chimeric PRRSV vaccine with dual Nsp2 deletions elicits cross-lineage protection against heterologous challenge - Zhuo-ran Miao; Bo Han; Ling-zhai Meng; Zhen-hui Ren; Yi-han Lu; Jing Li; Wen Sun; Shi-qin Zhang; Jia Wang; Jin-jin Ma; Jia-Lu Li; Yu-tong Zhu; et al. (The Veterinary Journal, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Hydrogen-based suspension roasting for efficient utilization of high-phosphorus oolitic hematite: Selective reduction mechanism and metallization behavior - Xuesong Sun; Yanjun Li; Zhidong Tang; Jianwen Yu; Yize Guo; Jianping Jin; Yuexin Han (Minerals Engineering, 2026)

Synergistic removal of Cr(VI) by Cr-reducing microflora and Fe-Mn modified composite under varying nutrient conditions - Mingdian Zhou; Yaozong Chen; Zhiyuan Yu; Xin Dai; Yu Chen; Haisheng Han; Min Gan; Wei Sun; Jianyu Zhu (Journal of Water Process Engineering, 2026)

Life extension of lithium-ion batteries using bidirectional pulse current: Focusing on amplitude - Shuoshuo Shi; Xiaodong Xu; Shengjin Tang; Hui Ye; Xiaoyan Sun; Jianqiang Jing; Junbin Guo; Chuanqiang Yu; Xuebing Han (Journal of Cleaner Production, 2026)

Environmentally relevant concentrations of nanoplastic increase the accumulation and endocrine effects of BDE47 and its metabolite 6-OH-BDE-47 in male frogs’ testes - Yinan Zhang; Bingyi Wang; Wenhui Sun; Lilai Shen; Zhiquan Liu; Binhao Wang; Jiafeng Ding; Yu Han; Hangjun Zhang (Journal of Environmental Sciences, 2026)

Non-uniform gradient depressurization strategy for balancing heat transfer and gas production in Dual-Gas Co-Production systems - Xian Sun; Hang Zheng; Hui Yang; Fu-Jun Cheng; Zhen Pan; Wen-Chen Han; Hao-Xiang Sun; Yang Yu; Ling-Ban Wang; Chang-Yu Sun (Fuel, 2026)

Morphology-engineered Ru/CeO2 for high-efficiency plasma CO2 methanation: Unveiling the dynamic CO re-oxidation mechanism - Boqiong Jiang; Zhehao Lu; Lihan Huang; Xinhua Zheng; Aijia Liu; Haoyu Yang; Yi Zhang; Jingyi Han; Shaocai Yu; Yuhai Sun (Chemical Engineering Journal, 2026)

Sodium alginate modified by dopamine multifunctional injectable hydrogel with photothermal, antibacterial, and hemostatic properties for accelerating infected wound repair - Xinbo Ma; Xiaonan Huang; Xuelian Zhang; Jiani Zhang; Xinyu Sun; Yue Ma; Jiawei Li; Han Yu; Yantao Zhao; Xue Chao (Carbohydrate Polymers, 2026)

λ-Carrageenan inhibits African swine fever virus infection potentially through its interaction with the viral envelope protein CD2v - Kun Han; Limeng Sun; Can Jin; Siqi Wan; Caiqin Cao; Yulu Yue; Man Lu; Xiaotong Wang; Yi Zheng; Hailong Liu; Yilin Guo; Dagang Tao; et al. (Carbohydrate Polymers, 2026)

Cooling characteristics of the dual-layer ventilation slope and underlying permafrost response process of the railbed - Zhenyu Zhang; Qihao Yu; Fenglei Han; Tianchun Dong; Dan Wang; Kun Chen; Zhaohui Sun; Shenglin Wang (Cold Regions Science and Technology, 2026)

Synergistic effects of iron tailings and maize straw on soil compression: roles of sand content and organic carbon - Aobo Sun; Changdong Han; Yanyu Han; Jiaqi Li; Jing An; Guangyan Liu; Na Yu; Hongtao Zou; Hongdou Liu (Journal of Soils and Sediments, 2026)

Biochar and Sulfur Reduce Cadmium Toxicity in Rice by Altering Cadmium Speciation: Roles of Soil DOC, Organic Acids, and Microorganisms - Xiaoxue Sun; Yi Zhang; Jianfei Yang; Han Li; Yu Lan; Zunqi Liu; Tianyi He (Journal of Soil Science and Plant Nutrition, 2026)

Long-term HRV metrics may assist in differentiating between prolonged disorders of consciousness and emergence from minimally conscious state : a cross-sectional study - Xinwei Tang; Na Ren; Zuojun Cao; Zi Yu; Xu Han; Weiqiang Cai; Youbei Yang; Lisi Lu; Mukedaisihan Maisedi; Zuowen Sun; Junfa Wu; Yi Wu; et al. (Acta Neurologica Belgica, 2026)

Source contributions and mechanisms underlying reduced precipitation acidity in the Lingang New Area of Shanghai - Aichun Chen; Huihui Zhang; Hanlin Sun; Xiaoxi Yang; Yifei Wang; Yanli Sun; Jiajun Han; Jingmiao Yu; Dong Zhang (Environmental Monitoring and Assessment, 2026)

Numerical investigation of cavitation and vortex evolution characteristics in a hull-propeller-rudder coupled system - Chao Wang; Yi-Ming Hu; Cong Sun; Yu Zhao; Yang Han; Lian-Zhou Wang; Jia-Xiu Cao (Ocean Engineering, 2026)

Comparison of dephosphorization processes for high-phosphorus oolitic hematite based on MLA mineralogical characteristic analysis - Yusen Yu; Wenbo Li; Yongsheng Sun; Yuexin Han; Yanjun Li (Minerals Engineering, 2026)

Cd toxicity thresholds in response to freeze-thaw and wetting-redrying cycles in various parental paddy soils - Jing Wang; Meng Wang; Lei Yu; Xiaoyi Sun; Luyao Qin; Jiaxiao Liu; Ruyan Zhou; Yun Han; Shibao Chen (Journal of Environmental Sciences, 2026)

Intercalation-mediated bionic nano-hydrogel adhesives for robust omni-domain adhesion - Jialve Sun; Zhengzhi Mu; Tianye Yang; Hexuan Yu; Wenda Song; Zhiyan Zhang; Junqiu Zhang; Shichao Niu; Zhiwu Han; Luquan Ren (Chemical Engineering Journal, 2026)

A glucose-triggered self-reinforcing hydrogel based on carboxymethyl chitosan/oxidized hyaluronic acid/borax for delivering nano-selenium and dynamic diabetic wound management - Wei-Xiong Li; Shanshan Li; Hao Cheng; Yu Chen; Han-Jian Hu; Shipeng Tang; Jian Sun; Xiao-Ping Liao; Gang-Biao Jiang; Hongyan Zhang (Carbohydrate Polymers, 2026)

Dehydroepiandrosterone activates ADGRG2 to regulate chloride homeostasis and sperm motility via Gs-cAMP pathways - Dan Jiang; Ji-Fei Han; Xian-Zheng Guo; Yu-Qi Ping; Fan Yang; Peng Xiao; Jin-Peng Sun; Xiao Yu; Zhao Yang; Hui Lin (Science China Life Sciences, 2026)

Genome-wide identification and promoter activity analysis of fibrillin gene families in different color carrot roots - Yu-Jie Sun; Rong-Rong Zhang; Zi-Han Zhao; Xu Zhang; Xue-Feng Peng; Ya-Hui Wang; Ai-Sheng Xiong (Protoplasma, 2026)

Two novel spermidine alkaloids from the roots of Capparis acutifolia - Yu-Xiao Han; Shu-Qing Kuai; Hui-Long Sun; Hong-Gang Wang (Natural Product Research, 2026)

Colletotrichum aenigma causes anthracnose disease of Ficus carica L. in China - Yu-kun Qi; Wen-zhang Liu; Feng-ying Han; Wen-cheng Zhu; Shi-jun Sun; Qing-hai Wang; Ling-xi Zhou (Crop Protection, 2026)

Advances in high-performance alginate hydrogels: properties, performance enhancement strategies, and their applications in the food industry - Jiabo Wang; Yuanpu Liu; Chuanwu Han; Zhihui Liu; Yumeng Yue; Zhiyuan Yu; Meng Ma; Qingjie Sun; Fengwei Xie; Man Li (Trends in Food Science & Technology, 2026)

Discrete artificial bee colony algorithm based on multiple neighborhood swaps for the hybrid flowshop scheduling problem with uncertain processing stages - Yang Yu; Xinbo Song; Zixiang Li; Liangliang Sun; Yuyan Han; Xinfu Pang; Zhujun Wang; Natalja M. Matsveichuk; Yuri N. Sotskov (Swarm and Evolutionary Computation, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Structural optimization of natural plant products: Construction and insecticidal activities study of eugenol's derivatives - Wen Zhang; Xiao-Han Zhang; Li-Hong Sun; Cheng-Yuan Liu; Wen-Hui Zhang; Yi-Wen Huang; Jun-Long Wang; Ji Zhang; Jun-Yu Liang (Pesticide Biochemistry and Physiology, 2026)

Numerical prediction on cavitation characteristics of a marine propeller in oblique flow without and with hull wake effects - Yu Sun; Shengyao Ge; Rui Wu; Wenyu Chen; Han Han; Depeng Ma; Huan Ping (Ocean Engineering, 2026)

Cyanobacterial blooms under CO2(aq)-limited conditions in karst reservoirs diminish the synergy of pollution reduction and carbon sequestration via the biological carbon pump - Yunfeng Xue; Cuihong Han; Hailong Sun; Chaowei Lai; Yu Wei; Haibo He (Journal of Hydrology, 2026)

Enhanced photocatalytic activation of peroxymonosulfate by HACC/BPNS composite for HCBD degradation: Unraveling sulfate radical-based mechanisms - Lulu Jiang; Ying Han; Yuetong Sun; Yu Liu; Yingang Xue (Journal of Environmental Chemical Engineering, 2026)

High-entropy prussian blue analogue for rapid and efficient adsorptive removal of thallium from water: Performance and mechanism insights - Ying He; Changhao Cai; Yingming Ma; Azhar Mahmood; Zhenbang Liu; Wei Wang; Yu Bao; Zhonghui Sun; Li Niu; Carlos Ruiz Canovas; Dongxue Han; Tangfu Xiao (Journal of Environmental Chemical Engineering, 2026)

Efficient sampling the microbiome in human exhaled bioaerosols: A comparison of condensation-based and wet-wall cyclone techniques - Han Gao; Mengqing Cheng; Weihao Li; Manman Lv; Yemin Han; Haotian Yu; Xinping Xu; Zuhong Lu; Dianhuai Meng; Longhua Sun; Quanjun Liu (Journal of Environmental Chemical Engineering, 2026)

Modulation of highland barley noodles quality by water-soluble polyphenols epigallocatechin gallate and ferulic acid - Mengting Wang; Yulin Wu; Zichu Wang; Yu Jiang; Yanfei Wang; Chuanwu Han; Yang Li; Jichun Tian; Meng Ma; Qingjie Sun; Fengwei Xie; Man Li (Food Chemistry, 2026)

Unraveling -Ni2+/-Mn2+ doped Ti3CNTx MXene nanowebs for high-performance asymmetric supercapacitors - Sabeen Fatima; Yu Sun; Lei Han; Nan Han; Muyang Li; Safia Khan; Klaus Leifer; Xiaoqing Jiang; Jie Li; Qingsong Wan; Hongji Fang; Yafei Ning; et al. (Chemical Engineering Journal, 2026)

Fine mapping and candidate gene dissection of the wheat powdery mildew resistance gene PmPBDH - Yuli Jin; Jiatong Li; Delin Li; Ningning Yu; Ya Zhao; Bo Wang; Jun Guo; Jiadong Zhang; Guantong Pan; Yaoxue Li; Yintao Dai; Nina Sun; et al. (Theoretical and Applied Genetics, 2026)

The presence of native semi-fossorial herbivores enhances the coupling between species and functional diversity in alpine meadows - Yuan Yuan Duan; Kun Qin; Yu Chen; Jie Li; Ni Wang; Xiao Dan Sun; Yan Ping Bai; Lin Han Li; Zheng Gang Guo (Agriculture, Ecosystems & Environment, 2026)

Effects of glycyrrhizic acid on growth performance and hepato-intestinal health of American bullfrogs (Aquarana catesbeiana) - Zhixiang Bai; Kesong Chen; Xingye Xu; Han Lin; Jingyang Sun; Hua Li; Yueming Hu; Mengzhen Jiang; Wensen Tan; Yanwen Wu; Yebing Yu; Chun Liu (Aquaculture International, 2026)

Microbial Responses to Warming Reduce Deep Blue Carbon Storage - Leilei Xiao; Jian Liu; Genevieve L. Noyce; Jaehyun Lee; Carlos M. Duarte; Meng Zhou; Min Luo; Ruifeng Sun; Run Dang; Lifeng Zhou; Lirong Zhang; Chuancheng Fu; et al. (Global Change Biology, 2026)
Coastal wetlands are critical blue carbon reservoirs, yet the depth‐resolved impacts of warming on belowground carbon dynamics remain poorly understood. Over the course of an 8‐year in situ experiment, we investigated plant‐derived carbon inputs, soil carbon losses via respiration, and microbially mediated carbon fixation across a 60 cm soil profile under a projected 2°C atmospheric warming scenario. Plant carbon fixation (above‐ and belowground net primary productivity) and soil respiration exhibited synchronized responses to warming, with an initial increase, followed by a decline in the mid‐term, and no significant response in the later stages. Soil and microbial respiration stabilized after prolonged exposure to elevated temperatures, as these processes were constrained by substrate availability. In contrast, phospholipid fatty acid profiling, amino sugar biomarkers, and metagenome‐assembled genomes consistently indicated a greater than one‐third reduction in microbial carbon fixation within subsoils (40–60 cm). Our fully factorial, depth‐stratified warming design reveals the particular vulnerability of deep soil microbial carbon retention to long‐term climate warming, independent of shifts in plant input or respiratory carbon loss. This work highlights underappreciated pathways influencing soil blue carbon dynamics in a changing world.

Dietary reuterin as a potential feed additive enhances growth performance, antioxidant capacity, and anti-inflammatory response in largemouth bass: Multi-omics insights into metabolic reprogramming - Jia-Le He; Han-Yin Xu; Yu-Long Sun; Tao Han; Jian-Kun Zhang; Qiang Chen; Ji-Teng Wang (Aquaculture, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Nickel refining fumes activate glutamine metabolism via the HIF‐1α/Notch pathway to drive epithelial-mesenchymal transition in Beas‐2B cells - Qian-Qian Sun; Han-Nong Yu; Rui-Ze Wu; Bo Zhang; Wen-Xue Yao; Wei-Yang Liu; Jia Han; Li-Yan Ju; Yu-Lin Pan; Yong-Hui Wu (Toxicology, 2026)

Sustainable ironmaking via Hydrogen-based suspension pre-reduction of hematite: reduction mechanisms, bonding behavior, and comparison with carbon routes - Xuesong Sun; Yanjun Li; Jianwen Yu; Yize Guo; Yuexin Han (Minerals Engineering, 2026)

Spatial patterns and environmental drivers of evapotranspiration across the Chinese Grassland Transect - Lexin Ma; Zhi Chen; Tianxiang Hao; Meng Yang; Quanhong Lin; Weikang Zhang; Lang Han; Zhaogang Liu; Mingyu Sun; Yong Lin; Xianjin Zhu; Shiping Chen; et al. (Journal of Hydrology, 2026)

A net-like colloid with peculiar CO2 sorption behavior formed by aggregation of organic ligand molecules in water - Jin Cai; Wan Chen; Hai Li; Xin Zheng; Han Tang; Ming-Ke Yang; Zi-Xuan Huang; Zi-Ying Zhao; Peng Xiao; Yun-Lei Peng; Xian-Ren Zhang; Long-Long Xie; et al. (Chemical Engineering Journal, 2026)

Identification of a novel nonsense variant in ARR3 in a family with early-onset high myopia - Jiahe Yu; Jie Zhang; Yaqin Jiang; Chunli Ma; Wenjing Wang; Kaihui Zhang; Rujin Tian; Haisu Chen; Haitao Han; Huixin Sun; Chuanzhi Peng; Han Zhang; et al. (Genes & Genomics, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Current status, challenges, and future prospects of non-thermal sterilization technologies in dairy products - Nina Ding; Qiyue Sun; Zhongna Yu; Hongning Jiang; Qijing Du; Rongbo Fan; Liangliang You; Yongxin Yang; Rongwei Han (Critical Reviews in Food Science and Nutrition, 2026)

Pathogenicity of Porcine reproductive and respiratory syndrome virus in the reproductive system of female piglets: Pathological damage to the uterine horns and developmental arrest - Yi-Xin Yan; Ying Guan; Lei Zhao; Han-Yu Li; Tong Xu; Li-Na Shao; Si-Yuan Lai; Yi Qing; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; et al. (Veterinary Microbiology, 2026)

Tillage and straw return alleviate soil compaction in Northeast China: From pore structure to root development and crop productivity - Aobo Sun; Na Yu; Yanyu Han; Jing An; Hongtao Zou (Soil and Tillage Research, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

A watershed-scale perspective: Elucidating the spatiotemporal dynamics and driving mechanisms of nitrate along the Lancang River - Meng Sun; Yufei Bao; Yuchun Wang; Hao Chen; Jiyuan Yu; Jie Wen; Shanze Li; Xiaodong Qu; Nanping Wu; Hanxiao He; Lingxin Han (Journal of Hazardous Materials, 2026)

Emergent constraints reveal underprediction of future global water availability under anthropogenic forcing - Senlin Tang; Qiang Zhang; Xintong Gong; Chong-Yu Xu; Vijay P. Singh; Fubao Sun; Yao Feng; Ziwei Li; Likun Han (Global and Planetary Change, 2026)

Self-directed assembly of single and bi-metallic organic frameworks (MOFs) over Nb2CTx MXene as highly stable electrodes for efficient overall water splitting - Jingyu Zhao; Xiaoxiao Zheng; Yu Sun; Muyang Li; Nan Han; Lei Han; Safia Khan; Klaus Leifer; Raffaello Papadakis; Sabeen Fatima; Gengchang Zhu; Hu Li (Fuel, 2026)

Mechanism of fructose and ammonium sulfate preference regulation in yellow Monascus pigment production: a metabolomic and proteomic study - Xianjin Liu; Wei Zou; Bin Xie; Yufan Zhang; Haolan Han; Xiang Yu; Jun Liu; Yiwen Sun; Yuanliang Hu; Yanli Feng (Food Bioscience, 2026)

Moderate oxidation–coagulation pretreatment for mitigating ultrafiltration membrane fouling by algae-laden water: Performance and mechanisms - Jinlong Han; Qiuwen Wang; Li Sun; Mathias Ulbricht; Lukas Fischer; Houyun Yang; Xiao-Yang Liu; Zhijun Ren; Andrzej Kraslawski; Kengo Kubota; Yu-You Li (Desalination, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Highly linear bionic strain decoupling sensor mediated by curved surface stress - Xueping Zhang; Junqiu Zhang; Jiachao Wu; Yu Chen; Xueyang Li; Wenjie Yu; Xiancun Meng; Guilin Li; Lina Ju; Bo Li; Tao Sun; Zhiwu Han; et al. (Chemical Engineering Journal, 2026)

A DAMP- and antigen-capturing nanosponge designed as personalized cancer vaccine - Ting Meng; Weikai Sun; Chuanning Wang; Han Yang; Yafei Qi; Daqian Sun; Bingrun Song; Bingzhao Li; Aixin Song; Na Sun; Zhiliang Gao; Dexin Yu (Chemical Engineering Journal, 2026)

An aerosol-scaled QMRA based on viral surrogates for indoor airborne pathogen risk assessment - Han Gao; Mengqing Cheng; Haotian Yu; Tian Wen; Xinping Xu; Longhua Sun; Zuhong Lu; Quanjun Liu (Building and Environment, 2026)

Aqueous LC-MS/MS quantification of α-/β-nicotinamide mononucleotide in dietary supplements using a pentabromophenyl column - Chng Sze Hoei; Nian-Hua Wu; Chao-Ming Tsen; Ping-Wei Sun; Han-Wei Chang; Shin-Yuan Wang; Hung-Yu Lin (Analytica Chimica Acta, 2026)

mRNA Rather than Protein Expression of Hepatic Selenoprotein H is More Sensitive to Short-term Low Aflatoxin B1 Exposure in Mice with Varying Selenium Intake - Ruirui Yu; Mengru Hao; Aiping Liu; Chenggang Yang; Ping Xu; Yong Zhou; Alexey A. Tinkov; Aolin Yang; Qingqing Lv; Ziyu Han; Chao Wang; Zhou Wang; et al. (Biological Trace Element Research, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

A new method for efficient recovery of boron from boron-bearing iron concentrate: low-temperature fluidized selective reduction and magnetic separation - Jianwen Yu; Xuanxiong Kang; Peiyu Li; Xuesong Sun; Yanjun Li; Yuexin Han; Zhongxu Qi; Dayon Sun (Minerals Engineering, 2026)

Integrating system dynamics and machine learning to establish the Water-Energy-Food-Climate-Land (WEFCL) nexus of aquavoltaics - Fi-John Chang; Chu-Han Chen; Meng-Hsin Lee; Yu-Han Chou; Wei Sun (Journal of Cleaner Production, 2026)

Mapping permafrost active layer thickness revealed by airborne frequency-domain electromagnetic data: A case study in Datong River Valley, Tibetan Plateau - Xipeng Shan; Rukuan Xie; Xuezhong Yu; Song Han; Siyuan Sun; Shijun Li (Journal of Applied Geophysics, 2026)

Temperature-pressure field evolution of hydrate-bearing sediments: A comparative study of depressurization strategies for gas recovery using a novel fan-shaped simulator - Ling-Ban Wang; Yi-Fei Sun; Yu-Hao Bu; Zhen-Bin Xu; Xian Sun; Han-Feng Shao; Chang-Yu Sun; Guang-Jin Chen (Gas Science and Engineering, 2026)

Seismic behavior of corroded precast concrete beam-column joints with wet-type connections - Yu-Heng Zhao; Xue Zhang; Guang Shi; Xiao-Han Zhuang; Jia-Lu Sun; Fang-Xin Jiang (Engineering Structures, 2026)

Electrically insulating BNNS/PVDF@AlN/PVP composites with simultaneously enhanced in-plane and through-plane thermal conductivities - Wei-Hua Han; Yaping Fan; Yu Long; Bin Sun; Yun-Ze Long; Chun-Cheng Hao (Chemical Engineering Journal, 2026)

A1-Reactive Astrocytes in the Posterior Part of Paraventricular Thalamic Nucleus Are Involved in Pain Modulation in Mice - Han-Xue Sun; Zhong-Yi Liu; Jia-Ni Li; Liu-Jie Zhao; Xue-Mei Wu; Chu-Han Liu; Jie Hong; Ke-Hua Zhu; Feng-Ling Wu; Si-Hai Chen; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2026)

Positive and negative responses of AMF community and diazotrophic community to peanut genetic diversity - Yanyan Yu; Miaomiao Li; Cong Wang; Zhongjie Sun; Xiongde Dong; Shijie Han; Junqiang Zheng (Applied Soil Ecology, 2026)

An aptamer integrated electrochemistry and photoluminescence dual-mode microfluidic biosensor for sensitive and accurate ovarian cancer extracellular vesicles detection - Xiaoshuang Chen; Junxia Han; Mingyuan Sun; Zhenhua Wang; Shuai Wang; Lin Han; Yu Zhang (Analytica Chimica Acta, 2026)

LD-110, a potent LSD1 PROTAC degrader, suppresses tumor growth by inducing ER stress and apoptosis - Danyi Zhai; Jiezhen Zhuo; Yudong Yin; Lan Li; Mengting Liang; Xin Zhou; Lihua Liu; Liangzhen Chen; Xiufang Xiong; Qing Yu; Xin Han; Yi Sun (Science Bulletin, 2025)

Thermal decomposition behavior of boron-bearing iron concentrate under nitrogen atmosphere: Kinetics, mineral phase transformation and microstructure evolution - Jianwen Yu; Xuanxiong Kang; Peiyu Li; Xuesong Sun; Yanjun Li; Yuexin Han; Zhongxu Qi; Dayon Sun (Minerals Engineering, 2025)

Mechanisms of phosphorus removal by biological carbon pump in karst reservoirs and their role in eutrophication mitigation: Insights from two subtropical karst reservoirs in Guizhou Province, China - Cuihong Han; Yu Wei; Hailong Sun; Song Ma; Hao Yan; Qian Bao; Yi Zhang; Yunfeng Xue; Haibo He (Journal of Hydrology, 2025)

Modulation of flavour perception under sodium-reduced conditions: A sensory–metabolic interaction framework driven by Debaryomyces hansenii SH4 and KCl - Han Li; Hongyu Li; Qianqian Yu; Chengfeng Sun; Huaishu Wang; Yonglin Gao; Rongxin Wen (Food Research International, 2025)

Proteomic and flavor dynamics in irradiated scallop adductor muscle during refrigerated storage via 4D-DIA proteomics - Zhupeng Zhang; Peng Ge; Chaoqi Han; Jie Zhang; Richeng Yu; Wenxiu Wang; Ran Suo; Jianfeng Sun (Food Chemistry, 2025)

Multi-task deep learning utilizing VOCs detected by HS-GC-IMS for geographical origin tracing and adulteration detection of turmeric powder - Xiao Han; Tong Wu; Shixin Cen; Jie Yong; Xinrang Tian; Xinyi Li; Rui Sun; Minghui Liu; Heshui Yu; Zheng Li (Food Control, 2025)

Harnessing dental stem cell-extracellular vesicles for osteogenesis, immunomodulation, angiogenesis, and neurogenesis during bone regeneration - Xi Xiang; Jianwen Li; Danyuan Xie; Keyu Lv; Hanyang Yu; Xinwei Han; Ying Ruan; Tingting Sun; Xuguang Gao; Youguang Lu; Janak L. Pathak; Sujuan Zeng (Chemical Engineering Journal, 2025)

A sequential nanotherapy potentiate anti-angiogenic therapy by disrupting lipid metabolism under metabolic stress - Qiye Xi; Xiaojing Lin; Yixian Xie; Fengyong Cheng; Ben Hu; Fengling Zhang; Fushan Sun; Bing Han; Yufang Lai; Yongxia Wang; Jigang Wang; Meng Yu (Chemical Engineering Journal, 2025)

Changes in above- and below-ground biodiversity mediate understory biomass response to prescribed burning in Northeast China - Huiying Cai; Dongmei Li; Yu Han; Tongxin Hu; Guang Yang; Long Sun (Plant and Soil, 2025)

Integrating miRNAs with QTL for identification of milk and reproduction related traits in dairy cattle - Wonseok Shin; Seyoung Mun; Songmi Kim; Byung Sun Yu; Kornsorn Srikulnath; Kung Ahn; Kyudong Han (Genes & Genomics, 2025)

A novel quad-modality deep neural network for estimating chlorophyll-a concentrations in Lianyungang’s lakes and reservoirs using Sentinel-2 MSI data - HaiHong He; Xue Li; Dewei Wang; Wenli Qiao; Yiming Sun; Yu Han; Feixiang Zhang; Xiyu Zhao (Water Research, 2025)

Experimental study on near-wall temperature distribution of wall fire with various rectangular fire sources - Yu Han; Xiepeng Sun; Xuehui Wang; Xiaolei Zhang; Longhua Hu (Engineering Structures, 2025)

Investigation into the design and application of alloy anodes for lithium-ion batteries - Tianhui Han; Qiqi Sun; Peng He; Dandan Han; Yonglei Xin; Guoling Li; Weidong Yu; Ying Zhao; Piaoping Yang; Zhiliang Liu (Chemical Engineering Journal, 2025)

Nanomaterial-powered immunotherapy: A next-generation therapeutic paradigm for bacterial infections - Xiaotong Sun; Shengnan Huang; Tong Ye; Lingfeng Xu; Yongfang Wang; Anqi Liu; Chao Liu; Yu Han; Mengfei Pang; Xuan Wu; Xin Pang (Chemical Engineering Journal, 2025)

Effect of upper seawater infiltration on submarine natural gas hydrate exploitation: using a pilot-scale fan-column simulator - Ling-Ban Wang; Yi-Fei Sun; Yu-Hao Bu; Zhen-Bin Xu; Xian Sun; Han-Feng Shao; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2025)

Experimental study of localized hydro-thermal-mechanical coupling characteristics of unsaturated silt under step-freezing conditions - Yu-zhi Zhang; Cheng-yan Li; Meng Wang; Yi-han Cui; You-cheng Sun (Cold Regions Science and Technology, 2025)

The recovery mechanism of granular sludge fragmentation and re-granulation caused by long-term high-concentration organic matter erosion in the SAD process: performance, sludge evolution, and metagenomic sequencing - Peng-fei Yu; Ding Wang; Yu-bo Fu; Xing-guan Ma; Hao Zheng; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Xing Jin (Bioresource Technology, 2025)

Unveiling dynamics of microbial communities, species interactions, and ecological assembly during low-temperature-induced sludge bulking in full-scale wastewater treatment systems - Han-Jun Sun; Xian Zhao; Jie Ding; Yu-Qian Wang; Wen-Shuo Wang; Zhi-Hua Feng; Sha Zhao; Liang Wang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2025)

Wuhapuella caenivorax gen. nov., sp. nov., a Novel Member of the Family Weeksellaceae, a Flocculent Bacteria Isolated from an Urban Sewage Treatment Plant - Yangyang Sun; Qianzhi Wang; Shunda Qiu; Changcui Chen; Siqi Wu; Na Gao; Han Chen; Jun Yu; Chunlei Yang; Hao Li; Shijie Bai; Dongru Qiu; et al. (Current Microbiology, 2025)

Efficient feature selection and fusion for real-time beef cattle detection - Yang Sun; Yamin Han; Xilong Feng; Hongming Zhang; Jie Wu; Yu Zhang; PeiJie Qin; Taoping Zhang (Computers and Electronics in Agriculture, 2025)

Harnessing PoSAP, a serum amyloid P component in Japanese flounder (Paralichthys olivaceus) for superior antibacterial immunity in teleost fish - Sheng-han Gao; Jia-qi Sun; Kun-yu Zhao; Gang Li; Jian Zhang; Xue-peng Li (Aquaculture, 2025)

An activatable aptamer probe Q2c for detection of grouper iridovirus - Mingzhu Liu; Jing Huang; Lin Huang; Qiwei Qin; Yanlei Chang; Lei Shi; Yun Sun; Yongcan Zhou; Shaowen Wang; Shuyu Han; Qing Yu; Pengfei Li (Aquaculture, 2025)

Predicting and understanding the performance of polyamide nanofiltration membrane for Li/Mg selective separation based on machine learning - Jing-Ou Sun; Tian-Wei Hua; Yan-Fang Guan; Han-Qing Yu (Water Research, 2025)

Antagonistic effect of changing salinity and dissolved organic carbon on N2O production via different pathways in saline lakes - Xiaoxi Sun; Beichen Wang; Jian Yang; Hui Yu; Bingfu Yao; Mingxian Han; Shenyan Dai; Teng Wen; Jibin Han; Xiying Zhang; Jinbo Zhang; Hongchen Jiang (Water Research, 2025)

Control system for soil microbes detrimental to trees using metabolites derived from algal bloom-causing microorganisms - Byung Sun Yu; Yujun Park; Seohyun Park; Jun-Woo Cho; Kyudong Han (Science of The Total Environment, 2025)

Numerical simulation of the methanol spray combustion process in a confined tube with obstacles - Zhuangzhuang Xu; Zhonghua Sheng; Han Sun; Xiaoxing Yang; Shengzheng Ji; Yue Yu; Guogang Yang (Process Safety and Environmental Protection, 2025)

Potential for hydroxamic acid modification via electronic effect: A case study of enhanced cassiterite flotation - Zhifeng Zhang; Yao Yu; Junhao Fu; Jian Cao; Chaozheng Deng; Wei Sun; Haisheng Han (Minerals Engineering, 2025)

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

Phosphorus strategy alters mechanism of microbial stress caused by soil arsenic contamination - Zhanghan Sun; Yanbin Du; Caihong Yu; XiaoXia Liu; Han Wang; Shengtao Shen; Zhiyuan Liu (Journal of Hazardous Materials, 2025)

Fe-modified biochar-driven ROS generation in the rhizosphere and their role in microplastic transformation - Zulqarnain Haider Khan; Han Yu; Hui Li; Syed Shabi Ul Hassan Kazmi; Ruixia Han; Muhammad Azeem; Xin Sun; Zia Ur Rehman; Gang Li (Journal of Hazardous Materials, 2025)

Dual bionic strategies to resist erosion of pipe elbows considering fluid drag - Haiyue Yu; Kaixin Sun; Leitong Shao; Junqiu Zhang; Zhiwu Han (Journal of Cleaner Production, 2025)

Enhanced comprehensive recovery of wolframite via novel aromatic heterocyclic hydroxamic acid in metal-based complex system - Zhifeng Zhang; Junhao Fu; Yao Yu; Haisheng Han; Wei Sun (Journal of Environmental Chemical Engineering, 2025)

Simultaneous accelerating H2O2 generation and activation via construction of CuS/NiS2 heterostructures in heterogeneous electro-Fenton for sulfamerazine degradation - Chenlin Wang; Chunhui Yu; Yuhan Ma; Fan Yang; Xinyang Sun; Kexin Wei; Junpu An; Li Li; Linlin Han; Kuobo Wang; Yongfeng Li (Journal of Environmental Chemical Engineering, 2025)

Nitrogen addition decouples the microbial necro-mass from soil organic carbon formation in a temperate grassland - Huanhuan Cheng; Yingbin Li; Shuo Li; Tianran Sun; Guoxiang Niu; Qi Li; Junjie Yang; Yanxia Ma; Yingzhi Gao; Qiang Yu; Haitao Zhao; Qiushi Ning; et al. (Journal of Environmental Sciences, 2025)

Exploring the limit of Cu-based small-pore zeolite framework collapse during hydrothermal aging in NO abatement from diesel vehicle exhaust - Wenqing Ding; Yu Sun; Jinpeng Du; Zhongqi Liu; Jingjing Liu; Tongliang Zhang; Wenpo Shan; Xiaoyan Shi; Sen Xue; Xuewang Han; Yunbo Yu; Yulong Shan; et al. (Journal of Environmental Sciences, 2025)

Variations in quality attributes of cow and goat milk subjected to microwave and high-pressure treatments over a two-week storage period - Nina Ding; Qiyue Sun; Zhongna Yu; Qijing Du; Rongbo Fan; Guangxu Ren; Liangliang You; Shuo Feng; Yongxin Yang; Rongwei Han (Innovative Food Science & Emerging Technologies, 2025)

Oxidative–textural coupling mechanisms in chicken breast stored at low-temperature gradients: Super-chilling as a quality preserving strategy - Jing Yi; Fei Chen; Han Li; Qianqian Yu; Chengfeng Sun; Rongxin Wen (Food Research International, 2025)

Co-microencapsulation of Lactobacillus paracasei and Inonotus obliquus polysaccharide in alginate system: Physicochemical and functional properties - Yilin Sun; Jing Han; Huilin Zhang; Wenyan Li; Yujun Jiang; Yu Zhang; Ling Guo (Food Hydrocolloids, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Centennial-scale evolution, source apportionment, and ecological risks of heavy metals in Daya Bay, South China sea - Xiangtian Man; Jian Sun; Yu Xiang; Hong Su; Honghui Huang; Yangguang Gu; Han Zhang; Richard W. Jordan; Shijun Jiang (Environmental Pollution, 2025)

Chloride ion-driven activation of Ru-CeO2 for efficient methoxycarbonylation of long-chain alkenes - Yi-Ran Du; Yi-Yu Tao; Jing-Wen Sun; Han-Sheng Li; Rui Zhang; Bao-Hua Xu (Chemical Engineering Journal, 2025)

Ultrarobust eutectogels with nanophase separation structure for self-damping pressure sensing - Zong-Ju Chen; Yu-Qiong Sun; Zi-Han Zhao; Li-Jia Pan; Cheng-Hui Li (Chemical Engineering Journal, 2025)

Synergistic microaerobic bio-decontamination of dimethyl sulfide and elemental mercury in the low-O2 content flue gas by a sulfur-oxidizing membrane biofilm reactor - Han-Biao Yang; Lu-Lu Sun; Xiu-Qin Tan; Yuan Zeng; Yu-Qi Huang; Zhen-Shan Huang; She-Jun Chen; Zai-Shan Wei (Chemical Engineering Journal, 2025)

Dissimilatory nitrate reduction to ammonium pathway during composting: Insight into key factors, functional microbes, and multi-factor interactions - Shuai Shi; Jiaxin Bao; Donghui Lv; Yonghui Xu; Zhiheng Guo; Jingjie Zhang; Shuai Ren; Yue Han; Ruixin Bi; Nana Jiang; Ning Wang; Jie Pan; et al. (Chemical Engineering Journal, 2025)

Microwave−assisted synthesis of NIR electrochemiluminescence Au nanoclusters with triethanolamine−Au nanoparticles/Co3O4/NiCo2O4 as co−reactant accelerator for miRNA−107 detection - Qiao Zhang; Lei Yu; Fangfang Liu; Jimei Song; Xing Gao; Yue Sun; Yuxiao Li; Yen Leng Pak; Quanxiang Han; Zhao Wang; Yan Huang; Jibin Song (Chemical Engineering Journal, 2025)

Conjugation-driven electronic structure engineering of halogenated indolequinones for bidirectional catalysis in lithium-sulfur batteries - Shiyao Liu; Hongmin Yu; Zhenhua Liu; Yueyue Zhang; Yutong Han; Yixuan Gu; Yuxuan Li; Zongtao Li; Zhao Wang; Hao Sun (Chemical Engineering Journal, 2025)

Causal Matrix Long Short-Term Memory Network for Interpretable Significant Wave Height Forecasting - Mingshen Xie; Wenjin Sun; Ying Han; Shuo Ren; Chunhui Li; Jinlin Ji; Yang Yu; Shuyi Zhou; Changming Dong (Journal of Marine Science and Engineering, 2025)
This study proposes a novel causality-structured matrix long short-term memory (C-mLSTM) model for significant wave height (SWH) forecasting. The framework incorporates a two-stage causal feature selection methodology using cointegration testing and Granger causality testing to identify long-term stable causal relationships among variables. These relationships are embedded within the C-mLSTM architecture, enabling the model to effectively capture both temporal dependencies and causal information within the data. Furthermore, the model integrates Bayesian optimization (BO) and twin delayed deep deterministic policy gradient (TD3) algorithms for synergistic optimization. This combined TD3-BO approach achieves an 11.11% improvement in the mean absolute percentage error (MAPE) on average compared to the base model without optimization. For 1–24 h SWH forecasts, the proposed TD3-BO-C-mLSTM outperforms the benchmark models TD3-BO-LSTM and TD3-BO-mLSTM in prediction accuracy. Finally, a Shapley additive explanations (SHAP) analysis was conducted on the input features of the BO-C-mLSTM model, which reveals interpretability patterns consistent with the two-stage causal feature selection methodology. This research demonstrates that integrating causal modeling with optimization strategies significantly enhances time-series forecasting performance.

Faster soil organic carbon turnover in MAOM versus POM: straw input causes larger microbial driven soil organic carbon decomposition but higher straw accumulation in MAOM - Xiongsheng Yu; Lili Wang; Qiang Wang; Guoyan Zhou; Han Sun; Georg Guggenberger; Yongfu Li; Kuzyakov Yakov; Yu Luo; Yingyi Fu (Soil and Tillage Research, 2025)

Adsorption configuration control on Pt-Bi2O3 for the oriented conversion of glycerol to glyceric acid via terminal hydroxyl oxidation - Han-Yue Yang; Bin Sun; Xue Xiao; Xuan Ai; Rui-Bin Jiang; Pei Chen; Yu Chen (Science Bulletin, 2025)

Deciphering the microbial mechanisms underlying glucose induced soil priming effects under low and high nutrient levels - Jiaqi Wang; Xichang Zhang; Yingyi Fu; Lukas Van Zwieten; Han Sun; Georg Guggenberger; Lingfei Hu; Yu Luo; Tida Ge; Yakov Kuzyakov (European Journal of Soil Biology, 2025)

Injectable short-fiber hydrogel with fatigue resistance and antibacterial properties for synergistic periodontitis therapy - Zhihui Han; Luhan Bao; Yuedi Yu; Yue Zhao; Manying Wang; Yang Sun; Minna Fu; Qianrong Zhou; Wenjuan Liu; Wenguo Cui; Youcheng Yu (Chemical Engineering Journal, 2025)

“One-two punch” strategy: A H2O2 self-sufficient nanosystem for efficient cervical cancer therapy via senescence induction and clearance - Lan Yu; Weiqiang Han; Jing Zhang; Guoxin Liu; Hongjuan Li; Yongqian Xu; Fengyu Liu; Shiguo Sun (Chemical Engineering Journal, 2025)

Optimizing patterned laser-induced graphene strain sensors via novel piezoresistive modeling and multi-objective analysis - Jia-Chen Shang; Wen-Feng Pan; Wen-Hao Zhao; Heng Yang; Yu-Yi Chen; Rui Wang; Ri-Han Wang; Ling-Yu Sun; Yao-Guang Cao; Shi-Chun Yang (Chemical Engineering Journal, 2025)

Determination of the deposition of urban submicron aerosols in the human respiratory tract considering hygroscopic growth - Aoyuan Yu; Jiayuan Lu; Xiaojing Shen; Xinyao Hu; Yangmei Zhang; Quan Liu; Hongfei Tong; Linlin Liang; Lei Liu; Qianli Ma; Lujie Han; Huizheng Che; et al. (Atmospheric Environment, 2025)

Sustained exposure to triclocarban and triclosan at environmental relevant concentration disrupts gut-liver axis in the black-spotted frog - Bingyi Wang; Wenhui Sun; Xindi Ye; Tyler D. Hoskins; Yu Han; Xia Yuan; Qi Chen; Zhiquan Liu; Hangjun Zhang (Aquatic Toxicology, 2025)

Nutrient-mediated changes in growth, biochemical composition, and biosilica deposition in Cyclotella cryptica - Yuting Yu; Yan Sun; Yuhang Li; Zhengfeng Zhu; Lin Zhang; Jian Li; Spiros N. Agathos; Chengxu Zhou; Jichang Han (Journal of Oceanology and Limnology, 2025)

ODP: A novel indicator for estimating photosynthetic capacity and yield of maize through UAV hyperspectral images - Shaolong Zhu; Tianle Yang; Dongwei Han; Weijun Zhang; Muhammad Zain; Qiaoqiao Yu; Yuanyuan Zhao; Fei Wu; Zhaosheng Yao; Tao Liu; Chengming Sun (Computers and Electronics in Agriculture, 2025)

Membranal phosphatidylglycerol enhances oxygen diffusion and release from cyanobacteria - Jian-Lu Duan; Yi Han; Xiao-Yu Liu; Mei-Yan Liu; Yu-Chen Sun; Jing-Ya Ma; Xiao-Dong Sun; Yue Wang; Miao-Miao Tan; Bo Gong; Xian-Zheng Yuan (Water Research, 2025)

Novel L1A/C RFLP 1–3-4 porcine reproductive and respiratory syndrome virus causing severe intestinal infections in China - Bo Han; Yi-han Lu; Jiu-ying Sun; Xin-lei Li; Wen-juan Zhang; Xiao-xue Yu; Gang Xu; Dao-wen Li; Xue-jiao Cheng; Chun-xue You; Ying-Feng Sun (Veterinary Microbiology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Improved antifouling and regeneration capability of polyaniline-modified halloysite nanotube/MXene composite membranes - Jing-Yi Feng; Wen-Hao Geng; Ru-Yu Chang; Yu-Han Wang; Yue-Xin Wang; Ze-Long Bao; Wen-Yi Sun; Lu-Yao Tian; Di Zhang; Hong-Zhang Geng (Journal of Water Process Engineering, 2025)

Machine learning based prediction by PlantCdMiner and experimental validation of cadmium-responsive genes in plants - Chaoqun Xu; Ling Sun; Lu-Dan Zhang; Ze-Jun Guo; Ji-Cheng Wang; Li-Han Zhuang; Dong-Na Ma; Ling-Yu Song; Jing Li; Qian-Su Ding; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2025)

Sustainable valorization of Haematococcus pluvialis cell wall residues: Functional biomaterial development for skin health - Miyang Han; Sejin Cheon; Young Mok Heo; Seunghyun Kang; Byung Sun Yu; Kyudong Han (Journal of Environmental Chemical Engineering, 2025)

Efficient moisture energy harvesting through electronegativity enhancement and dual-gradient asymmetric structural design - Mingxing Jing; Yiyang Fu; Yu Yang; Hongyuan Zhu; Wensheng Wang; Han Wu; Zhuangzhi Sun (Journal of Environmental Chemical Engineering, 2025)

Self-assembly of Zein-based nanoparticles for oral isoliquiritigenin delivery against Salmonella infections - Cang Li; Yu Huang; Yuchen Liu; Zhipeng Li; Yao Deng; Hao Ren; Donghao Zhao; Lu Han; Jian Sun (Innovative Food Science & Emerging Technologies, 2025)

Application of electrospun biomimetic packaging materials for prolonged preservation and quality retention of Mongolian cheese - Yu Hao; Jiaxing Han; Qi Cao; Yaxin Yu; Chaoping Jiang; Lingling Wu; Peng Zhang; Wenxiu Sun (International Dairy Journal, 2025)

In situ construction of an organic/metal bridging interface toward zinc metal anode with ultra-long cycle life of 5000 h - Zhe Gong; Han Yu; Zhuo Li; Chenyi Yang; Feifei Gao; Pengfei Wang; Na Sun; Mingdong Zhou; Kai Zhu; Yaguang Sun (Chemical Engineering Journal, 2025)

Chemical composition and chemotaxonomic studies on the roots of Angelica acutiloba - Zhi-Xia Sun; Fei-Fei Geng; Han-Yu Zhang; Yong-Hu Chen; Zhe Jiang; Xue-Zheng Li (Biochemical Systematics and Ecology, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Corrigendum to “Design, hydrodynamic analysis, and test of a manta ray-inspired soft wing for flapping wing propulsion of underwater gliders” [Ocean Eng. 327 (2025) 120998] - Yudong Guo; Yuting Li; Xiao Yu; Libing Han; Wendong Niu; Tongshuai Sun (Ocean Engineering, 2025)

Urban landscape lakes with backwater hide higher antibiotic resistance risk than living water - Qian Han; Yu Wang; Chenwei Shi; Yuan Qian; Xiaochen Wang; Sijie Wang; Xiaofang Sun; Qiaoling Yu; Huan Li (Journal of Hazardous Materials, 2025)

NLRC3 regulates RIP2, STING, TBK1, and TRAF6 mediated type I IFN signaling and inflammatory response in large yellow croaker Larimichthys crocea - Yu Qing Xu; Ying Li; Kun Huang Han; Jia Xi Zhang; Kai Qing Li; Jing Jiang; Zhao Han Sun; Yi Lei Wang; Yong Hua Jiang; Peng Fei Zou (Fish & Shellfish Immunology, 2025)

A bionic yeast for the colon-targeted delivery of curcumin in the treatment of inflammatory bowel disease - Dunsheng Liang; Xiao-Fan Shen; Ting-Ting Li; Yao Deng; Hong-Liang Xiao; Zhi-Peng Li; Shuan-Cheng Bai; Xiao-Yu Ma; Xiao-ping Liao; Dong-Hao Zhao; Hao Ren; Chaoqun Zhang; et al. (Chemical Engineering Journal, 2025)

Hydrated eutectic electrolytes with decoupled weakly hydrogen bonded solvated structures enable fast kinetics for high-performance zinc-ion batteries - Wenruo Li; Xinyao Dong; Farva Ilyas; Haoyuan Zhu; Luzheng Zhao; Wei Liu; Weiqiang Kong; Xu Han; Jiancong Guo; Zaoyan Yu; Yushuai Song; Zhensheng Guan; et al. (Chemical Engineering Journal, 2025)

Fungal network and plant metabolites drive the assembly of the peanut root microbiome - Chen-Yu Ma; Xiao-Han Wu; Hao-Ming Wang; Xiang-Yu Zhang; Yan-Jun Fei; Shi-Yi Huang; Yi-Bo Wu; Zi-Han Zhao; Hui-Jun Jiang; Kai Sun; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

Single-cell RNA sequencing generates an atlas of normal tibia cartilage under mechanical loading conditions - Junjie Wang; Zewen Sun; Chenghao Yu; Haibo Zhao; Mingyue Yan; Shenjie Sun; Xu Han; Tianrui Wang; Yingze Zhang; Jianjun Li; Tengbo Yu (Molecular and Cellular Biochemistry, 2025)

Response of diatoms to environmental changes in the Porphyra cultivation system in Haizhou Bay using GBT model and GAM - Shuo Chen; Haibin Han; Jinchen Yu; Tao Sun; Jin Zhou (Marine Pollution Bulletin, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Cryptochromes (CRYs) in pepper: Genome-wide identification, evolution and functional analysis of the negative role of CaCRY1 under Phytophthora capsici infection - Fei Sun; Yue Chen; Ying Luo; Feng Yang; Ting Yu; Huibin Han; Youxin Yang; Yong Zhou (Plant Science, 2025)

Research on speed optimization of fixed route ship with low data dependence - Chaodong Hu; Yu Wang; Xu Han; Hui Liu; Qun Sun; Bo Zhou (Ocean Engineering, 2025)

Metabolic and ecological responses of denitrifying consortia to different carbon source strategies under fluctuating C/N conditions - Rui-Zhe Sun; Yuan Pan; Jun Wang; Tong Gao; Han-Qing Yu; Jin Wang (Environmental Research, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

Bead-free digital enzyme-linked immunoassay on PDMS microwell array - Han Wu; Huaiheng Zhou; Zhanqiang Sun; Jiayao Fang; Weiran An; Xiaoli Yu; Bo Zheng (Analytica Chimica Acta, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Design, hydrodynamic analysis, and test of a manta ray-inspired soft wing for flapping wing propulsion of underwater gliders - Yudong Guo; Yuting Li; Xiao Yu; Libing Han; Wendong Niu; Tongshuai Sun (Ocean Engineering, 2025)

Two E-clade protein phosphatase 2Cs enhance ABA signaling by dephosphorylating ABI1 in Arabidopsis - Ya Zhang; Liyuan Han; Junjie Liu; Miao Chang; Chuanling Li; Jian-Xiu Shang; Zhiping Deng; Wenqiang Tang; Yu Sun (Molecular Plant, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Converting static to Dynamic: Biomimetic Ultra-Sensitive Wide-Range flexible pressure sensor inspired by the Contact-Regulation process of scorpion pectines - Junqiu Zhang; Jiachao Wu; Lili Liu; Xiangbo Gu; Xueping Zhang; Xueyang Li; Zijian Shi; Yu Chen; Jiqi Gao; Junfeng Zhang; Tao Sun; Honglie Song; et al. (Chemical Engineering Journal, 2025)

CD38 Coordinates with NF-κB to Promote Cochlear Inflammation in Noise-Induced Hearing Loss: the Protective Effect of Apigenin - Da Liu; Na Sai; Ying Zhou; Ning Yu; Qing-qing Jiang; Wei Sun; Wei-ju Han; Weiwei Guo (Molecular Neurobiology, 2025)

Anti-ferroptosis effects of undescribed abietane diterpenoids from Prunella vulgaris subsp . hispida (Benth.) Hultén - Heng-Li Yan; Xiao-Qiao Yang; Han-Fei Liu; Fen-Cong Pan; Jin-Yu Li; Wei-Dong Pan; Ni Zhang; Hua-Yong Lou; Chao Sun (Natural Product Research, 2025)

Spatially explicit land use of manufacturing sectors and its biodiversity impacts in China - Yutao Wang; Zhixiu Han; Yiru Song; Chen Sun; Lin Sun; Huajun Yu (Resources, Conservation and Recycling, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Theoretical analysis on absorption heat transformers boosted multi-effect distillation system for ocean thermal energy conversion - Suyun Yi; Zhixiang Zhang; Han Yuan; Yu Bai; Yongchao Sun; Wenyi Peng; Ning Mei; Yonggong Yuan; Tao Jiang (Desalination, 2025)

Recurrence of Cerebral Arteriovenous Malformation Following Complete Obliteration Through Endovascular Embolization - Qiang Hao; Haibin Zhang; Heze Han; Hengwei Jin; Li Ma; Ruinan Li; Zhipeng Li; Anqi Li; Kexin Yuan; Qinghui Zhu; Ke Wang; Runting Li; et al. (Translational Stroke Research, 2025)

Allopatric Speciation and Interspecific Gene Flow Driven by Niche Conservatism of Diploderma Tree Lizards in Taiwan - Tzong‐Han Lin; Zong‐Yu Shen; Ming‐Hsun Chou; Pei‐Wei Sun; Chin‐Chia Shen; Jen‐Pan Huang; Si‐Min Lin (Molecular Ecology, 2025)
Allopatric speciation is a widely accepted hypothesis for species distributed across geographic barriers. Meanwhile, niche conservatism, the tendency of species to retain their ancestral ecological traits, helps reinforce genetic differentiation by stabilising species distributions over time and reducing the role of competition in shaping range boundaries. In contrast, hybridisation can occur at the edges of distribution after secondary contact following climatic or geological events, leading to a reduction in genetic divergence between divergent lineages. In this study, we investigated the role of geographic barriers, niche conservatism and gene flow in the speciation history of Diploderma species in Taiwan, where geographically distinct taxa share similar environmental preferences. By using ddRAD‐seq data, seven distinct genetic clusters were identified with two putatively new cryptic species in D. brevipes and D. polygonatum . Most sister species pairs share similar climatic niches based on niche equivalency and similarity tests. We further detected significant historical gene flow between lineages of D. brevipes and D. polygonatum , where secondary contact might have occurred because of palaeoclimate changes and historical demographic expansion. Our results demonstrate that niche conservatism does not always act in concert to strengthen the result of allopatric speciation; instead, it may also lead to gene flow between divergent lineages following secondary contact. On the other hand, postdivergence gene flow may be a creating force generating phenotypic diversity in sexually selected traits in our study system. The underestimated species diversity of Diploderma in Taiwan requires further taxonomic work in the future.

Flame extension characteristics and the temperature profile below the tunnel ceiling with various source-ceiling heights - Xiepeng Sun; Fei Ren; Yong Yang; Yu Han; Xiang Fang (Tunnelling and Underground Space Technology, 2025)

Unprecedented short-circuit current density and efficiency of vacuum-deposited organic solar cells based on 8H-thieno[2′,3′:4,5]thieno[3,2-b] thieno[2,3-d]pyrrole - Bin-Wen Chen; Ming-Wei An; Kang Wang; Sang Young Jeong; Xu Wang; Zhen-Lin Qiu; Kun Cao; Shan-Yu Zheng; Lu Wang; Han Young Woo; Da-Qin Yun; Lin-Long Deng; et al. (Science Bulletin, 2025)

Coprecipitates between iron oxides and biodegradable organic acids for boosting Fenton-like catalysis under neutral pH conditions - Yulu Zhang; Shiming Zhang; Huali Yu; Haiyan Guo; Xuewei Dong; Lei Han; Hong Sun; Lianfeng Wang (Journal of Environmental Management, 2025)

Development of zebrafish (Danio rerio) mesh-type model at multi-life stages and Monte Carlo simulations of dosimetric parameters - Huiyuan Xue; Wenxing Xu; Xiaotong Gao; Han Gao; Xinjie Wang; Jin Gao; Yidi Wang; Kaijin Yan; Tao Wu; Jiahao Guo; Binquan Niu; Mingxu Zheng; et al. (Journal of Environmental Radioactivity, 2025)

Synergistic neurotoxicity of clothianidin and photoaged microplastics in zebrafish: Implications for neuroendocrine disruption - Ping Ding; Yajing Han; Yanan Sun; XiaoXia Chen; Qing Ge; Wei Huang; Lijuan Zhang; Adela Jing Li; Guocheng Hu; Yunjiang Yu (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

S–Mo conversion stimulates soil electron transfer and hydrocarbon removal for nearly one year - Jialu Sun; Xiaojuan Yi; Yuewei Yang; Yun Zhang; Xin Yu; Side Yang; Xiaolin Zhang; Ting Han; Xinhong Peng; Xiaojing Li (Chemical Engineering Journal, 2025)

Achieving the ‘Golden Mean’ in ionic liquid-based electrolytes through ether functionalization: Enhanced lithium-ion conductivity and robust interphases - Taohong He; Bofang Shi; Xiangming Cui; Yushan Han; Hang Ma; Shiyi Sun; Jingchun Hou; Xiaofei Wang; Mingtao Li; Mingbo Ma; Qi Yu; Jianan Wang; et al. (Chemical Engineering Journal, 2025)

Multifunctional flexible MXene/TA@CNC electronic hydrogel patch with robust adhesion and self-healing properties for wearable electronics - Haoyu Wang; Ping Han; Ying Yu; Shaolong Han; Yue Qiao; Yuehan Li; Bin Sun; Zheng Gu (Chemical Engineering Journal, 2025)

Rapid Mapping of Quantitative Trait Loci for the Growth Habit in Peanuts Using Bulked Segregant Analysis - Qia Ning; Li Li; Hailong Liu; Xiaoshu Chen; Yongchao Lv; Xiaoping Sun; Yue Zhao; Meijun Li; Huayuan Gao; Yu Han; Ridan Sun; Lianxi Zhang (Plant Molecular Biology Reporter, 2025)

The overlooked shadow killer: Elizabethkingia anophelis as a potent pathogen in American bullfrogs (Aquarana catesbeiana) - Chun Liu; Han Lin; Jie Ma; Yebing Yu; Ruinan Wang; Xinyi Tang; Jingyang Sun; Zhendong Qin; Biao Jiang; Wei Li; Youlu Su; Li Lin (Aquaculture, 2025)

Spatial distribution of bacterial communities driven by environmental factors in the sediment of Lateolabrax japonicus ponds - Yu-Min Xu; Zheng Zhu; Wu-Lang Luo; Wei Huang; Jun-Han Liang; Hong-Yan Sun; Qi-Wei Qin (Aquaculture, 2025)

Cadmium induces spontaneous abortion by impairing endometrial stromal cell decidualization - Xue-Ke Zhang; Xuan Li; Xing-Xing Han; Dong-Ying Sun; Yu-Qin Wang; Zi-Zhuo Cao; Lu Liu; Zi-Han Meng; Guo-Jing Li; Yu-Jie Dong; Dan-Yang Li; Xiao-Qing Peng; et al. (Toxicology, 2025)

A Self-adaptive two stage iterative greedy algorithm based job scales for energy-efficient distributed permutation flowshop scheduling problem - Yang Yu; Quan Zhong; Liangliang Sun; Yuyan Han; Qichun Zhang; Xuelei Jing; Zhujun Wang (Swarm and Evolutionary Computation, 2025)

Corrigendum to “Maternal Zearalenone exposure impacted ovarian follicle formation and development of suckled offspring” [Sci. Total Environ. 788 (2021) 147792] - Li Kong; Ai-Hong Zhao; Qian-Wen Wang; Yan-Qin Feng; Zi-Hui Yan; Ming-Hao Li; Fa-Li Zhang; Han Wang; Kai-Yu Shen; Ying Liu; Yu-Jiang Sun; Wei Shen; et al. (Science of The Total Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Neoarchean orogenic belt evolution in the northeast North China Craton: Implications for the reconstruction of early Earth’s microplates - Guozheng Sun; Shuwen Liu; Sanzhong Li; Timothy M. Kusky; Fangyang Hu; Han Bao; Lei Gao; Yalu Hu; Shengyao Yu; Liming Dai; Lintao Wang; Xi Wang (Precambrian Research, 2025)

Boosting chlorobenzene oxidation over MIL-101(Cr) derived CrOx catalysts: The stepwise regulation of CrOx clusters and oxygen species by calcination atmospheres - Boqiong Jiang; Jun Liu; Keyan Wei; Hanfeng Lu; Xiaole Weng; Jingyi Han; Yi Zhang; Shaocai Yu; Yuhai Sun (Journal of Hazardous Materials, 2025)

High-resolution characterization of rhizosphere oxygen (O2) dynamics in different wetland plant species after light/dark transitions - Ye Zheng; Zhihong Zhang; Yu Sun; Zhaode Wang; Jianeng Chen; Narangerel Serdyanjiv; Odsuren Batdelger; Chao Han (Flora, 2025)

Corrigendum to ‘Mechanisms of imbalanced testicular homeostasis in infancy due to aberrant histone acetylation in undifferentiated spermatogonia under different concentrations of Di(2-ethylhexyl) phthalate (DEHP) exposure’ [Environ. Pollut. 347 (2024) 123742] - Yu Tian; Jiachen Guo; Lei Hua; Yinuo Jiang; Wei Ge; Xiaoyuan Zhang; Diya Cai; Dongliang Lu; Bin Wang; Wei Shen; Zhongyi Sun; Baoquan Han (Environmental Pollution, 2025)

Constructing a low-cost total Ce(III)-based adsorbent for efficient removal and recovery of phosphate - Tao Zhang; Junle Li; Dongqing Liu; Yuling Ma; Yu Han; Sujie Shan; Kai Sun; Elena V. Zelinskaya; Aijie Wang; Hongliang Sun; Wei Wang (Chemical Engineering Journal, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Dorsal CA1 NECTIN3 Reduction Mediates Early-Life Stress-Induced Object Recognition Memory Deficits in Adolescent Female Mice - Yu-Nu Ma; Chen-Chen Zhang; Ya-Xin Sun; Xiao Liu; Xue-Xin Li; Han Wang; Ting Wang; Xiao-Dong Wang; Yun-Ai Su; Ji-Tao Li; Tian-Mei Si (Neuroscience Bulletin, 2025)

Transcriptome Sequencing Reveals Effects of Artificial Feed Domestication on Intestinal Performance and Gene Expression of Carnivorous Mandarin Fish (Siniperca chuatsi) and Related Mechanisms - Jia-Xing Luo; Xiao-Tian Gao; Zhen Rong; Li-Han Zhang; Yan-Feng Sun; Zun-Li Qi; Qi Yu; Khor Waiho; Wei-Xu Zhao; Yi-Huan Xu; Chun-Long Zhao; Cheng-Bin Wu (Marine Biotechnology, 2025)

Effect of heat exposure on histology, transcriptomics and co-expression network: A synthetic study in Japanese flounder (Paralichthys olivaceus) - Ping Han; Mingzhe Yuan; Zhennan Sun; Yadong Xue; Xiumei Liu; Jianming Chen; Haiyang Yu; Xubo Wang (Aquaculture, 2025)

Eliminating the effect of pH: Dual-matrix modulation adsorbent enables efficient lithium extraction from concentrated seawater - Yu Han; Liuqian An; Yan Yang; Yuling Ma; Hongliang Sun; Jinxin Yao; Tao Zhang; Wei Wang (Water Research, 2025)

Iron oxides promote physicochemical stabilization of carbon despite enhancing microbial activity in the rice rhizosphere - Han Sun; Xiaomin Ma; Lukas Van Zwieten; Yu Luo; Robert W. Brown; Georg Guggenberger; Sheng Tang; Yakov Kuzyakov; Peduruhewa H. Jeewani (Science of The Total Environment, 2025)

A bottom-up nationwide analysis of sectoral land use reveals spatial heterogeneity across the United States - Zhixiu Han; Wei Xie; Yiru Song; Lin Sun; Huajun Yu; Bin Chen; Yang Li; Yutao Wang (Resources, Conservation and Recycling, 2025)

Chemotaxis of rhizosphere Pseudomonas sp. induced by foliar spraying of lanthanum reduces cadmium uptake by pakchoi - Meng Wang; Lei Yu; Jing Wang; Luyao Qin; Xiaoyi Sun; Jiaxiao Liu; Yun Han; Shibao Chen (Journal of Hazardous Materials, 2025)

Development of “environmentally friendly” super Escherichia coli strains that can completely biodegrade toluene - Yu Wang; Cen Qian; Yong-Dong Deng; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Yuan-Zhang Sun; Hong-Juan Han; Wen-Hui Zhang; Hao Zhang; et al. (Chemical Engineering Journal, 2025)

Ultrasound-Targeted β-Catenin Gene Therapy Improves the Cardiac Function in Mice After Myocardial Infarction - Lei Yang; Tong Gao; Yu Huang; Pei-he Wang; Xin-hao Han; Jie Wu; Lei Huang; Qing-en Da; Kun-fu Ouyang; Zhen Han; Hai Tian; Lu Sun (Cardiovascular Toxicology, 2025)

A novel ATP2A2 mutation in Darier and genotype phenotype: correlation analysis - Xiaofen Guo; Juan Du; Mingwei Lv; Yi Hu; Qi Zhen; Weiwei Chen; Yirui Wang; Zhuo Li; Chunmeng Liu; Xinyu Feng; Wanli Niu; Yu Zhang; et al. (Genes & Genomics, 2025)

Modulation of an omega-3 fatty acid desaturase for eicosapentaenoic acid biosynthesis in the alga Nannochloropsis oceanica - Jie Zheng; Ying Shi; Lihua Yu; Han Sun; Wenguang Zhou; Jin Liu (Algal Research, 2025)

Sonar-Based Simultaneous Localization and Mapping Using the Semi-Direct Method - Xu Han; Jinghao Sun; Shu Zhang; Junyu Dong; Hui Yu (Journal of Marine Science and Engineering, 2024)
The SLAM problem is a common challenge faced by ROVs working underwater, with the key issue being the accurate estimation of pose. In this work, we make full use of the positional information of point clouds and the surrounding pixel data. To obtain better feature extraction results in specific directions, we propose a method that accelerates the computation of the two-dimensional SO-CFAR algorithm, with the time cost being only a very slight increase compared to the one-dimensional SO-CFAR. We develop a sonar semi-direct method, adapted from the direct method used in visual SLAM. With the initialization from the ICP algorithm, we apply this method to further refine the pose estimation. To overcome the deficiencies of sonar images, we preprocess the images and reformulate the sonar imaging model in imitation of camera imaging models, further optimizing the pose by minimizing photometric error and fully leveraging pixel information. The improved front end and the accelerated two-dimensional SO-CFAR are assessed through quantitative experiments. The performance of SLAM in large real-world environments is assessed through qualitative experiments.

Integrating rhizosphere bacterial structure and metabolites with soil Cd availability in different parent paddy soils - Jing Wang; Meng Wang; Lei Yu; Xiaoyi Sun; Luyao Qin; Jiaxiao Liu; Yun Han; Shibao Chen (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Overexpression of GmSRC2 confers resistance to Phytophthora sojae in soybean - Sushuang Deng; Yu Zhang; Xiaowan Fang; Han Gou; Ruidong Sun; Huidong Xuan; Haitang Wang; Jinming Zhao; Han Xing; Na Guo (Plant Science, 2024)

Adaptive fuzzy quantized state feedback control for AUVs with model uncertainty - Yaning Han; Jiapeng Liu; Jinpeng Yu; Chongwei Sun (Ocean Engineering, 2024)

Synthesis of CoFe2O4@C based on Fe/Co-BTC for efficient detection, determination and degradation of nitenpyram residue: An electrochemical study, condition optimization and mechanism - Yuan-Zhen Wang; Guo-Qiang Xu; Yu-Han Sun; Liu Yang; Yu-Long Liu; Ying Fu (Journal of Cleaner Production, 2024)

A generalized Faustmann model with multiple carbon pools - Zhihan Yu; Zhuo Ning; Han Zhang; Hongqiang Yang; Sun Joseph Chang (Forest Policy and Economics, 2024)

d-Allulose production via a simplified in vitro multienzyme cascade strategy: Biosynthesis and crystallization - Han Zhang; Zhen Sun; Xinling Du; Qianqian Cheng; Fuchun Ji; Zishen Nie; Julei Zhan; Zhouping Wang; Aitao Li; Irina Delidovich; Yu Xia (Food Bioscience, 2024)

Unappreciated role of secondary metabolism-derived small mediators in degrading bisphenol A and antibiotics by a laccase-expressing fungus - Kai Sun; Zi-Hao Wu; Jie Liu; Zhou-Hua Cheng; Dong-Feng Liu; Hui Lin; Han-Qing Yu (Environmental Pollution, 2024)

Hinokiflavone from Platycladi cacumen as a potent broad-spectrum inhibitor of gut microbial Loop-1 β-glucuronidases: Inhibition kinetics and molecular simulation - Yue Han; Yu-Tong Liu; Lu Chen; Hao-Fan Sun; Guang-Hao Zhu; Dong-Ning Kang; Qi Zhou; Hui Tang; Yu-Ling Yin; Jie Hou (Chemico-Biological Interactions, 2024)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

Similarity of Chinese and Pakistani oral microbiome - Xiaofang Sun; Binghua Han; Qian Han; Qiaoling Yu; Sijie Wang; Jie Feng; Tianshu Feng; Xiaoshan Li; Shiheng Zhang; Huan Li (Antonie van Leeuwenhoek, 2024)

Life cycle carbon emission assessment and carbon payback period analysis for the regeneration of old residential areas in cold regions: Case study in Qingdao, China - Baodi Sun; Chenghao Zhong; Dehu Yu; Qing Han; Jingchao Tang (Sustainable Cities and Society, 2024)

Niche expansion of archaeocyaths during their palaeogeographic migration: Evidence from the Chengjiang Biota - Aihua Yang; Cui Luo; Jian Han; Andrey Yu. Zhuravlev; Joachim Reitner; Haijing Sun; Han Zeng; Fangchen Zhao; Shixue Hu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

To be or not to be: The fate of submerged macrophyte biodiversity in the plateau lakes after restoration for the last decade - Qingxiang Han; Junyao Sun; Qingchuan Chou; Te Cao; Wei Li; Yu Cao (Journal of Environmental Management, 2024)

Arginine alleviates LPS-induced leukocytes inflammation and apoptosis via adjusted NODs signaling - Yuan-Xin Qian; Feng-Feng Zhou; Qiang Chen; Fen Dong; Han-Ying Xu; Yu-Long Sun; Ji-Teng Wang; Tao Han (Fish & Shellfish Immunology, 2024)

Aging mechanism of Ni-rich cathode-based lithium-ion batteries: Focusing on upper cut-off voltages - Fengfei Wang; Shengjin Tang; Xuebing Han; Yu Wu; Languang Lu; Chuanqiang Yu; Xiaoyan Sun; Minggao Ouyang (Chemical Engineering Journal, 2024)

Construction of PTFE/PI-PI/PANI-PA composite nanofibrous membrane for efficient photothermal membrane distillation and VOCs interception - Jingge Ju; Jun Yu; Tiantian Zhang; Yan Zhang; Yanfei Chen; Jiacheng Han; Ying Sun; Weimin Kang (Chemical Engineering Journal, 2024)

Regulation of N Zn O bonds via carbonized polymer dots in polyaniline composite cathode for high performance stable aqueous Zn-ion batteries - Bao-Hong Xu; Yi-Han Song; Guo-Duo Yang; Jia-Yu Zhang; Yu-Qi Liu; Jie-Qiong Liu; Qi-Meng Zhang; Xing-Long Wu; Ming-Xiao Deng; Hai-Zhu Sun (Chemical Engineering Journal, 2024)

Experimental study on the transitional behavior of the room fire under sub-atmospheric pressures - Xiepeng Sun; Yu Han; Xiang Fang; Xiaolei Zhang; Fei Tang; Longhua Hu (Chemical Engineering Journal, 2024)

Projected urban flood risk assessment under climate change and urbanization based on an optimized multi-scale geographically weighted regression - Feifei Han; Jingshan Yu; Guihuan Zhou; Shuang Li; Tong Sun (Sustainable Cities and Society, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Non-enzymatic electrochemical sensor based on ionic liquid [BMIM][PF6] functionalized zirconium‑copper bimetallic MOF composite for the detection of nitrite in food samples - Li Zhang; Yu Han; Ming Sun; Shaobin Li (Food Chemistry, 2024)

Crosslinking ability of hydrolyzed distarch phosphate and its stabilizing effect on rehydrated sea cucumber - Jiaqi Yu; Wenhao Ge; Kaifeng Wang; Wenhui Hao; Shangju Yang; Ying Xu; Tingyu Feng; Peng Han; Xun Sun (Food Chemistry, 2024)

Evaluation of forage quality in various soybean varieties and high-yield cultivation techniques - Baiquan Sun; Shan Yuan; Mahmoud Naser; Yanfeng Zhou; Hongchang Jia; Yang Yu; Xiangyu Yao; Tingting Wu; Wenwen Song; Bingjun Jiang; Hongxia Dong; Chunlei Zhang; et al. (Field Crops Research, 2024)

Anthropogenic gadolinium contaminations in the marine environment and its ecological implications - Zhaolin Zhang; Wei Jiang; Tingwu Gu; Ning Guo; Ruipeng Sun; Yang Zeng; Yansong Han; Kefu Yu (Environmental Pollution, 2024)

Metabolomics reveals the lipid metabolism disorder in Pelophylax nigromaculatus exposed to environmentally relevant levels of microcystin-LR - Yinan Zhang; Wenhui Sun; Bingyi Wang; Zhiqun Liu; Zhiquan Liu; Xiaofang Zhang; Binhao Wang; Yu Han; Hangjun Zhang (Environmental Pollution, 2024)

Exploiting a tumor softening targeted bomb for mechanical gene therapy of chemoresistant Triple-Negative breast cancer - Yuting Shen; Xin Guan; Shaoyue Li; Xiaodong Hou; Jifeng Yu; Haohao Yin; Xuexia Shan; Xiaoxia Han; Lifan Wang; Boyang Zhou; Xiao Li; Liping Sun; et al. (Chemical Engineering Journal, 2024)

Magneto-elastic for wireless intraocular pressure monitoring - Yu Lin; Shengxin Xiang; Wenjun Zou; Xiaohua Chen; Feixiang Gao; Yi Liu; Yijie Sun; Ping Chen; Quanxi Zhang; Xuelian Han; Baoping Wang; Yong Yao; et al. (Chemical Engineering Journal, 2024)

Cerium-based sorbent with 100% Ce(III) and high dispersion for enhanced phosphate removal from wastewater - Tao Zhang; Sujie Shan; Dongqing Liu; Yu Han; Kai Sun; Wei Wang (Chemical Engineering Journal, 2024)

A novel neuroprotective method against ischemic stroke by accelerating the drainage of brain interstitial fluid - Jingge Lian; Liu Yang; Hanbo Tan; Shaoyi Su; Leonor Serrano Lopes; Fangxiao Cheng; Junhao Yan; Yu Fu; Wanyi Fu; Zhaoheng Xie; Jianfei Sun; Jicong Zhang; et al. (Science China Life Sciences, 2024)

An improved CapsNet based on data augmentation for driver vigilance estimation with forehead single-channel EEG - Huizhou Yang; Jingwen Huang; Yifei Yu; Zhigang Sun; Shouyi Zhang; Yunfei Liu; Han Liu; Lijuan Xia (Cognitive Neurodynamics, 2024)

The dietary supplementation of Sargassum fusiforme can effectively alleviate high-fat diet induced metabolic abnormalities - Yu Bai; Yuanyuan Fu; Kang Chen; Yan Sun; Chengxu Zhou; Jichang Han; Xiaojun Yan (Algal Research, 2024)

Quantifying the negative effects of dissolved organic carbon of maize straw-derived biochar on its carbon sequestration potential in a paddy soil - Lanfang Han; Beibei Liu; Yu Luo; Liying Chen; Chuanxin Ma; Chao Xu; Ke Sun; Baoshan Xing (Soil Biology and Biochemistry, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Insight into the differential response of functional denitrifiers to novel formulated organic amendments in soybean agroecosystem - Ugochi Uzoamaka Egbeagu; Yue Zhang; Yuanhang Wang; Ayodeji Bello; Liting Deng; Yu Sun; Yue Han; Liyan Zhao; Shuai Shi; Huajing Liu; Xiuhong Xu (Rhizosphere, 2024)

A novel selective collector MIBATC and its performance on flotation separation of chalcopyrite from sphalerite and pyrite - Xuesong Sun; Jianwen Yu; Yanjun Li; Yuexin Han; Peng Gao (Minerals Engineering, 2024)

Temperature evolution, flame traveling transition structure inside a compartment of various fire source locations - Xiepeng Sun; Qiang Wang; Jiang Lv; Xiang Fang; Yu Han; Fei Tang; Longhua Hu (Fuel, 2024)

An agent-assisted heterogeneous learning swarm optimizer for large-scale optimization - Yu Sun; Han Cao (Swarm and Evolutionary Computation, 2024)

Association between residential greenness and incident delirium: A prospective cohort study in the UK Biobank - Qida He; Mengtong Sun; Yu Wang; Guoxian Li; Hanqing Zhao; Ze Ma; Zhaolong Feng; Tongxing Li; Qiang Han; Na Sun; Linyan Li; Yueping Shen (Science of The Total Environment, 2024)

Control of carbon dioxide exchange fluxes by rainfall and biological carbon pump in karst river–lake systems - Chaowei Lai; Zaihua Liu; Qingchun Yu; Hailong Sun; Fan Xia; Xuejun He; Zhen Ma; Yongqiang Han; Xing Liu; Pengyun Hao; Qian Bao; Mingyu Shao; et al. (Science of The Total Environment, 2024)

Lithofacies, architecture and evolution of carbonate tidal delta system: Implications for reservoir heterogeneity (mid-cretaceous Mishrif Formation, Southeast Iraq) - Xiaowei Sun; Zhanfeng Qiao; Rui Guo; Guangya Zhu; Jianyong Zhang; Guanming Shao; Yu Zhang; Haiying Han; Zhehang Xu (Marine and Petroleum Geology, 2024)

Insight into the regulation effect of steam dilution on oxygen-enriched ammonia combustion characteristics - Yu Zhang; Bo Han; Xincheng Li; Wenda Zhang; Linyao Zhang; Yijun Zhao; Shaozeng Sun (Fuel, 2024)

Engineered biochar with ultrahigh surface areas derived from postpyrolysis with urea for efficient removal of plasticizer - Gang Ji; Yuxin Hou; Yu Zhang; Zhangxiong Han; Qian Sun; Rongting Ji; Ziyan Li; Jiangang Han; Hu Cheng; Yang Song; Jianming Xue (Fuel, 2024)

Rational construction of defective Z-Scheme tandem heterojunction interfacial charge transfer channels for efficient uranium collection and resistance to biological contamination - Yachao Xu; Xue Han; Zhong Zhou; Peng Yu; Bojing Sun; Ying Wang (Chemical Engineering Journal, 2024)

Risk of Cardiovascular Disease Hospitalization After Common Psychiatric Disorders: Analyses of Disease Susceptibility and Progression Trajectory in the UK Biobank - Xin Han; Yu Zeng; Yanan Shang; Yao Hu; Can Hou; Huazhen Yang; Wenwen Chen; Zhiye Ying; Yajing Sun; Yuanyuan Qu; Junren Wang; Wei Zhang; et al. (Phenomics, 2024)
Whether associations between psychiatric disorders and hospitalization for cardiovascular diseases (CVDs) can be modified by disease susceptibility and the temporal pattern of these associated CVDs remain unknown. In our study, we conducted a matched cohort study of the UK Biobank including 44,430 patients with common psychiatric disorders (anxiety, depression, and stress-related disorders) between 1997 and 2019, together with 222,150 sex-, Townsend deprivation index-, and birth year- individually matched unexposed individuals. The hazard ratios (HRs) for CVD hospitalization associated with a prior psychiatric disorder were derived from Cox models, adjusted for multiple confounders. We then stratified the analyses by self-reported family history of CVD and CVD polygenic risk score (PRS) calculated based on summary statistics of independent genome-wide association studies. We further conducted disease trajectory analysis and visualized the temporal pattern of CVDs after common psychiatric disorders. During a mean follow-up of 12.28 years, we observed an elevated risk of CVD hospitalization among patients with psychiatric disorders, compared with matched unexposed individuals (hazard ratios [HRs] = 1.20, 95% confidence interval [CI]: 1.18–1.23), especially during the first six months of follow-up (1.72 [1.55–1.91]). The stratification analyses by family history of CVD and by CVD PRS obtained similar estimates between subgroups with different susceptibilities to CVD. We conducted trajectory analysis to visualize the temporal pattern of CVDs after common psychiatric disorders, identifying primary hypertension, acute myocardial infarction, and stroke as three main intermediate steps leading to further increased risk of other CVDs. In conclusion, the association between common psychiatric disorders and subsequent CVD hospitalization is not modified by predisposition to CVD. Hypertension, acute myocardial infarction, and stroke are three initial CVDs linking psychiatric disorders to other CVD sequelae, highlighting a need of timely intervention on these targets to prevent further CVD sequelae among all individuals with common psychiatric disorders.

Evolution of Elastic–Plastic Characteristics of Rocks Within Middle-Deep Geothermal Reservoirs Under High Temperature - Qiuyan Wang; Daobing Wang; Bo Yu; Dongliang Sun; Yongliang Wang; Nai Hao; Dongxu Han (Natural Resources Research, 2024)

Mitigation Effect of Exogenous Dopamine Treatment on Downy Mildew-Infected Cucumber - Ze-Yu Ji; Ze-Yu Liu; Li-Ming Shi; Xin-Yu Lu; Yu-Ying Han; Yan Sun (Journal of Plant Growth Regulation, 2024)

Genome-wide identification, transcriptional analysis, and acetylated histone site recognition of the Bromodomain gene family in Pyropia yezoensis - Xiaoqian Zhang; Qiran Sun; Hongying Yu; Zehao Zhang; Ying Pang; Lei Han; Fugeng Tang; Dongmei Wang (Algal Research, 2024)

Why pile-supported building settled continuously after water level was stabilized during dewatering: Clues from interaction between pile and multi aquifers - Xiu-Li Xue; Hai-Yu Sun; Chao-Feng Zeng; Hong-Bo Chen; Gang Zheng; Chang-Jie Xu; Lei Han (Journal of Hydrology, 2024)

Contributions of microlayer to flow boiling heat transfer in the mini-channel - Yujie Chen; Bohong Wang; Bo Gao; Wei Li; Dongliang Sun; Wei Zhang; Dongxu Han; Wenquan Tao; Bo Yu (Journal of Cleaner Production, 2024)

Improving the color storage stability of phycocyanin under light and acidified conditions through antisolvent precipitation of phycocyanin-zein complex - Zengyu Yu; Shufang Yang; Weiyang Zhao; Han Sun; Qing Kong (Algal Research, 2024)

Experimental Study on Cyclic Simple Shear Test of Coastal Tidal Soft Soil - Xiuxia Yu; Honglei Sun; Junwei Liu; Hongxuan Zhao; Yu Han (Journal of Marine Science and Engineering, 2024)
Based on undrained cyclic simple shear tests conducted on coastal tidal soft soil under various conditions of cyclic stress ratios and moisture contents, this study investigated the influence of these factors on the dynamic properties of the soil. The findings indicated that with increasing moisture content and stress cycle ratio, the stress–strain hysteresis loop gradually expanded, resulting in a higher strain difference and a transition from a dense to a sparse curve pattern. Moreover, the symmetry of the hysteresis loop was lost in the later stages of shearing. With an increase in the number of cycles, the cumulative shear strain gradually increased, and the increase in the cyclic ratio of water content to stress reduced the number of cyclic shear cycles required to achieve failure, thereby accelerating the soil’s failure rate. A predictive formula was developed based on the experimental results to estimate the failure cycles as a function of the cyclic stress ratio and moisture content. Furthermore, the softening index decreased gradually with an increasing number of cycles, and a higher moisture content and cyclic stress ratio accelerated the soil’s softening process. It was observed that under the conditions of optimal moisture content, the soil exhibited a slower softening rate during the initial stage of shearing.

Insight into N2O emission and denitrifier communities under different aeration intensities in composting of cattle manure from perspective of multi-factor interaction analysis - Yue Han; Ruixin Bi; Yuanhang Wang; Lei Sun; Xinda Liu; Shuai Shi; Nuo Chang; Liyan Zhao; Jiaxin Bao; Yonghui Xu; Wanying Liu; Jining Zhang; et al. (Science of The Total Environment, 2024)

Major source categories of PM2.5 oxidative potential in wintertime Beijing and surroundings based on online dithiothreitol-based field measurements - Rico K.Y. Cheung; Lu Qi; Manousos I. Manousakas; Joseph V. Puthussery; Yan Zheng; Theodore K. Koenig; Tianqu Cui; Tiantian Wang; Yanli Ge; Gaoyuan Wei; Yu Kuang; Mengshuang Sheng; et al. (Science of The Total Environment, 2024)

Targeting the undruggables—the power of protein degraders - Chao Zhang; Yongbo Liu; Guangchen Li; Zhouli Yang; Chi Han; Xiuyun Sun; Chunquan Sheng; Ke Ding; Yu Rao (Science Bulletin, 2024)

A comparative study on urban waterlogging susceptibility assessment based on multiple data-driven models - Feifei Han; Jingshan Yu; Guihuan Zhou; Shuang Li; Tong Sun (Journal of Environmental Management, 2024)

Improvement of biotic nitrate reduction in constructed photoautotrophic biofilm-soil microbial fuel cells - Yu Cheng; Jue Ding; Jiahui Wan; Li Tang; Akaninyene Joseph; Muhammad Usman; Ningyuan Zhu; Yanxia Zhang; Han Sun; Eldon R. Rene; Marton Lendvay; Yiping Li (Journal of Environmental Management, 2024)

Electrocatalytic carbon dioxide conversion to formate using gas-diffusion electrodes with group 12–15 metals - Guangxia Piao; Gukgyeong Yu; Seonghun Kim; Jin Sun Cha; Dong Suk Han; Hyunwoong Park (Journal of Environmental Chemical Engineering, 2024)

Phycocyanin from microalgae: A comprehensive review covering microalgal culture, phycocyanin sources and stability - Zengyu Yu; Weiyang Zhao; Han Sun; Haijin Mou; Jin Liu; Hui Yu; Lei Dai; Qing Kong; Shufang Yang (Food Research International, 2024)

Greenness and its composition and configuration in association with allergic rhinitis in preschool children - Han Chen; Xia Meng; Yongfu Yu; Jin Sun; Zhiping Niu; Jing Wei; Ling Zhang; Chan Lu; Wei Yu; Tingting Wang; Xiaohong Zheng; Dan Norbäck; et al. (Environmental Research, 2024)

Reconstruction of Fe sacrifice protective layer enables highly effective CoP catalyst for hydrogen evolution reaction at high current density - Yingying Xu; Yingxia Zhao; Ming Sun; Wei Xie; Ying Wu; Gao Cheng; Yuanhong Zhong; Shenbo Han; Lin Yu (Chemical Engineering Journal, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

Overexpression of TRIM44 mediates the NF-κB pathway to promote the progression of ovarian cancer - Yang Yu; ShiYing Li; Jialin Sun; Yu Wang; LiangZhen Xie; Ying Guo; Jia Li; FengJuan Han (Genes & Genomics, 2024)

Identification of lignans as ATP citrate lyase (ACLY) inhibitors from the roots of Pouzolzia zeylanica - Jin-Long Li; Jia-Yi Jiang; Shan-Shan Gu; Lei Zhang; Yan Sun; Xue-Han Wang; Dan-Yu Li; Zhe-Yu Chen; Sheng-Shi Jiang; Wei-Zhong Zhu; Hao-Wen Jiang; Hong-Jie Zhang (Natural Product Research, 2024)

Neural network establishes co-occurrence links between transformation products of the contaminant and the soil microbiome - Yuhui Xiang; Yansong Yu; Jiahui Wang; Weiwei Li; Yu Rong; Haibo Ling; Zhongbing Chen; Yiguang Qian; Xiaole Han; Jie Sun; Yuyi Yang; Liang Chen; et al. (Science of The Total Environment, 2024)

Cellular Cd2+ fluxes in roots confirm increased Cd availability to rice (Oryza sativa L.) induced by soil acidifications - Xiaoyi Sun; Meng Wang; Luyao Qin; Lei Yu; Jing Wang; Han Zheng; Wenneng Zhou; Shibao Chen (Journal of Environmental Sciences, 2024)

Efficient detection of flusilazole by an electrochemical sensor derived from MOF MIL-53(Fe) for food safety - Yu-Han Sun; Liu Yang; Xian-Xian Ji; Yuan-Zhen Wang; Yu-Long Liu; Ying Fu; Fei Ye (Food Chemistry, 2024)

Construction of integrated oxygen-rich carbon-based metal-free cathode to simultaneous boost wastewater treatment performance and energy recovery in bio-electro-Fenton system - Ruyan Chen; Mengsha Han; Yaning Shi; Wei Guo; Yuhan Wu; Tianduo Zhang; Xiao Han; Cuiwei Du; Chongfei Yu; Jinglan Feng; Shuying Dong; Jianhui Sun; et al. (Chemical Engineering Journal, 2024)

Improving prediction of N2O emissions during composting using model-agnostic meta-learning - Shuai Shi; Jiaxin Bao; Zhiheng Guo; Yue Han; Yonghui Xu; Ugochi Uzoamaka Egbeagu; Liyan Zhao; Nana Jiang; Lei Sun; Xinda Liu; Wanying Liu; Nuo Chang; et al. (Science of The Total Environment, 2024)

Quasi-2D spin-Peierls transition through interstitial anionic electrons in K(NH3)2 - Chi Ding; Qing Lu; Zhaopeng Guo; Tianheng Huang; Junjie Wang; Yu Han; Dingyu Xing; Jian Sun (Science Bulletin, 2024)

Activation of peroxymonosulfate by a CuCo-NC diatomic catalyst on N-doped graphene for selective generation of 1O2 towards efficient organic pollutant treatment - Yuxuan Sun; Jie Yu; Xuan Guo; Yuhang Cui; Zijian Zhang; Xiaoyuan Zhang; Shiming Hu; Chenghao Yang; Bo Chi; Kosuke Noborio; Song Han (Journal of Environmental Chemical Engineering, 2024)

A theoretical investigation on the transformer oil pyrolysis mechanism and the effect of the small molecule acid in oils - Huijuan Wang; Wei Xia; Huimin Yu; Hua Chen; Yongli Pan; Yingxin Sun; Shengtao Li; Sheng Han (Fuel, 2024)

Mechanisms of imbalanced testicular homeostasis in infancy due to aberrant histone acetylation in undifferentiated spermatogonia under different concentrations of Di(2-ethylhexyl) phthalate (DEHP) exposure - Yu Tian; Jiachen Guo; Lei Hua; Yinuo Jiang; Wei Ge; Xiaoyuan Zhang; Diya Cai; Dongliang Lu; Bin Wang; Wei Shen; Zhongyi Sun; Baoquan Han (Environmental Pollution, 2024)

The impacts of planting patterns combined with irrigation management practices on soil water content, watermelon yield and quality - Xiaolin Qiang; Zhaojun Sun; Xingqiang Li; Siqi Li; Zhao Yu; Jun He; Qian Li; Lei Han (Agroforestry Systems, 2024)

Adsorption characteristics of Ag+ on sphalerite surface: a combined experimental and first-principle study - Heng Yu; Hongliang Zhang; Chenyang Zhang; Wei Sun; Mingjun Han; Rong Wang; Xin Wei; Songjiang Li (Environmental Science and Pollution Research, 2024)

Differences in ingestion and biodegradation of the melamine formaldehyde plastic by yellow mealworms Tenebrio molitor and superworms Zophobas atratus, and the prediction of functional gut microbes - Xin Li; Yijing Wang; Huayang Sun; Yumeng Wang; Xiaoyu Han; Jingli Yu; Xin Zhao; Baoqin Liu (Chemosphere, 2024)

Interaction between Sea perch iridovirus (SPIV) infection and gut microbes in sea perch Lateolabrax japonicus - Zheng Zhu; Yu-Min Xu; Wen-Feng Yang; Wu-Lang Luo; Wei Huang; Jun-Han Liang; Jin-Ding Chen; Hong-Yan Sun; Qi-Wei Qin (Aquaculture, 2024)

Urban sector land use metabolism reveals inequalities across cities and inverse virtual land flows - Wei Xie; Xuechun Yang; Zhixiu Han; Mingxing Sun; Yang Li; Hongyi Xie; Huajun Yu; Bin Chen; Brian Fath; Yutao Wang (Resources, Conservation and Recycling, 2024)

Factors affecting chemical and textural properties of dried tuber, fruit and vegetable - Yue Li; Han Zhao; Kexin Xiang; Dajing Li; Chunju Liu; Haiou Wang; Wenqian Pang; Liying Niu; Rui Yu; Xiyun Sun (Journal of Food Engineering, 2024)

Analysis of key enzyme activity and aroma volatile compounds in microwave-irradiated quinoa during storage - Hongwei Cao; Jinzhe Han; Rulian Sun; Zhaoxia Li; Yu Zhang; Hongdong Song; Kai Huang; Ying Zhang; Xiao Guan (Journal of Cereal Science, 2024)

Peroxymonosulfate activation by walnut shell activated carbon supported nano zero-valent iron for the degradation of tetracycline: Performance, degradation pathway and mechanism - Pingping Duan; Fanlong Kong; Xiuzheng Fu; Zhijie Han; Guangwei Sun; Zhengda Yu; Sen Wang; Yuqian Cui (Environmental Research, 2024)

Mechanism of propylene effect on the NH3-SCR performance of Cu-SSZ-13 catalyst - Wenqing Ding; Yu Sun; Jingjing Liu; Sen Xue; Xuewang Han; Zidi Yan; Yunbo Yu; Yulong Shan; Hong He (Chemical Engineering Journal, 2024)

Promotion of anaerobic biodegradation of azo dye RR2 by different biowaste-derived biochars: Characteristics and mechanism study by machine learning - Yu-Qian Wang; Jie Ding; Ji-Wei Pang; Chuan-Dong Wu; Han-Jun Sun; Rui Fang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2024)

Improve meat production and virus resistance by simultaneously editing multiple genes in livestock using Cas12iMax - Jilong Ren; Tang Hai; Yangcan Chen; Ke Sun; Zhiqiang Han; Jing Wang; Chongyang Li; Qingwei Wang; Leyun Wang; Huabing Zhu; Dawei Yu; Wei Li; et al. (Science China Life Sciences, 2024)

Triphenyl phosphate exposure impairs colorectal health by altering host immunity and colorectal microbiota - Changchun Ye; Zilu Chen; Wenhao Lin; Zepeng Dong; Jie Han; Jingyi Zhang; Xueqian Ma; Junhui Yu; Xuejun Sun; Ying Li; Jianbao Zheng (Chemosphere, 2024)

Multi-scale failure mechanisms of hydraulic engineering exposed to seasonally frozen salinization environment: Integrating SBAS-InSAR and mechanical experiments - Zhaoxi Wang; Chen Cao; Qingbo Yu; Qing Wang; Cencen Niu; Jiejie Shen; Kuanxing Zhu; Jing Liu; Mengxia Han; Huicheng Fu; Xun Sun; Weitong Xia; et al. (Science of The Total Environment, 2024)

Comamonas-dominant microbial community in carbon poor aquitard sediments revealed by metagenomic-based growth rate investigation - Miao Zhang; Bixi Zhao; Yuxi Yan; Zhanwen Cheng; Zengyi Li; Long Han; Yuqin Sun; Yan Zheng; Yu Xia (Science of The Total Environment, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Experimental and computational study on the adsorption mechanism of silver ions on galena surface - Heng Yu; Hongliang Zhang; Chenyang Zhang; Wei Sun; Mingjun Han; Rong Wang; Xin Wei; Songjiang Li (Journal of Water Process Engineering, 2024)

Numerical simulation of velocity distribution and pollution transport in a two-stage channel with vegetation on a floodplain - Yu Bai; Lijuan Han; Yufeng Zhao; Lu Huang; Qian Wang; Guojin Sun (Journal of Hydrology, 2024)

Stabilizing F-Al-O active center via confinement of Al2O3 in SiC framework for conversion of 1,1-difluoroethane greenhouse gas - Xiaoli Wei; Yiwei Sun; Jianhai Jiang; Zhen Wang; Wei Zhang; Bing Liu; Shucheng Wang; Xiaodan Yang; Wanjin Yu; Jianjun Zhang; Wenfeng Han (Journal of Fluorine Chemistry, 2024)

Integrated analysis of transcriptome and metabolome reveals the regulatory mechanism of largemouth bass (Micropterus salmoides) in response to Nocardia seriolae infection - Fen Dong; Yu-Long Sun; Yuan-Xin Qian; Qiang Chen; Jia-Le He; Ji-Teng Wang; Tao Han; Xiu-Mei Zhang; Yu-Ting Deng (Fish & Shellfish Immunology, 2024)

Visible-light-driven photo-Fenton oxidation enhanced by Fe/Bi-nanocrystal phase transformation as a universal way for various organic pollutants mineralization - Tulai Sun; Zi-Yan Jin; Bin Deng; Gan He; Qiong-Yu Wang; Mian Hu; Zhangliang Han; Zhaoke Zheng; Jun Zhao; Jimmy Yun; Jia Zhao; Yihan Zhu; et al. (Chemical Engineering Journal, 2024)

Insidious transmission of Mycobacterium tuberculosis in Ordos, China: a molecular epidemiology study - Hailin Sun; Zichun Ma; Fuli Ai; Bing Han; Peng Li; Juan Liu; Yiheng Wu; Yufeng Wang; Bing Li; Dan Qi; Yu Pang (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Ecosystem carbon exchange across China's coastal wetlands: Spatial patterns, mechanisms, and magnitudes - Jilong Wang; Guirui Yu; Lang Han; Yuan Yao; Mingyu Sun; Zhifeng Yan (Agricultural and Forest Meteorology, 2024)

High spatial variability in water use efficiency of terrestrial ecosystems throughout China is predominated by biological factors - Xiaojun Dou; Guirui Yu; Zhi Chen; Meng Yang; Tianxiang Hao; Lang Han; Zhaogang Liu; Lexin Ma; Yong Lin; Xianjin Zhu; Weikang Zhang; Mingyu Sun; et al. (Agricultural and Forest Meteorology, 2024)

Laccase-evoked removal of antibiotics: Reaction kinetics, conversion mechanisms, and ecotoxicity assessment - Kai Sun; Mei-Hua Chen; Xue-Min Qi; Dan Hong; Ling-Zhi Dai; Shun-Yao Li; Yi-Chen Lu; Han-Qing Yu (Critical Reviews in Environmental Science and Technology, 2024)

Isolation and Cultivation of Carotenoid-Producing Strains from Tidal Flat Sediment and Proposal of Croceibacterium aestuarii sp. nov., a Novel Carotenoid-Producing Species in the Family Erythrobacteraceae - Xiao-Yan Sun; Han Dong; Yu Zhang; Jia-Wei Gao; Peng Zhou; Cong Sun; Lin Xu (Journal of Marine Science and Engineering, 2024)
Carotenoids are extensively used in drugs, cosmetics, nutrients, and foods, owing to their antioxidant and anti-inflammatory characteristics. Diverse marine heterotrophic prokaryotes can accumulate carotenoids and become promising alternatives for the advancement of carotenoids production. In this research, 55 strains were isolated and cultivated from tidal flat sediment in Zhoushan and classified into the phyla Pseudomonadota (n = 24), Bacillota (n = 18), Bacteroidota (n = 9), and Actinomycetota (n = 4). Nine of them accumulated carotenoids, and most of them belonged to the families Flavobacteriaceae (n = 4) and Erythrobacteraceae (n = 4). Among those carotenoid-producing strains, one strain, designated as D39T, was proposed as one novel species belonging to the genus Croceibacterium through polyphasic taxonomy approaches. Genomic annotations and carotenoid compound determinations revealed that strain D39T encoded crtEBIYZG genes and mainly accumulated zeaxanthin as major carotenoids. Furthermore, carotenoid biosynthesis pathway in the majority of Croceibacterium strains were identical with that in the strain D39T, implying that Croceibacterium members can be sources of producing zeaxanthin. This study enhances knowledge of microbial biodiversity in tidal flats, proposes a novel carotenoid-producing Croceibacterium species, and elucidates carotenoid biosynthesis pathway in the genus Croceibacterium, which contribute to enriching marine carotenoid-producing strains and promoting a comprehensive insight into genomic contents of them.

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Relative role of soil nutrients vs. carbon availability on soil carbon mineralization in grassland receiving long-term N addition - Liangchao Jiang; Huanhuan Cheng; Yang Peng; Tianran Sun; Yingzhi Gao; Ruzhen Wang; Yanxia Ma; Junjie Yang; Qiang Yu; Haiyang Zhang; Xingguo Han; Qiushi Ning (Soil and Tillage Research, 2024)

Bibliometric analysis of papers on antibiotic resistance genes in aquatic environments on a global scale from 2012 to 2022: Evidence from universality, development and harmfulness - Xiaofang Sun; Xiaochen Wang; Qian Han; Qiaoling Yu; Ruijun Wanyan; Huan Li (Science of The Total Environment, 2024)

Variability in methylmercury exposure across migratory terrestrial bird species: Influencing factors, biomagnification and potential risks - Lingling Xing; Tong Zhang; Xuetao Han; Maowen Xie; Le Chao; Jingrui Chen; Xiaoming Yu; Jiahong Zhou; Guoxiang Yu; Jiachen Sun (Science of The Total Environment, 2024)

Cumulated influence of natural and anthropogenic drivers on surface seawater barium: Evidence from a high-resolution coral record in the northern South China Sea - Chunmei Feng; Wei Jiang; Kefu Yu; Yinan Sun; Sirong Xie; Yansong Han; Chaoshuai Wei (Science of The Total Environment, 2024)

Sodium nitroprusside (SNP) treatment increases the postharvest resistance of apple fruit to Alternaria alternata by enhancing antioxidant enzyme activity - Jie Han; Yingying Fan; Tao Sun; Jing An; Yu Ding; Weiwei Zhang; Fengjuan Liu; Cheng Wang (Physiological and Molecular Plant Pathology, 2024)

Spatiotemporal dynamics and driving factors of vegetation coverage around linear cultural heritage: A case study of the Beijing-Hangzhou Grand Canal - Aihui Jiang; Fengzhi Sun; Baolei Zhang; Quanyuan Wu; Shangshu Cai; Zhiwei Yang; Yong Chang; Rongqing Han; Sisi Yu (Journal of Environmental Management, 2024)

Characterization of odor properties of human milk: Effect of inter-individual nutrient differences on key odor-active compounds and odor attributes - Mingguang Yu; Qinggang Xie; Han Sun; Ying Wang; Yuan Tang; Baosong Wang; Huanlu Song; Lijin Wang; Shilong Jiang; Kaifeng Li; Yongjiu Zhang; Chengdong Zheng (Food Chemistry, 2024)

Tunicate cellulose nanocrystals reinforced modified calcium sulfate bone cement with enhanced mechanical properties for bone repair - Xiaoyu Lv; Hui Yu; Jianing Han; Yage Hou; Yi Sun; Kaihua Liu; Wutong Zhou; Jingdi Chen (Carbohydrate Polymers, 2024)

Preliminary Investigation on Efficacy and Safety of Substance P-Coated Stent for Promoting Re-Endothelialization: A Porcine Coronary Artery Restenosis Model - Dae Sung Park; Seok Oh; Yu Jeong Jin; Mi Hyang Na; Munki Kim; Jeong Ha Kim; Dae Young Hyun; Kyung Hoon Cho; Young Joon Hong; Ju Han Kim; Youngkeun Ahn; Manuel Hermida-Prieto; et al. (Tissue Engineering and Regenerative Medicine, 2024)

Cascade effects of climate and vegetation influencing the spatial variation of evapotranspiration in China - Lexin Ma; Guirui Yu; Zhi Chen; Meng Yang; Tianxiang Hao; Xianjin Zhu; Weikang Zhang; Quanhong Lin; Zhaogang Liu; Lang Han; Xiaojun Dou; Mingyu Sun; et al. (Agricultural and Forest Meteorology, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Precipitation consistently promotes, but temperature oppositely drives carbon fluxes in temperate and alpine grasslands in China - Zhaogang Liu; Zhi Chen; Meng Yang; Tianxiang Hao; Guirui Yu; Xianjin Zhu; Weikang Zhang; Lexin Ma; Xiaojun Dou; Yong Lin; Wenxing Luo; Lang Han; et al. (Agricultural and Forest Meteorology, 2024)

High-precision target ranging in complex orchard scenes by utilizing semantic segmentation results and binocular vision - Yu Wen; Jinlin Xue; Han Sun; Yue Song; Pengfei Lv; Shaohua Liu; Yangyang Chu; Tianyu Zhang (Computers and Electronics in Agriculture, 2023)

m6A modification associated with YTHDF1 is involved in Japanese encephalitis virus infection - Xiao-han Li; Jing Chen; Yu-da Ou; Xiang Zhong; Jia-huan Hu; Rui-cong Sun; Ying-jun Lv; Jian-chao Wei; Yun Young Go; Bin Zhou (Veterinary Microbiology, 2023)

Two-dimensional, high-resolution imaging of pH dynamics in the phyllosphere of submerged macrophyte using a new Nano-optode - Jianyu Lin; Yu Sun; Hao Zhang; Qiushi Shen; Li Xu; Qingfei Zeng; Yaling Su; Chao Han (Science of The Total Environment, 2023)

Characterization of the odor compounds in human milk by DHS/GC × GC-O-MS: A feasible and efficient method - Mingguang Yu; Qinggang Xie; Huanlu Song; Lijin Wang; Han Sun; Shilong Jiang; Yongjiu Zhang; Chengdong Zheng (Food Research International, 2023)

Studies on blocking the JAK2/STAT3 signaling pathway with elastin peptides from skipjack tuna (Katsuwonus pelamis) bulbus cordis to alleviate osteoarthritis - Qiaoli Wu; Bing Liu; Rongxian Yu; Xiaoling Sun; Ziyan Wang; Jun Zhou; Chenyang Lu; Jing Zhang; Jiaojiao Han; Xiurong Su (Food Bioscience, 2023)

Integration of Sentinel–1 and Landsat–8 data for identifying deformation risk of hydraulic engineering in seasonally frozen salinization regions - Zhaoxi Wang; Chen Cao; Qingbo Yu; Xin Xu; Qing Wang; Cencen Niu; Jiejie Shen; Mengxia Han; Huicheng Fu; Kuanxing Zhu; Jing Liu; Weitong Xia; et al. (CATENA, 2023)

Improving yield-related traits by editing the promoter of the heading date gene Ehd1 in rice - Shengting Li; Yanqiu Luo; Guangliang Wei; Wubei Zong; Wanyong Zeng; Dongdong Xiao; Han Zhang; Yingang Song; Yu Hao; Kangli Sun; Chen Lei; Xiaotong Guo; et al. (Theoretical and Applied Genetics, 2023)

Classification of Glomerular Pathology Images in Children Using Convolutional Neural Networks with Improved SE-ResNet Module - Xiang-Yong Kong; Xin-Shen Zhao; Xiao-Han Sun; Ping Wang; Ying Wu; Rui-Yang Peng; Qi-Yuan Zhang; Yu-Ze Wang; Rong Li; Yi-Heng Yang; Ying-Rui Lv (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Parerythrobacter aestuarii sp. nov., Isolated from Seawater in the Tidal Region of Taizhou - Han Dong; Ren-Zhuang Han; Yu Zhang; Maripat Xamxidin; Peng Zhou; Cong Sun; Wu Qu; Lin Xu (Current Microbiology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Enforcing energy consumption promotes microbial extracellular respiration for xenobiotic bioconversion - Zi‐Han Liang; Hong Sun; Yang Li; Anyi Hu; Qiang Tang; Han‐Qing Yu (Environmental Microbiology, 2023)
Extracellular electron transfer (EET) empowers electrogens to catalyse the bioconversion of a wide range of xenobiotics in the environment. Synthetic bioengineering has proven effective in promoting EET output. However, conventional strategies mainly focus on modifications of EET‐related genes or pathways, which leads to a bottleneck due to the intricate nature of electrogenic metabolic properties and intricate pathway regulation that remain unelucidated. Herein, we propose a novel EET pathway‐independent approach, from an energy manipulation perspective, to enhance microbial EET output. The Controlled Hydrolyzation of ATP to Enhance Extracellular Respiration (CHEER) strategy promotes energy utilization and persistently reduces the intracellular ATP level in Shewanella oneidensis , a representative electrogenic microbe. This approach leads to the accelerated consumption of carbon substrate, increased biomass accumulation and an expanded intracellular NADH pool. Both microbial electrolysis cell and microbial fuel cell tests exhibit that the CHEER strain substantially enhances EET capability. Analysis of transcriptome profiles reveals that the CHEER strain considerably bolsters biomass synthesis and metabolic activity. When applied to the bioconversion of model xenobiotics including methyl orange, Cr(VI) and U(VI), the CHEER strain consistently exhibits enhanced removal efficiencies. This work provides a new perspective and a feasible strategy to enhance microbial EET for efficient xenobiotic conversion.

Unraveling heterogeneity of dissolved organic matter in highly connected natural water bodies at molecular level - Guan-Lin Chen; Chen Qian; Bo Gong; Meng Du; Rui-Zhe Sun; Jie-Jie Chen; Han-Qing Yu (Water Research, 2023)

α-LA attenuates microcystin-LR-induced hepatocellular oxidative stress in mice through Nrf2-mediated antioxidant and detoxifying enzymes - Jun Bai; Chaoyun Chen; Yaochuan Sun; Shangchun Li; Renjiang He; Qingbi Zhang; Qian Sun; Yu Huang; Ailin Tan; Li Yuan; Yinxing Huang; Yuanyuan Lan; et al. (Toxicon, 2023)

Unlocking the potential of resuscitation-promoting factor for enhancing anaerobic microbial dechlorination of polychlorinated biphenyls - Zhen Han; Aiqin Hou; Xiaolin Cai; Mengqi Xie; Faqian Sun; Chaofeng Shen; Hongjun Lin; Haiying Yu; Xiaomei Su (Science of The Total Environment, 2023)

High recovery of lithium from coal residue by roasting and sulfuric acid leaching - Yu Xie; Chenquan Ni; Zhengwei Han; Hui Zhong; Zhiguo He; Wei Sun (Minerals Engineering, 2023)

Dynamics of chromophoric dissolved organic matter in a highly productive Amundsen Sea polynya - Ji Hu; Siyou Xue; Jun Zhao; Zhengbing Han; Dong Li; Haifeng Zhang; Peisong Yu; Minhui Zheng; Jianming Pan; Yongge Sun (Marine Chemistry, 2023)

Decision support framework adapted to local conditions to select technologies for rural domestic sewage treatment in the Yangtze River Economic Belt - Mei-Yun Lu; Shan-Shan Yang; Xin-Lei Yu; Han-Jun Sun; Ji-Wei Pang; Nan-Qi Ren; Jie Ding (Journal of Cleaner Production, 2023)

The nonlinear effect of new urbanization on water pollutant emissions: Empirical analysis based on the panel threshold model - Qianwen Yu; Zehao Sun; Junyuan Shen; Xia Xu; Qingye Han; Min Zhu (Journal of Environmental Management, 2023)

Strategy of functional nucleic acids-mediated isothermal amplification for detection of foodborne microbial contaminants: A review - Jie Zhou; Teng-Yu Wang; Zhi Lan; Han-Jie Yang; Xing-Jian Ye; Rui Min; Zhao-Hui Wang; Qing Huang; Jing Cao; Yu-E Gao; Wen-Long Wang; Xiu-Lan Sun; et al. (Food Research International, 2023)

Spatio-temporal variation of bacterial community structure in two intertidal sediment types of Jiaozhou Bay - Xuechao Chen; Xinran Zhang; Hao Yu; Meiaoxue Han; Jianhua Sun; Gang Liu; Yan Ji; Chuan Zhai; Liyan Zhu; Hongbing Shao; Yantao Liang; Andrew McMinn; et al. (Environmental Research, 2023)

Physicochemical and biological changes on naturally aged microplastic surfaces in real environments over 10 months - Xue Yu; Bing Wang; Chenglong Han; Ling Liu; Xiaoxin Han; Boyang Zheng; Bo Zhang; Jiawei Sun; Zhiyin Zhang; Weiqi Ma; Lifang Zhai; Xueqiang Lu (Environmental Pollution, 2023)

Coral skeletons reveal the impacts of oil pollution on seawater chemistry in the northern South China Sea - Sirong Xie; Wei Jiang; Chunmei Feng; Yinan Sun; Yansong Han; Yuwen Xiao; Chaoshuai Wei; Kefu Yu (Chemosphere, 2023)

SlbHLH152, a bHLH transcription factor positively regulates iron homeostasis in tomato - Xiaoli Li; Haohao Cao; Deshui Yu; Kedong Xu; Yi Zhang; Xinxin Shangguan; Xiaohong Zheng; Zhongzhou Yang; Chaoqiong Li; Xingchen Pan; Yiming Cui; Zhiqing Zhang; et al. (Plant Science, 2023)

The potential mediation of hypoxia-inducible factor-1α in heat shock protein 27 translocations, caspase-3 and calpain activities and yak meat tenderness during postmortem aging - Xijin Zhu; Renqing Dingkao; Nan Sun; Ling Han; Qunli Yu (Meat Science, 2023)

Divergent environmental responses of long-term variations in evapotranspiration over four grassland ecosystems in China based on eddy-covariance measurements - Han Zheng; Guirui Yu; Qiufeng Wang; Zhi Chen; Xianjin Zhu; Han Bao; Yuchen Sun; Panpan Niu; Yingnian Li; Peili Shi; Yanbin Hao; Fawei Zhang; et al. (Journal of Hydrology, 2023)

A pilot study on recovery of iron from sulfur-bearing hematite ore using hydrogen-based mineral phase transformation followed by magnetic separation - Jianwen Yu; Hao Sun; Peiyu Li; Wenjie Han; Yanjun Li; Yuexin Han (Journal of Environmental Chemical Engineering, 2023)

Fe3S4 nanozyme inhibits tumor growth by synergistic effects of ferroptosis and apoptosis - Aimin Wu; Ming Han; Hao Ding; Hanbing Rao; Zhiwei Lu; Mengmeng Sun; Yanying Wang; Yinyin Chen; Yu Zhang; Xianxiang Wang; Daiwen Chen (Chemical Engineering Journal, 2023)

Air pollution exposure and plasma fatty acid profile in pregnant women: a cohort study - Chenhui Yang; Ye Shen; Yiqiong Zhang; Han Xiao; Xiaojie Sun; Jiaqiang Liao; Xinmei Chen; Wenxin Zhang; Ling Yu; Wei Xia; Shunqing Xu; Yuanyuan Li (Environmental Science and Pollution Research, 2023)

Carbon source shaped microbial ecology, metabolism and performance in denitrification systems - Yuan Pan; Rui-Zhe Sun; Yan Wang; Guan-Lin Chen; Ying-Ying Fu; Han-Qing Yu (Water Research, 2023)

Diatom evidence for late Holocene environmental change in a permafrost peatland in the northern Greater Khingan Mountains, Northeast China - Dongxue Han; Yang Sun; Zicheng Yu; Ming Jiang; Jinxin Cong; Chuanyu Gao; Guoping Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Alleviating eutrophication by reducing the abundance of Cyanophyta due to dissolved inorganic carbon fertilization: Insights from Erhai Lake, China - Chaowei Lai; Zhen Ma; Zaihua Liu; Hailong Sun; Qingchun Yu; Fan Xia; Xuejun He; Qian Bao; Yongqiang Han; Xing Liu; Haibo He (Journal of Environmental Sciences, 2023)

In-situ electrochemical synthesis of heteroatoms-doped reduced graphene oxide toward nonradical degradation of tetracycline - Xiaohong Sun; Nan Yang; Heng Dong; Han Yu; Hongbing Yu; Linya Feng (Chemical Engineering Journal, 2023)

Meningeal lymphatics restoration and neurovascular protection synergistically improve traumatic brain injury treatment - Jingquan Lin; Hangxiang Sun; Hongjie Jiang; Rui Xue; Bing Qin; Jianan Lu; Zhoule Zhu; Chengwei Cai; Jiawei Han; Jianmin Zhang; Xiaohua Yu; Junming Zhu (Chemical Engineering Journal, 2023)

Formation of soil organic carbon pool is regulated by the structure of dissolved organic matter and microbial carbon pump efficacy: A decadal study comparing different carbon management strategies - Yalan Chen; Zhangliu Du; Zhe (Han) Weng; Ke Sun; Yuqin Zhang; Qin Liu; Yan Yang; Yang Li; Zhibo Wang; Yu Luo; Bo Gao; Bin Chen; et al. (Global Change Biology, 2023)
To achieve long‐term increases in soil organic carbon (SOC) storage, it is essential to understand the effects of carbon management strategies on SOC formation pathways, particularly through changes in microbial necromass carbon (MNC) and dissolved organic carbon (DOC). Using a 14‐year field study, we demonstrate that both biochar and maize straw lifted the SOC ceiling, but through different pathways. Biochar, while raising SOC and DOC content, decreased substrate degradability by increasing carbon aromaticity. This resulted in suppressed microbial abundance and enzyme activity, which lowered soil respiration, weakened in vivo turnover and ex vivo modification for MNC production (i.e., low microbial carbon pump “efficacy”), and led to lower efficiency in decomposing MNC, ultimately resulting in the net accumulation of SOC and MNC. In contrast, straw incorporation increased the content and decreased the aromaticity of SOC and DOC. The enhanced SOC degradability and soil nutrient content, such as total nitrogen and total phosphorous, stimulated the microbial population and activity, thereby boosting soil respiration and enhancing microbial carbon pump “efficacy” for MNC production. The total C added to biochar and straw plots were estimated as 27.3–54.5 and 41.4 Mg C ha −1 , respectively. Our results demonstrated that biochar was more efficient in lifting the SOC stock via exogenous stable carbon input and MNC stabilization, although the latter showed low “efficacy”. Meanwhile, straw incorporation significantly promoted net MNC accumulation but also stimulated SOC mineralization, resulting in a smaller increase in SOC content (by 50%) compared to biochar (by 53%–102%). The results address the decadal‐scale effects of biochar and straw application on the formation of the stable organic carbon pool in soil, and understanding the causal mechanisms can allow field practices to maximize SOC content.

High-efficient capture and degradation of formaldehyde based on the electric-field-enhanced catalytic effect - Yuan Gang Lu; Wen Kang Zhao; De Cai Fang; Jia Yu Zheng; Bei Chen Sun; Tao Zhang; Chang Bao Han (Journal of Hazardous Materials, 2023)

Toxicity of microplastics and triclosan, alone and in combination, to the fertilisation success of a broadcast spawning bivalve Tegillarca granosa - Lingzheng Lu; Wei Huang; Yu Han; Difei Tong; Shuge Sun; Yihan Yu; Guangxu Liu; Wei Shi (Environmental Toxicology and Pharmacology, 2023)

FDX1 enhances endometriosis cell cuproptosis via G6PD-mediated redox homeostasis - Jiayi Lu; Xi Ling; Yonghong Sun; Lu Liu; Lan Liu; Xiaoyun Wang; Chao Lu; Chune Ren; Xue Han; Zhenhai Yu (Apoptosis, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Investigation of underlying links between nitrogen transformation and microorganisms' network modularity in the novel static aerobic composting of dairy manure by “stepwise verification interaction analysis” - Yu Sun; Yonghui Xu; Jining Zhang; Ayodeji Bello; Xiang Li; Wanying Liu; Ugochi Uzoamaka Egbeagu; Liyan Zhao; Yue Han; Lijun Cheng; Wenhao Zhang; Qingxin Meng; et al. (Science of The Total Environment, 2023)

Risk assessment and binding mechanisms of potentially toxic metals in sediments from different water levels in a coastal wetland - Fusheng Sun; Guanghui Yu; Xingxing Han; Zhilai Chi; Yunchao Lang; Congqiang Liu (Journal of Environmental Sciences, 2023)

Formation of ferrihydrite induced by low pe+pH in paddy soil reduces Cd uptake by rice: Evidence from Cd isotope fractionation - Luyao Qin; Meng Wang; Xiaoyi Sun; Lei Yu; Jing Wang; Yun Han; Shibao Chen (Environmental Pollution, 2023)

Network prediction of surgical complication clusters: a prospective multicenter cohort study - Xiaochu Yu; Peng Wu; Zixing Wang; Wei Han; Yuguang Huang; Shijie Xin; Qiang Zhang; Shengxiu Zhao; Hong Sun; Guanghua Lei; Taiping Zhang; Luwen Zhang; et al. (Science China Life Sciences, 2023)

Bacterial community mapping of the AIA mouse gastrointestinal tract under dietary intervention with skipjack tuna (Katsuwonus pelamis) elastin peptides - Qiaoli Wu; Bing Liu; Rongxian Yu; Xiaoling Sun; Ziyan Wang; Jun Zhou; Chenyang Lu; Haitao Wan; Jing Zhang; Jiaojiao Han; Xiurong Su (Food Bioscience, 2023)

Anion assisted completely reconfigured manganese oxides with optimal proton adsorption for boosting acidic hydrogen evolution reaction - Wen Kang Zhao; Bei Chen Sun; Chang Bao Han; Kai Ling Zhou; Chao Wang; Jia Yu Zheng; Yuangang Lu; Decai Fang; Hui Yan (Chemical Engineering Journal, 2023)

RNA-Sequencing Reveals Gene Expression and Pathway Signatures in Umbilical Cord Blood Affected by Birth Delivery Mode - Yongjie Liu; Kun Sun; Yuexin Gan; Han Liu; Juehua Yu; Wei Xu; Lin Zhang; Dan Chen (Phenomics, 2023)

Effects of instantaneous changes in temperature, light, and salinity on the dynamics of dissolved organic carbon release by Sargassum thunbergii - Zhi-Fang Zhao; Zhong-Jian Huang; Zuo-Deng Sun; Zheng-Yi Liu; Song Qin; Tong Han; Xin-Yu Qi; Xi-Yan Sun; Zhi-Hai Zhong (Marine Pollution Bulletin, 2023)

RETRACTED: PBAT/PLA humic acid biodegradable film applied on solar greenhouse tomato plants increased lycopene and decreased total acid contents - Lu Lu; Ying Han; Jiayin Wang; Jing Xu; Yansu Li; Mintao Sun; Fujian Zhao; Chaoxing He; Yujun Sun; Yijia Wang; Pengfei Huang; Xianchang Yu; et al. (Science of The Total Environment, 2023)

Effects of the water-soluble fraction of diesel oil on the sera biochemical indicators, histological changes, and immune responses of black rockfish Sebastes schlegelii - Yingli Gao; Zeyu Li; Gaoshang Han; Lu Qiang; Yungui Sun; Ruiming Tan; Yongxiang Yu (Marine Environmental Research, 2023)

Characteristics of changes in volatile organic compounds and microbial communities during the storage of pickles - Xi-han Sun; Xin Qi; Yu-di Han; Zhi-jun Guo; Cheng-bi Cui; Chang-qing Lin (Food Chemistry, 2023)

A new strategy to alleviate the obesity induced by endocrine disruptors—A unique lysine metabolic pathway of nanoselenium Siraitia grosvenorii to repair gut microbiota and resist obesity - Yu Wang; Wei Sun; Sen Yan; Zhiyuan Meng; Ming Jia; Sinuo Tian; Shiran Huang; Xiaoxuan Sun; Shihang Han; Canping Pan; Jinling Diao; Qiuxia Wang; et al. (Food and Chemical Toxicology, 2023)

Mammalian carcass decay increases carbon storage and temporal turnover of carbon-fixing microbes in alpine meadow soil - Xiaochen Wang; Qian Han; Qiaoling Yu; Sijie Wang; Jiawei Yang; Wanghong Su; Ruijun Wan-Yan; Xiaofang Sun; Huan Li (Environmental Research, 2023)

The phosphorus limitation in the post-fire forest soils increases soil CO2 emission via declining cellular carbon use efficiency and increasing extracellular phosphatase - Muhammad Auwal; Han Sun; U.K Adamu; Jun Meng; Lukas Van Zwieten; Bhupinder Pal Singh; Yu Luo; Jianming Xu (CATENA, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Plant and fungal species interactions differ between aboveground and belowground habitats in mountain forests of eastern China - Teng Yang; Leho Tedersoo; Pamela S. Soltis; Douglas E. Soltis; Miao Sun; Yuying Ma; Yingying Ni; Xu Liu; Xiao Fu; Yu Shi; Han-Yang Lin; Yun-Peng Zhao; et al. (Science China Life Sciences, 2023)

Improved torque compensation control based-maximum power point tracking strategy for large scale floating offshore wind turbines - Hao Chen; Yu Sun; Youming Cai; Jean-Frédéric Charpentier; Jingang Han; Nadia Aït-Ahmed; Mohamed Benbouzid (Ocean Engineering, 2023)

Proteomic analysis reveals differential responsive mechanisms in Solanum nigrum exposed to low and high dose of cadmium - Ling-Yu Song; Xiang Liu; Lu-Dan Zhang; Wen-Jun Hu; Chao-Qun Xu; Jing Li; Shi-Wei Song; Ze-Jun Guo; Chen-Yang Sun; Han-Chen Tang; Ji-Cheng Wang; Xue-Yi Zhu; et al. (Journal of Hazardous Materials, 2023)

Study of CO2 solubility enhancement by nanomaterials in carbonated water: Implications for enhanced oil recovery and CO2 storage - Xiaofei Sun; Haoyu Ning; Yuhao Shi; Guo Yu; Zixiong Jia; Mingen Han; Yanyu Zhang (Journal of Cleaner Production, 2023)

Multilevel driving factors affecting ecosystem services and biodiversity dynamics on the Qinghai-Tibet Plateau - Hua Liu; Shiliang Liu; Fangfang Wang; Yixuan Liu; Zhenli Han; Qingbo Wang; Lu Yu; Yuhong Dong; Jian Sun (Journal of Cleaner Production, 2023)

Nano-sized alumina supported palladium catalysts for methane combustion with excellent thermal stability - Wei Shi; Guangyan Xu; Xuewang Han; Yingjie Wang; Zhi Liu; Sen Xue; Nannan Sun; Xiaoyan Shi; Yunbo Yu; Hong He (Journal of Environmental Sciences, 2023)

Formation of ferritin-agaro oligosaccharide-epigallocatechin gallate nanoparticle induced by CHAPS and partitioned by the ferritin shell with enhanced delivery efficiency - Rui Yang; Junrui Ma; Jiangnan Hu; Haili Sun; Yu Han; Demei Meng; Zhiwei Wang; Lei Cheng (Food Hydrocolloids, 2023)

Preclinical Evaluation of an Everolimus-Eluting Bioresorbable Vascular Scaffold Via a Long-Term Rabbit Iliac Artery Model - Dae Sung Park; Myung Ho Jeong; Yu Jeong Jin; Mi Hyang Na; Doo Sun Sim; Munki Kim; Kyung Hoon Cho; Dae Young Hyun; Seok Oh; Jeong Ha Kim; Kyung Seob Lim; Jun-Kyu Park; et al. (Tissue Engineering and Regenerative Medicine, 2023)

Collinsella urealyticum sp. nov., a urease-positive bacterial strain isolated from swine faeces - Byeong Seob Oh; Seoung Woo Ryu; Seung Yeob Yu; Jeong Eun Bak; Won Jung Choi; Ji-Sun Kim; Jung-Sook Lee; Seung-Hwan Park; Se Won Kang; Jiyoung Lee; Mi-Kyung Lee; Won Yong Jung; et al. (Archives of Microbiology, 2023)

Ecological carrying capacity and carbon sequestration potential of bivalve shellfish in marine ranching: A case study in Bohai Bay, China - Zepeng Li; Yan Chen; Gang Wang; Jiandong Mu; Yanfeng Sun; Haolin Yu; Jiangling Xu; Ying Yan; Shuangyue Luo; Fuqiang Han; Jie Feng; Zhe Pan (Frontiers in Marine Science, 2023)
Introduction Shellfish play an important role in ecological restoration and as carbon (C) sinks, but studies on their ecological carrying capacity (ECC) and C sequestration potential are sparse. Methods In this study, we selected a 57-hectare artificial oyster reef in a typical marine ranching in Bohai Bay, China, to evaluate the ECC and their C sequestration potential of bivalve shellfish, and projecting their impact on functional groups in the system, with an Ecopath with Ecosim (EwE) food web model. We conducted four biological surveys to obtain the biomass measurements, with one conducted in each of the summer, autumn, and winter of 2019 and one in the spring of 2020; and the functional groups included in the surveys comprised fish, cephalopods, crustaceans, snails, bivalve shellfish, annelids, other macrobenthos, meiobenthos, starfish, sea cucumbers, zooplankton, phytoplankton, and detritus. Results and Discussion The EwE model prediction results showed that the ECC of bivalve shellfish was established to be 282.66 t/km 2 , far more than the existing quantity of 187.76 t/km 2 . Therefore, at present, the ecosystem of the study marine ranching is not yet mature. Moreover, our ecological network analysis parameters indicated that the marine ranching ecosystem will be mature and stable when the bivalve shellfish population reaches its ECC. However, the increase in bivalve shellfish biomass will result in a decrease in the population sizes of species competing for food resources with bivalve shellfish, mainly gobiid fish such as Tridentiger bifasciatus, Tridentiger trigonocephalus, Tridentiger barbatus . Simultaneously, when the bivalve shellfish reach their ECC, 29.23 t of CO 2 can be sequestrated by bivalve shellfish, comprising 14.32 t being removed from the ecosystem as prey and 14.91 t being stored on the seafloor through biodeposition. Conclusion Therefore, the research demonstrated that, within the scope of ECC, the increasing bivalve shellfish can improve the C sequestration capacity of the marine ranch ecosystem, and effective management of bivalve shellfish in marine ranching can improve the economic benefits and C sink service functions of marine ranching.

Evaluation of BDE-47-induced neurodevelopmental toxicity in zebrafish embryos - Juan Zhuang; Zheng-jun Pan; Ying Qin; Hui Liang; Wen-feng Zhang; Ze-yu Sun; Han-bo Shi (Environmental Science and Pollution Research, 2023)

Single bubble probe atomic force microscope and impinging-jet technique unravel the interfacial interactions controlled by long chain fatty acid in anaerobic digestion - Jian-Lu Duan; Yi Han; Li-Juan Feng; Jing-Ya Ma; Xiao-Dong Sun; Xiao-Yu Liu; Fan-Shu Geng; Jia-Li Jiang; Mei-Yan Liu; Yu-Chen Sun; Pascal Peu; Bing-Jie Ni; et al. (Water Research, 2023)

Benzimidazole fungicide biotransformation by comammox Nitrospira bacteria: Transformation pathways and associated proteomic responses - Ping Han; Ana B. Rios-Miguel; Xiufeng Tang; Yaochun Yu; Li-Jun Zhou; Lijun Hou; Min Liu; Dongyao Sun; Mike S.M. Jetten; Cornelia U. Welte; Yujie Men; Sebastian Lücker (Journal of Hazardous Materials, 2023)

QTL detection for internode diameter and its association with yield-related traits in wheat - Haitao Yu; Yanan Liu; Zongfeng Zou; Xusheng Sun; Jinshan Zhang; Shun Song; Lijie Wang; Ran Qin; Han Sun; Fa Cui; Chunhua Zhao; Shubing Shi (Cereal Research Communications, 2023)

Geographical distance, host evolutionary history and diet drive gut microbiome diversity of fish across the Yellow River - Baozhu Pan; Xu Han; Ke Yu; He Sun; Rong Mu; Chun‐Ang Lian (Molecular Ecology, 2023)
Fish represent a large part of the taxonomic diversity of vertebrates and are of high commercial value. However, the factors influencing the gut microbiota composition of freshwater fish over large spatial scales remain unclear. Therefore, this study explored gut microbiome diversity in 24 fish species from the Yellow River, which spans over 1500 km across China. The results showed that geographical distance, host phylogeny and diet significantly influenced gut microbial community diversity, whereas sex, body length and body weight had minimal influence. Geographical distance was the primary factor shaping gut microbiota, and dissimilarity in microbial community structure increased with an increase in geographical distance, which was mainly driven by dispersal limitation. The microbial communities were more homogeneous at higher host taxonomic resolutions due to the dominant role of homogeneous selection in community convergence. Phylosymbiosis was observed across all host species, with a stronger pattern in Cypriniformes, which harbour host‐specific microbial taxa. Host diet explained little variation in gut microbiome diversity, although it was significant for all diversity metrics tested. These findings collectively suggest that the geographical and host‐based patterns of fish gut microbiota tend to be shaped by different ecological forces across the Yellow River. The present work provides a robust assessment of multiple factors driving fish gut microbial community assembly and offers insight into the mechanisms underlying shifts in fish gut microbiota in rivers across large spatial scales.

Evaluation of the distribution and mobility of labile phosphorus in sediment profiles of Lake Nansi, the largest eutrophic freshwater lake in northern China - Ye Zheng; Yu Sun; Zhihong Zhang; Chao Han; Zhaode Wang; Cheng Liu; Fan Ke; Lei Zhang; Qiushi Shen (Chemosphere, 2023)

Toxicity effects of nanoplastics on soybean (Glycine max L.): Mechanisms and transcriptomic analysis - Guankai Qiu; Zhongmin Han; Quanying Wang; Tianye Wang; Zhenghao Sun; Yong Yu; Xuerong Han; Hongwen Yu (Chemosphere, 2023)

Metagenomics reveals the response of antibiotic resistance genes to elevated temperature in the Yellow River - Qiaoling Yu; Qian Han; Shunqin Shi; Xiaofang Sun; Xiaochen Wang; Sijie Wang; Jiawei Yang; Wanghong Su; Zhibiao Nan; Huan Li (Science of The Total Environment, 2023)

Co-substrate promoting the biodegradation of refractory DOM in semi-coking wastewater: DOM evolution and microbial community - Min-Hui Cai; Ye-Chao Tian; Ai-Min Li; Yan Li; Yu-Ze Han; Jun Li; Hong-Fang Sun; Xin Wang; Qing Zhou; Wen-Tao Li (Journal of Environmental Chemical Engineering, 2023)

Modeling on the phase equilibrium of gas hydrate in electrolytes containing system - Jin Cai; Xiao-Hui Wang; Peng Xiao; Han Tang; Bei Liu; Chang-Yu Sun; Guang-Jin Chen (Fuel, 2023)

Deciphering biochar compost co-application impact on microbial communities mediating carbon and nitrogen transformation across different stages of corn development - Ayodeji Bello; Wanying Liu; Nuo Chang; Kehinde Olajide Erinle; Liting Deng; Ugochi Uzoamaka Egbeagu; Busayo Joshua Babalola; Han Yue; Yu Sun; Zimin Wei; Xiuhong Xu (Environmental Research, 2023)

Regulating desolvation and homogenized ion flux towards highly reversible dendrite-free zinc anode - Xin Qi; Fuli Xie; Yu-Ting Xu; Hai Xu; Cheng-Lin Sun; Sheng-Han Wang; Jian-Yong Hu; Xiao-Feng Wang (Chemical Engineering Journal, 2023)

Facile electrochemically induced vacancy modulation of NiCo2O4 cathode toward high-performance aqueous Zn-based battery - Yu Zhang; Dan Sun; Yixun Wang; Xiaoqi Liu; Hongman Sun; Tonghui Cai; Xuejin Li; Han Hu; Xiaoyun Zhang; Wei Xing; Zifeng Yan (Chemical Engineering Journal, 2023)

Impacts of the COVID-19 lockdown on atmospheric oxidizing capacity and secondary aerosol formation over the Beijing-Tianjin-Hebei region in Winter-Spring 2020 - Yue Li; Zhiwei Han; Yu Song; Jiawei Li; Yele Sun; Tiantian Wang (Atmospheric Environment, 2023)

Spatiotemporal Dynamics of the Molecular Expression Pattern and Intercellular Interactions in the Glial Scar Response to Spinal Cord Injury - Leilei Gong; Yun Gu; Xiaoxiao Han; Chengcheng Luan; Chang Liu; Xinghui Wang; Yufeng Sun; Mengru Zheng; Mengya Fang; Shuhai Yang; Lai Xu; Hualin Sun; et al. (Neuroscience Bulletin, 2023)
Nerve regeneration in adult mammalian spinal cord is poor because of the lack of intrinsic regeneration of neurons and extrinsic factors – the glial scar is triggered by injury and inhibits or promotes regeneration. Recent technological advances in spatial transcriptomics (ST) provide a unique opportunity to decipher most genes systematically throughout scar formation, which remains poorly understood. Here, we first constructed the tissue-wide gene expression patterns of mouse spinal cords over the course of scar formation using ST after spinal cord injury from 32 samples. Locally, we profiled gene expression gradients from the leading edge to the core of the scar areas to further understand the scar microenvironment, such as neurotransmitter disorders, activation of the pro-inflammatory response, neurotoxic saturated lipids, angiogenesis, obstructed axon extension, and extracellular structure re-organization. In addition, we described 21 cell transcriptional states during scar formation and delineated the origins, functional diversity, and possible trajectories of subpopulations of fibroblasts, glia, and immune cells. Specifically, we found some regulators in special cell types, such as Thbs1 and Col1a2 in macrophages, CD36 and Postn in fibroblasts, Plxnb2 and Nxpe3 in microglia, Clu in astrocytes, and CD74 in oligodendrocytes. Furthermore, salvianolic acid B, a blood–brain barrier permeation and CD36 inhibitor, was administered after surgery and found to remedy fibrosis. Subsequently, we described the extent of the scar boundary and profiled the bidirectional ligand-receptor interactions at the neighboring cluster boundary, contributing to maintain scar architecture during gliosis and fibrosis, and found that GPR37L1_PSAP, and GPR37_PSAP were the most significant gene-pairs among microglia, fibroblasts, and astrocytes. Last, we quantified the fraction of scar-resident cells and proposed four possible phases of scar formation: macrophage infiltration, proliferation and differentiation of scar-resident cells, scar emergence, and scar stationary. Together, these profiles delineated the spatial heterogeneity of the scar, confirmed the previous concepts about scar architecture, provided some new clues for scar formation, and served as a valuable resource for the treatment of central nervous system injury.

Improved Seafloor Geodetic Positioning via Sound Velocity Correction Based on the Precise Round-Trip Acoustic Positioning Model - Dajun Sun; Miao Yu; Cuie Zheng; Yunfeng Han; Zongyan Li (Marine Geodesy, 2023)

Using colloidal AFM probe technique and XDLVO theory to predict the transport of nanoplastics in porous media - Li-Juan Feng; Zong-Lin Shi; Jian-Lu Duan; Yi Han; Xiao-Dong Sun; Jing-Ya Ma; Xiao-Yu Liu; Huan-Xin Zhang; Ning Guo; Chao Song; Wan-Song Zong; Xian-Zheng Yuan (Chemosphere, 2023)

Influence of aged and pristine polyethylene microplastics on bioavailability of three heavy metals in soil: Toxic effects to earthworms (Eisenia fetida) - Ming Li; Hao Jia; Qingchuan Gao; Song Han; Yong Yu; Long Sun (Chemosphere, 2023)

Urbanization effects on intensifying extreme precipitation in the rapidly urbanized Tai Lake Plain in East China - Chaogui Lei; Zhihui Yu; Xiuming Sun; Yuefeng Wang; Jia Yuan; Qiang Wang; Longfei Han; Youpeng Xu (Urban Climate, 2023)

Triptolide exposure induces oxidative stress and decreases oocyte quality in mouse - Qian-Qian Hao; Zhi-Ran Xu; Han Nie; Feng-Xin Qiao; Ming-Xin Sun; Yue-Cen Liu; Hai-Long Wang; Zhong-Quan Qi; Chang-Long Xu; Yu Liu (Toxicon, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Synergistic effect of hydrogen and nanoscale zero-valent iron on ex-situ biogas upgrading and acetate recovery - Kai-Kai Wu; Lei Zhao; Zhong-Fang Sun; Zi-Han Wang; Chuan Chen; Hong-Yu Ren; Shan-Shan Yang; Nan-Qi Ren (Science of The Total Environment, 2023)

Interannual variation and sources identification of heavy metals in seawater near shipping lanes: Evidence from a coral record from the northern South China Sea - Sirong Xie; Wei Jiang; Yinan Sun; Kefu Yu; Chunmei Feng; Yansong Han; Yuwen Xiao; Chaoshuai Wei (Science of The Total Environment, 2023)

Exploration of β-glucosidase-producing microorganisms community structure and key communities driving cellulose degradation during composting of pure corn straw by multi-interaction analysis - Yue Han; Wanying Liu; Nuo Chang; Lei Sun; Ayodeji Bello; Liting Deng; Liyan Zhao; Ugochi Uzoamaka Egbeagu; Bo Wang; Yan Zhao; Mingming Zhao; Ruixin Bi; et al. (Journal of Environmental Management, 2023)

Resource utilization of bovine bone to prepare biochar as persulfate activator for phenol degradation - Mingze Sun; Jianhua Qu; Tianyi Han; Jiaqi Xue; Kaige Li; Zhao Jiang; Guangshan Zhang; Hui Yu; Ying Zhang (Journal of Cleaner Production, 2023)

Effectiveness and degradation pathways of bisphenol A (BPA) initiated by hydroxyl radicals and sulfate radicals in water: Initial reaction sites based on DFT prediction - Qi Han; Mingming Wang; Feiyun Sun; Boping Yu; Zijun Dong; Pu Li; Jingwen Luo; Mu Li; Xingliang Jin; Zhiguang Dai (Environmental Research, 2023)

Overview of preparation, modification, and application of tunicate-derived nanocellulose - Xiaoyu Lv; Jianing Han; Min Liu; Hui Yu; Kaihua Liu; Yifan Yang; Yi Sun; Panpan Pan; Zhenlin Liang; Lirong Chang; Jingdi Chen (Chemical Engineering Journal, 2023)

The Nucleus Accumbens CRH–CRHR1 System Mediates Early-Life Stress-Induced Sleep Disturbance and Dendritic Atrophy in the Adult Mouse - Ting Wang; Yu-Nu Ma; Chen-Chen Zhang; Xiao Liu; Ya-Xin Sun; Hong-Li Wang; Han Wang; Yu-Heng Zhong; Yun-Ai Su; Ji-Tao Li; Tian-Mei Si (Neuroscience Bulletin, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Immunogenicity and protective efficacy of a DNA vaccine inducing optimal expression of the SARS-CoV-2 S gene in hACE2 mice - Zhuo-xin Li; Sheng Feng; He Zhang; Xin-yu Zhuang; Chao Shang; Shi-yu Sun; Ji-cheng Han; Yu-biao Xie; Jin-yong Zhang; Wei Wang; Cheng-hui Li; Guan-yu Zhao; et al. (Archives of Virology, 2022)

A designed plasmid‐transition strategy enables rapid construction of robust and versatile synthetic exoelectrogens for environmental applications - Yang‐Yang Fan; Qiang Tang; Hong Sun; Han‐Qing Yu (Environmental Microbiology, 2022)
Genetic engineering is promising to expand the application scope of exoelectrogens in energy and environmental applications and plasmid vectors, as one type of fundamental tool, are intensively applied. Antibiotics are widely utilized for plasmid selection and maintenance; however, their utilization suffers from environmental concerns on the spread of resistance genes, elevated costs, inevitable genotypic instability and phenotypic heterogeneity. In this work, we establish an auxotrophic complementation system for stable plasmid maintenance without antibiotic association, in Shewanella oneidensis , an attractive model exoelectrogen. A plasmid‐transition strategy is designed to facilitate the rapid and efficient construction of the auxotrophic complementation system. Such a system not only enables the same intensive gene expression as the conventional antibiotic‐associated plasmid system but also exhibits remarkably superior robustness and stability. With this system, the menaquinone pool of the extracellular respiratory chain is enhanced first independently and further synergized by engineering the Mtr conduit, leading to significantly promoted extracellular electron transfer (EET) outputs (up to 10.33‐ and 2.97‐fold improvement in the maximum current density and the maximum output voltage) and heavy metal Cr(VI) reduction ability (5.15‐fold improvement). This work provides a robust and stable platform to engineer exoelectrogens for environmental applications.

Lignans from Bupleurum marginatum and their antioxidant activity - Jian Zhou; Xin He; Rongjin Sun; Zhenlong Yu; Chao Wang; Sa Deng; Baojing Zhang; Shanshan Huang; Chunhui Han; Dawei Li (Natural Product Research, 2022)

Paracandidimonas lactea sp. nov., a urea-utilizing bacterium isolated from landfill - Chu Zhang; Qian Pu; Jun-jie Ying; Ying Chen; Cheng-ze Li; Hang-tao Wu; Bin-jie Wang; Yu-han Zhang; Guo-hong Zeng; Ou Li; Xiu-fang Hu; Cong Sun (Archives of Microbiology, 2022)

Validity Analysis of the Morphological Identification of Three Highly Morphologically Similar Species Belonging to the Genus Niviventer (Rodentia: Muridae) - Yao-Yao Li; Hao-Tian Li; Jia-Wei Hao; Chen-Yi Zhang; Guan-Ze Liu; Xing-Han Lin; Xiao-Qing Sun; Guo-Chen Zang; Yu-Chun Li (Journal of Mammalian Evolution, 2022)

Complete mitochondrial genomes of Thyreophagus entomophagus and Acarus siro (Sarcoptiformes: Astigmatina) provide insight into mitogenome features, evolution, and phylogeny among Acaroidea mites - Yu Fang; Mingzhong Sun; Ying Fang; Zetao Zuo; Luyao Liu; Lingmiao Chu; Lan Ding; Caixiao Hu; Feiyan Li; Renrui Han; Xingquan Xia; Shulin Zhou; et al. (Experimental and Applied Acarology, 2022)

Fried-food consumption and risk of overweight/obesity, type 2 diabetes mellitus, and hypertension in adults: a meta-analysis of observational studies - Pei Qin; Dechen Liu; Xiaoyan Wu; Yunhong Zeng; Xizhuo Sun; Yanyan Zhang; Yang Li; Yuying Wu; Minghui Han; Ranran Qie; Shengbing Huang; Yang Zhao; et al. (Critical Reviews in Food Science and Nutrition, 2022)

Two new 2,5-diketopiperazine derivatives from mangrove-derived endophytic fungus Nigrospora camelliae-sinensis S30 - Dan-Yu Huang; Xu-Hua Nong; Yu-Qin Zhang; Wei Xu; Long-Yu Sun; Tao Zhang; Guang-Ying Chen; Chang-Ri Han (Natural Product Research, 2022)

Knowledge Difference of Tumor Nutrition Risk Among Thoracic Cancer Patients, Their Family Members, Physicians, and Nurses - Jiaojiao Suo; Yu Sun; Weigang Xiu; Yan Fu; Yijia Qin; Lili Zhong; Jialong Han; Huijie Zhou; Hao Wei; Yan Wang; Jiang Zhu (Journal of Cancer Education, 2022)

Curcumin Inhibits Cell Damage and Apoptosis Caused by Thapsigargin-Induced Endoplasmic Reticulum Stress Involving the Recovery of Mitochondrial Function Mediated by Mitofusin-2 - He-Yan Zhou; Yu-Ying Sun; Ping Chang; Han-Chang Huang (Neurotoxicity Research, 2022)

Altered Connectedness of the Brain Chronnectome During the Progression to Alzheimer’s Disease - Maryam Ghanbari; Zhen Zhou; Li-Ming Hsu; Ying Han; Yu Sun; Pew-Thian Yap; Han Zhang; Dinggang Shen (Neuroinformatics, 2022)

Lanthanum Impairs Learning and Memory by Activating Microglia in the Hippocampus of Mice - Licheng Yan; Jinghua Yang; Miao Yu; Wenchang Sun; Yarao Han; Xiaobo Lu; Cuihong Jin; Shengwen Wu; Yuan Cai (Biological Trace Element Research, 2022)

Overexpression of MxWRKY53 increased iron and high salinity stress tolerance in Arabidopsis thaliana - Deguo Han; Tianlong Xu; Jiaxin Han; Wanda Liu; Yu Wang; Xingguo Li; Xiaohan Sun; Xinhui Wang; Tiemei Li; Guohui Yang (In Vitro Cellular & Developmental Biology - Plant, 2022)

The adaptation mechanism based on an integrated vulnerability assessment of potato production to climate change in Inner Mongolia, China - Na Huang; Jialin Wang; Yu Song; Yuying Pan; Guolin Han; Ziyuan Zhang; Shangqian Ma; Guofeng Sun; Cong Liu; Zhihua Pan (Mitigation and Adaptation Strategies for Global Change, 2022)

Alteribacter salitolerans sp. nov., isolated from a saline-alkaline soil - Shuang Wang; Lei Sun; Manik Prabhu Narsing Rao; Guo-Hong Liu; Pin-Jiao Jin; Zhou-Yan Dong; Zheng-Han Lian; Xiao-Yu Hao; Ming-Yi Zhang; Wen-Jun Li (Archives of Microbiology, 2022)

Genome sequence analysis of Cronobacter phage PF-CE2 and proposal of a new species in the genus Pseudotevenvirus - Mengshi Xiao; Xinmiao Ren; Ying Yu; Han Sun; Haijin Mou; Xiaodan Fu (Archives of Virology, 2021)

A New Instrumental Array in Sichuan, China, to Monitor Vibrations and Perturbations of the Lithosphere, Atmosphere, and Ionosphere - Chieh-Hung Chen; Yang-Yi Sun; Kai Lin; Chen Zhou; Rui Xu; Haiyin Qing; Yongxin Gao; Tao Chen; Fei Wang; Huaizhong Yu; Peng Han; Chi-Chia Tang; et al. (Surveys in Geophysics, 2021)

Characteristics of ambient ammonia and its effects on particulate ammonium in winter of urban Beijing, China - Rui Zhang; Yuhua Han; Aijun Shi; Xuesong Sun; Xiao Yan; Yuhu Huang; Yu Wang (Environmental Science and Pollution Research, 2021)

Zircon U–Pb geochronology from a Paleoproterozoic mafic dyke in the Jiapigou terrane (North China Craton): inferences about formation and evolution of the early crust - Shu Wang; Jinggui Sun; Ridong Yu; Jilong Han; Yuming Liu; Xiaolei Chu; Xinwen Zhang (Arabian Journal of Geosciences, 2021)

Social disruption–induced stress pre-exposure aggravates, while the presence of conspecifics diminishes, acetic acid–induced writhing - Yi-Han Liao; Yi-Chi Su; Yu-Han Huang; Hao Chen; Ya-Hsuan Chan; Li-Han Sun; Chianfang G. Cherng; Ing-Tiau B. Kuo; Lung Yu (Psychopharmacology, 2021)

GmFULa improves soybean yield by enhancing carbon assimilation without altering flowering time or maturity - Yanlei Yue; Shi Sun; Jiawen Li; Haidong Yu; Hongxia Wu; Baiquan Sun; Tao Li; Tianfu Han; Bingjun Jiang (Plant Cell Reports, 2021)
Key message GmFULa improved soybean yield by enhancing carbon assimilation. Meanwhile, different from known yield-related genes, it did not alter flowering time or maturity. Abstract Soybean ( Glycine max (L.) Merr.) is highly demanded by a continuously growing human population. However, increasing soybean yield is a major challenge. FRUITFULL ( FUL ), a MADS-box transcription factor, plays important roles in multiple developmental processes, especially fruit and pod development, which are crucial for soybean yield formation. However, the functions of its homologs in soybean are not clear. Here, through haplotype analysis, we found that one haplotype of the soybean homolog GmFULa ( GmFULa-H02 ) is dominant in cultivated soybeans, suggesting that GmFULa-H02 was highly selected during domestication and varietal improvement of soybean. Interestingly, transgenic overexpression of GmFULa enhanced vegetative growth with more biomass accumulated and ultimately increased the yield but without affecting the plant height or changing the flowering time and maturity, indicating that it enhances the efficiency of dry matter accumulation. It also promoted the yield factors like branch number, pod number and 100-seed weight, which ultimately increased the yield. It increased the palisade tissue cell number and the chlorophyll content to promote photosynthesis and increase the soluble sugar content in leaves and fresh seeds. Furthermore, GmFULa were found to be sublocalized in the nucleus and positively regulate sucrose synthases ( SUSs ) and sucrose transporters ( SUTs ) by binding with the conserved CArG boxes in their promoters. Overall, these results showed GmFULa promotes the capacity of assimilation and the transport of the resultant assimilates to increase yield, and provided insights into the link between GmFULa and sucrose synthesis with transport-related molecular pathways that control seed yield.

Collinsella acetigenes sp. nov., an Anaerobic Actinobacterium Isolated from Human Feces, and Emended Description of the Genus Collinsella and Collinsella aerofaciens - Kook-Il Han; Ji-Sun Kim; Mi Kyung Eom; Keun Chul Lee; Min Kuk Suh; Han Sol Kim; Seung-Hwan Park; Ju Huck Lee; Se Won Kang; Jam-Eon Park; Byeong Seob Oh; Seoung Woo Ryu; et al. (Current Microbiology, 2021)

Screening and application of SSR markers related to seed storability traits in maize (Zea mays L.) - Xiaoyang Guo; Xiaohui Sun; Shan Liu; Chengxu Gong; Chenchen Feng; Xiao Han; Tingting Lv; Yu Zhou; Zhenhua Wang; Hong Di (Genetic Resources and Crop Evolution, 2021)

Lipid biomarker composition in surface sediments from the Carlsberg Ridge near the Tianxiu Hydrothermal Field - Shengyi Mao; Hongxiang Guan; Lihua Liu; Xiqiu Han; Xueping Chen; Juan Yu; Yongge Sun; Yejian Wang (Acta Oceanologica Sinica, 2021)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

The Knowledge and Attitude Towards Advance Care Planning Among Chinese Patients with Advanced Cancer - Xiao-Ting Hou; Yu-Han Lu; Hong Yang; Ren-Xiu Guo; Yun Wang; Li-Hong Wen; Ya-Ru Zhang; Hong-Yu Sun (Journal of Cancer Education, 2021)

A Novel Method to Differentiate Tonsil-Derived Mesenchymal Stem Cells In Vitro into Estrogen-Secreting Cells - Hee-Yeon Kim; Younghay Lee; Hee-Soo Yoon; Yu-Hee Kim; Kyong-A Cho; So-Youn Woo; Han Sun Kim; Bo-Young Park; Sung-Chul Jung; Inho Jo; Woo-Jae Park; Joo-Won Park; et al. (Tissue Engineering and Regenerative Medicine, 2021)

Marinobacter shengliensis subsp. alexandrii Subsp. Nov., Isolated from Cultivable Phycosphere Microbiota of Highly Toxic Dinoflagellate Alexandrium catenella LZT09 and Description of Marinobacter shengliensis Subsp. shengliensis Subsp. Nov - Xi Yang; Rong Xiang; Nurhezreen Md Iqbal; Yu-Han Duan; Xiao-Ai Zhang; Lei Wang; Lin-Zeng Yu; Jia-Zhou Li; Ming-Fei Sun; Qiao Yang; Chun-Tian Zheng; Shen-Quan Liao (Current Microbiology, 2021)

Polybrominated diphenyl ethers in soils from Tianjin, North China: distribution, health risk, and temporal trends - Yu Han; Jiali Cheng; Lei He; Minna Zhang; Shan Ren; Jiazheng Sun; Xiangyang Xing; Zhenwu Tang (Environmental Geochemistry and Health, 2021)

Effects of degradation succession of alpine wetland on soil organic carbon and total nitrogen in the Yellow River source zone, west China - Chun-ying Lin; Xi-lai Li; Jing Zhang; Hua-fang Sun; Juan Zhang; Hui-bang Han; Qi-hua Wang; Cheng-biao Ma; Cheng-yi Li; Yu-xing Zhang; Xue-qian Ma (Journal of Mountain Science, 2021)

The adaptability of typical precipitation ensemble prediction systems in the Huaihe River basin, China - Han Wang; Ping-an Zhong; Fei-lin Zhu; Qing-wen Lu; Yu-fei Ma; Sun-yu Xu (Stochastic Environmental Research and Risk Assessment, 2021)

Diversity-oriented synthesis and antifungal activities of novel pimprinine derivative bearing a 1,3,4-oxadiazole-5-thioether moiety - Zi-Long Song; Yun Zhu; Jing-Rui Liu; Shu-Ke Guo; Yu-Cheng Gu; Xinya Han; Hong-Qiang Dong; Qi Sun; Wei-Hua Zhang; Ming-Zhi Zhang (Molecular Diversity, 2021)

Modes of genetic adaptations underlying functional innovations in the rumen - Xiangyu Pan; Yudong Cai; Zongjun Li; Xianqing Chen; Rasmus Heller; Nini Wang; Yu Wang; Chen Zhao; Yong Wang; Han Xu; Songhai Li; Ming Li; et al. (Science China Life Sciences, 2021)

Nutrients Have a Different Impact on the Salt Tolerance of Two Coexisting Suaeda Species in the Yellow River Delta - Qi-Hui Zhang; Kulihong Sairebieli; Ming-Ming Zhao; Xiao-Han Sun; Wei Wang; Xiao-Na Yu; Ning Du; Wei-Hua Guo (Wetlands, 2020)

Predicting Functional Outcome Based on Linked Data After Acute Ischemic Stroke: S-SMART Score - Tae Jung Kim; Ji Sung Lee; Mi-Sun Oh; Ji-Woo Kim; Jae Sun Yoon; Jae-Sung Lim; Chan-Hyuk Lee; Heejung Mo; Han-Yeong Jeong; Yerim Kim; Sang-Hwa Lee; Keun-Hwa Jung; et al. (Translational Stroke Research, 2020)

Histopathology, Molecular Identification and Antifungal Susceptibility Testing of Nannizziopsis arthrosporioides from a Captive Cuban Rock Iguana (Cyclura nubila) - Yen-Han Chen; Meng-Jou Chi; Pei-Lun Sun; Pin-Huan Yu; Chen-Hsuan Liu; Jose F. Cano-Lira; Wen-Ta Li (Mycopathologia, 2020)

Infusion of Human Mesenchymal Stem Cells Improves Regenerative Niche in Thioacetamide-Injured Mouse Liver - Ying-Hsien Kao; Yu-Chun Lin; Po-Huang Lee; Chia-Wei Lin; Po-Han Chen; Tzong-Shyuan Tai; Yo-Chen Chang; Ming-Huei Chou; Chih-Yang Chang; Cheuk-Kwan Sun (Tissue Engineering and Regenerative Medicine, 2020)

The gut-microbiota-testis axis mediated by the activation of the Nrf2 antioxidant pathway is related to prepuberal steroidogenesis disorders induced by di-(2-ethylhexyl) phthalate - Tian-Xin Zhao; Yue-Xin Wei; Jun-Ke Wang; Lin-Dong Han; Mang Sun; Yu-Hao Wu; Lian-Ju Shen; Chun-Lan Long; Sheng-De Wu; Guang-Hui Wei (Environmental Science and Pollution Research, 2020)

Extracellular ATP affects cell viability, respiratory O2 uptake, and intracellular ATP production of tobacco cell suspension culture in response to hydrogen peroxide-induced oxidative stress - Qin-zheng Hou; Yu-pei Wang; Bao-qiang Fan; Kun Sun; Jun-yu Liang; Han-qing Feng; Ling-yun Jia (Biologia, 2020)

A Facile and Sensitive DNA Sensing of Harmful Algal Blooms Based on Graphene Oxide Nanosheets - Le Qiang; Yu Zhang; Chao Wu; Yingkuan Han; Suchun Wang; Yanyan Wang; Congcong Zhang; Guangzhou Liu; Qi Wu; Hong Liu; Ian R. Jenkinson; Jun Sun; et al. (Marine Biotechnology, 2020)

Mesorhizobium rhizophilum sp. nov., a 1-aminocyclopropane-1-carboxylate deaminase producing bacterium isolated from rhizosphere of maize in Northeast China - Jun-lian Gao; Jing Xue; Yu-chen Sun; Han Xue; En Tao Wang; Hui Yan; Shuai Tong; Li-wei Wang; Xiuhai Zhang; Jian-guang Sun (Antonie van Leeuwenhoek, 2020)

Targeting Inflammation, PHA-767491 Shows a Broad Spectrum in Protein Aggregation Diseases - Yu-Han Chung; Chia-Wei Lin; Hsin-Yu Huang; Shu-Ling Chen; Hei-Jen Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Ya-Ching Chang; Hsiu Mei Hsieh-Li (Journal of Molecular Neuroscience, 2020)

Variation and evolution of C:N ratio among different organs enable plants to adapt to N‐limited environments - Jiahui Zhang; Nianpeng He; Congcong Liu; Li Xu; Zhi Chen; Ying Li; Ruomeng Wang; Guirui Yu; Wei Sun; Chunwang Xiao; Han Y. H. Chen; Peter B. Reich (Global Change Biology, 2020)
Carbon (C) and nitrogen (N) are the primary elements involved in the growth and development of plants. The C:N ratio is an indicator of nitrogen use efficiency (NUE) and an input parameter for some ecological and ecosystem models. However, knowledge remains limited about the convergent or divergent variation in the C:N ratios among different plant organs (e.g., leaf, branch, trunk, and root) and how evolution and environment affect the coefficient shifts. Using systematic measurements of the leaf–branch–trunk–root of 2,139 species from tropical to cold‐temperate forests, we comprehensively evaluated variation in C:N ratio in different organs in different taxa and forest types. The ratios showed convergence in the direction of change but divergence in the rate of change. Plants evolved toward lower C:N ratios in the leaf and branch, with N playing a more important role than C. The C:N ratio of plant organs (except for the leaf) was constrained by phylogeny, but not strongly. Both the change of C:N during evolution and its spatial variation (lower C:N ratio at midlatitudes) help develop the adaptive growth hypothesis. That is, plants with a higher C:N ratio promote NUE under strong N‐limited conditions to ensure survival priority, whereas plants with a lower C:N ratio under less N‐limited environments benefit growth priority. In nature, larger proportion of species with a high C:N ratio enabled communities to inhabit more N‐limited conditions. Our results provide new insights on the evolution and drivers of C:N ratio among different plant organs, as well as provide a quantitative basis to optimize land surface process models.

A multidisciplinary assessment of the impact of spilled acids on geoecosystems: an overview - Sung Pil Hyun; Doyun Shin; Hee Sun Moon; Young-Soo Han; Seonjin Ha; Yoonho Lee; Eunhee Lee; Hyun Jung; Yu Sik Hwang (Environmental Science and Pollution Research, 2020)

Fungal community succession under influence of biochar in cow manure composting - Xin Jiang; Liting Deng; Qingxin Meng; Yu Sun; Yue Han; Xiaotong Wu; Siyuan Sheng; Haifeng Zhu; Bello Ayodeji; Ugochi Uzoamaka Egbeagu; Xiuhong Xu (Environmental Science and Pollution Research, 2020)

Influence of the degree of donor bone marrow hyperplasia on patient clinical outcomes after allogeneic hematopoietic stem cell transplantation - Feifei Tang; Xiaodong Mo; Xiaohui Zhang; Yu Wang; Chenhua Yan; Yuhong Chen; Huan Chen; Wei Han; Yao Chen; Fengrong Wang; Jingzhi Wang; Yuqian Sun; et al. (Science China Life Sciences, 2020)

Mechanism of CNP-mediated DG-PKC and IP4 signaling pathway in diabetic rats with gastric motility disorder - Hui-Ming Lian; Jun-Yu Guo; Yan Sun; Mo-Han Zhang; Li-Hua Piao; Zheng Jin; Ying-Lan Cai (Molecular Biology Reports, 2020)

Angiotensin II induces apoptosis of cardiac microvascular endothelial cells via regulating PTP1B/PI3K/Akt pathway - Yanyan Wang; Yuyuan Fan; Yu Song; Xueting Han; Mingqiang Fu; Jingfeng Wang; Xiaotong Cui; Juan Cao; Li Chen; Kai Hu; Aijun Sun; Jingmin Zhou; et al. (In Vitro Cellular & Developmental Biology - Animal, 2019)

Jurassic granitic magmatism in the lesser Xing’an-Zhangguangcai ranges of NE China: the Dong’an example - Ji-Long Han; Jing-Gui Sun; Yang Liu; Liang Ren; Chang-Sheng Wang; Xiao-Tian Zhang; Yun-Peng He; Ri-Dong Yu; Qian Lu (International Geology Review, 2019)

Relevance of number and physiological status of conspecifics in preventing stress-induced decreases in newly proliferated cells and neuroblasts - Li-Han Sun; Wen-Yu Tzeng; Yi-Han Liao; Wen-Ting Deng; Chianfang G. Cherng; Lung Yu (Psychopharmacology, 2019)

Orientin Improves Cognition by Enhancing Autophagosome Clearance in an Alzheimer’s Mouse Model - Yi Zhong; Qing-yu Zheng; Cheng-yan Sun; Ze Zhang; Kun Han; Ning Jia (Journal of Molecular Neuroscience, 2019)

Effects of 2,3′,4,4′5-pentachlorobiphenyl exposure during pregnancy on epigenetic imprinting and maturation of offspring’s oocytes in mice - Qi-Long He; Xu-Yu Wei; Xiao-Ying Han; Qian Zhou; Hai-Quan Wang; Nai-Zheng Ding; Xiao-Qian Meng; Heide Schatten; Qing-Yuan Sun; Shu-Zhen Liu (Archives of Toxicology, 2019)

Short-term exposure to ambient air pollution and daily atherosclerotic heart disease mortality in a cool climate - Guangcong Liu; Baijun Sun; Lianzheng Yu; Jianping Chen; Bing Han; Bo Liu; Jie Chen (Environmental Science and Pollution Research, 2019)

Is There Any Correlation Between Landscape Characteristics and Total Nitrogen in Wetlands Receiving Agricultural Drainages? - Han Yu; Xiaodong Wang; Lijuan Chu; Guodong Wang; Guangzhi Sun; Mingyang Sun; Jingyu Wang; Ming Jiang (Chinese Geographical Science, 2019)

Growth, artificial seedling raising and cultivation of Sargassum confusum (Fucales, Phaeophyceae) inhabiting the coast of Shandong Peninsula, China - Jinhua Pan; Zhuangzhi Zhang; Shenhui Yu; Houwei Han; Xin Jiang; Liming Jiang; Guangjin Liang; Juan Sun; Xiaojie Li; Guanpin Yang (Journal of Applied Phycology, 2019)

Membrane biofouling retardation by zwitterionic peptide and its impact on the bacterial adhesion - Si-Yu Wang; Deng-Cheng Han; Chao Song; Meng-Na Li; Muhammad Zaheer Afzal; Shu-Guang Wang; Xue-Fei Sun (Environmental Science and Pollution Research, 2019)

Correction to: Facile synthesis of the magnetic metal–organic framework Fe3O4/Cu3(BTC)2 for efficient dye removal - Hui Sun; Hengyuan Zhang; Huimin Mao; Bin Yu; Jian Han; Gajanan Bhat (Environmental Chemistry Letters, 2019)

Facile synthesis of the magnetic metal–organic framework Fe3O4/Cu3(BTC)2 for efficient dye removal - Hui Sun; Hengyuan Zhang; Huimin Mao; Bin Yu; Jian Han; Gajanan Bhat (Environmental Chemistry Letters, 2019)

Degradation potential and diversity of oil-degrading bacteria isolated from the sediments of the Jiaozhou Bay, China - Wei Gao; Xiangxing Gao; Tiezhu Mi; Bin Han; Yiran Zhang; Xinzi Li; Xiaofei Yin; Chengjun Sun; Qian Li; Zhisong Cui; Xiao Luan; Zhigang Yu; et al. (Acta Oceanologica Sinica, 2019)

Application of different single extraction procedures for assessing the bioavailability of heavy metal(loid)s in soils from overlapped areas of farmland and coal resources - Ping Luo; Xin Xiao; Xiaoxuan Han; Yu Ma; Xiaofei Sun; Jiachao Jiang; Hui Wang (Environmental Science and Pollution Research, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Macrophage-derived CCL18 promotes osteosarcoma proliferation and migration by upregulating the expression of UCA1 - Yang Su; Yan Zhou; Yuan-jue Sun; Ya-Ling Wang; Jun-yi Yin; Yu-jing Huang; Jian-jun Zhang; Ai-na He; Kun Han; Hui-zhen Zhang; Yang Yao; Xiao-Bin Lv; et al. (Journal of Molecular Medicine, 2019)

Lycium barbarum polysaccharide attenuates diabetic testicular dysfunction via inhibition of the PI3K/Akt pathway-mediated abnormal autophagy in male mice - Guang-Jiang Shi; Jie Zheng; Xiao-Xu Han; Ya-Ping Jiang; Zhi-Mei Li; Jing Wu; Qing Chang; Yang Niu; Tao Sun; Yu-Xiang Li; Zhen Chen; Jian-Qiang Yu (Cell and Tissue Research, 2018)

QTL for flag leaf size and their influence on yield-related traits in wheat - Chunhua Zhao; Yinguang Bao; Xiuqin Wang; Haitao Yu; Anming Ding; Chunhui Guan; Junpeng Cui; Yongzhen Wu; Han Sun; Xingfeng Li; Dongfeng Zhai; Linzhi Li; et al. (Euphytica, 2018)

Confluentibacter flavum sp. nov., Isolated from the Saline Lake - Yu. Li; Xin-Jun Hou; Xia Shen; Shuai-Bo Han; Zhao Ju; Zhe Zhao; Xiao-Yun Yu; Min Wu; Cong Sun (Current Microbiology, 2018)

Knockout of ush2a gene in zebrafish causes hearing impairment and late onset rod-cone dystrophy - Shanshan Han; Xiliang Liu; Shanglun Xie; Meng Gao; Fei Liu; Shanshan Yu; Peng Sun; Changquan Wang; Stephen Archacki; Zhaojing Lu; Xuebin Hu; Yayun Qin; et al. (Human Genetics, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Late Cretaceous–Cenozoic uplift, deformation, and erosion of the SW Tianshan Mountains in Kyrgyzstan and Western China - Zhengle Chen; Zongxiu Wang; Fengbin Han; Wengao Zhang; Qing Zhang; Zhenju Zhou; Xiaohu Wang; Weifeng Xiao; Shuqin Han; Xinqi Yu; Yue Sun; Takenov Nurgazy; et al. (International Geology Review, 2018)

Isolation and identification of Salmonella pullorum bacteriophage YSP2 and its use as a therapy for chicken diarrhea - Kunyuan Tie; Yuyu Yuan; Shiqing Yan; Xi Yu; Qiuyang Zhang; Huihui Xu; Yang Zhang; Jingmin Gu; Changjiang Sun; Liancheng Lei; Wenyu Han; Xin Feng (Virus Genes, 2018)

Mitigation of nitrous oxide emissions from acidic soils by Bacillus amyloliquefaciens , a plant growth‐promoting bacterium - Shanghua Wu; Guoqiang Zhuang; Zhihui Bai; Yu Cen; Shengjun Xu; Haishu Sun; Xingguo Han; Xuliang Zhuang (Global Change Biology, 2018)
Nitrous oxide (N 2 O) is a long‐lived greenhouse gas that can result in the alteration of atmospheric chemistry and cause accompanying changes in global climate. To date, many techniques have been used to mitigate the emissions of N 2 O from agricultural fields, which represent one of the most important sources of N 2 O. In this study, we designed a greenhouse pot experiment and a microcosmic serum bottle incubation experiment using acidic soil from a vegetable farm to study the effects of Bacillus amyloliquefaciens ( BA ) on plant growth and N 2 O emission rates. The addition of BA to the soil promoted plant growth enhanced the soil pH and increased the total nitrogen ( TN ) contents in the plants. At the same time, it decreased the concentrations of ammonium ( NH 4 + ), nitrate ( NO 3 − ) and TN in the soil. Overall, the addition of BA resulted in a 50% net reduction of N 2 O emissions compared with the control. Based on quantitative PCR and the network analysis of DNA sequencing, it was demonstrated that BA partially inhibited the nitrification process through the significant reduction of ammonia oxidizing bacteria. Meanwhile, it enhanced the denitrification process, mainly by increasing the abundance of N 2 O‐reducing bacteria in the treatment with BA . The results of our microcosm experiment provided evidence that strongly supported the above findings under more strictly controlled laboratory conditions. Taken together, the results of our study evidently demonstrated that BA has dual effects on the promotion of plant growth and the dramatic reduction of greenhouse emissions, thus suggesting the possibility of screening beneficial microbial organisms from the environment that can promote plant growth and mitigate greenhouse trace gases.

In type 2 diabetes induced by cigarette smoking, activation of p38 MAPK is involved in pancreatic β-cell apoptosis - Hui Xu; Qiushi Wang; Qian Sun; Yu Qin; Aohan Han; Ye Cao; Qianlei Yang; Ping Yang; Jiachun Lu; Qizhan Liu; Quanyong Xiang (Environmental Science and Pollution Research, 2018)

Polyphasic taxonomic characterisation of a novel strain as Pararhizobium haloflavum sp. nov., isolated from soil samples near a sewage treatment tank - Xia Shen; Yu Li; Zhe Zhao; Yi-Fan Han; Wen-Wu Zhang; Xiao-Yun Yu; Chong-Ya Zhang; Cong Sun; Min Wu (Antonie van Leeuwenhoek, 2018)

Tree-ring stable carbon isotope-based April–June relative humidity reconstruction since ad 1648 in Mt. Tianmu, China - Yu Liu; Weiyuan Ta; Qiang Li; Huiming Song; Changfeng Sun; Qiufang Cai; Han Liu; Lu Wang; Sile Hu; Junyan Sun; Wenbiao Zhang; Wenzhu Li (Climate Dynamics, 2018)

Alternative oxidase functions in the excess excitation energy-induced resistance to pathogen infection - Qin-zheng Hou; Kun Sun; Ling-yun Jia; Jun-yu Liang; Jia-jia Xie; Li-na Lu; Han-qing Feng; Jing Wen (Biologia, 2018)

iTRAQ-based comparative proteomic analysis provides insights into somatic embryogenesis in Gossypium hirsutum L. - Hua-Guo Zhu; Wen-Han Cheng; Wen-Gang Tian; Yang-Jun Li; Feng Liu; Fei Xue; Qian-Hao Zhu; Yu-Qiang Sun; Jie Sun (Plant Molecular Biology, 2018)

Ameliorative Effect of VE, IGF-I, and hCG on the Fluoride-Induced Testosterone Release Suppression in Mice Leydig Cells - Yuxiang Yu; Yongli Han; Ruiyan Niu; Jundong Wang; Ram Kumar Manthari; Mohammad Mehdi Ommati; Zilong Sun (Biological Trace Element Research, 2018)

Effects of glucose and gibberellic acid on glucosinolate content and antioxidant properties of Chinese kale sprouts - Hui-ying Miao; Meng-yu Wang; Jia-qi Chang; Han Tao; Bo Sun; Qiao-mei Wang (Journal of Zhejiang University-SCIENCE B, 2017)

Down-regulation of Noggin and miR-138 coordinately promote osteogenesis of mesenchymal stem cells - Xing-Kun Sun; Jin Zhou; Lei Zhang; Tian Ma; Yu-Han Wang; Yan-Mei Yang; Yan-Ting Tang; Hong Li; Li-Jun Wang (Journal of Molecular Histology, 2017)

An anti-Propionibacterium acnes antibody shows heterologous resistance to an Actinobacillus pleuropneumoniae infection independent of neutrophils in mice - Jian-fang Liu; Qiu-yue Ma; Ri-ning Zhu; Meng-jun Cheng; Chun-tong Bao; Jing-min Gu; Chang-jiang Sun; Paul Richard Langford; Wen-yu Han; Lian-cheng Lei (Immunologic Research, 2017)

20(S)-25-methoxyl-dammarane-3β, 12β, 20-triol negatively regulates activation of STAT3 and ERK pathways and exhibits anti-cancer effects in HepG2 cells - Hui-Han Ai; Zi-Long Zhou; Lu-Guo Sun; Mei-Ting Yang; Wei Li; Chun-Lei Yu; Zhen-Bo Song; Yan-Xin Huang; Yin Wu; Lei Liu; Xiao-Guang Yang; Yu-Qing Zhao; et al. (Apoptosis, 2017)

A genetic variant in the placenta-derived MHC class I chain-related gene A increases the risk of preterm birth in a Chinese population - Junjiao Song; Jing Li; Han Liu; Yuexin Gan; Yang Sun; Min Yu; Yongjun Zhang; Fei Luo; Ying Tian; Weiye Wang; Jun Zhang; Julian Little; et al. (Human Genetics, 2017)

Kinetics of Antioxidant-Producing Maillard Reaction in the Mixture of Ribose and Sea Cucumber ( Stichopus japonicus ) Gut Hydrolysates - Jia-Run Han; Zhi-Mo Zhu; Hai-Tao Wu; Na Sun; Yue Tang; Cui-Ping Yu; Chen-Chen Zhao; Zheng-Yu Zhang; Ao-Ting Li; Jia-Nan Yan (Journal of Aquatic Food Product Technology, 2017)

Microsatellite records for volume 9, issue 3 - Aiguo Yang; Biao Wu; Chao Shen; Guangming Zhang; Hanmiao Liu; Hongying Guo; Jiaman Li; Jinliang Liu; Liqing Zhou; Longbing Rao; Man Yang; Mengdi Li; et al. (Conservation Genetics Resources, 2017)

High-resolution mapping of QTL for fatty acid composition in soybean using specific-locus amplified fragment sequencing - Bin Li; Shengxü Fan; Fukuan Yu; Ying Chen; Shengrui Zhang; Fenxia Han; Shurong Yan; Lianzheng Wang; Junming Sun (Theoretical and Applied Genetics, 2017)

Characteristics of Aerococcus viridans isolated from bovine subclinical mastitis and its effect on milk SCC, yield, and composition - Meng Sun; Jian Gao; Tariq Ali; Dan Yu; Shiyao Zhang; Saeed U. Khan; Séamus Fanning; Bo Han (Tropical Animal Health and Production, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Cloning and expression analysis of zygote arrest 1 (Zar1) in New Zealand white rabbits - DAN WANG; SHU-YU XIE; WEI ZHANG; CAI-XIA SUN; TAO HUANG; AN-SI WANG; XUE-LEI HAN; GUI-RONG SUN; MING LI (Journal of Genetics, 2017)

Effects of aluminum trichloride on the cartilage stimulatory growth factors in rats - Fan Zhang; Xudong Sun; Hongyan Yu; Xu Yang; Miao Song; Yanfei Han; Yanfei Li; Yanzhu Zhu (BioMetals, 2017)

De novo transcriptome analysis reveals insights into dynamic homeostasis regulation of somatic embryogenesis in upland cotton (G. hirsutum L.) - Wen-Han Cheng; Hua-Guo Zhu; Wen-Gang Tian; Shou-Hong Zhu; Xian-Peng Xiong; Yu-Qiang Sun; Qian-Hao Zhu; Jie Sun (Plant Molecular Biology, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Alcohol intake and Helicobacter pylori infection: a dose–response meta-analysis of observational studies - Shi-Yu Liu; Xin-Chen Han; Jan Sun; Guang-Xia Chen; Xiao-Ying Zhou; Guo-Xin Zhang (Infectious Diseases, 2016)

Transcription factor Sp1 prevents TRF2ΔBΔM-induced premature senescence in human diploid fibroblasts - Hyun Ju An; Hyeon Ju Lee; Suhwa Jang; Yu-Jin Jung; Sun Shim Choi; Sang Chul Park; Jeong A. Han (Molecular and Cellular Biochemistry, 2016)

Gabapentinoid Insensitivity after Repeated Administration is Associated with Down-Regulation of the α2δ-1 Subunit in Rats with Central Post-Stroke Pain Hypersensitivity - Yan Yang; Fei Yang; Fan Yang; Chun-Li Li; Yan Wang; Zhen Li; Yun-Fei Lu; Yao-Qing Yu; Han Fu; Ting He; Wei Sun; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2016)

Top-down effects of bighead carp (Aristichthys nobilis) and Leptodora richardi (Haplopoda, Leptodoridae) in a subtropical reservoir during the winter–spring transition: a mesocosm experiment - Shuai-Ying Zhao; Yu-Ping Sun; Bo-Ping Han (Hydrobiologia, 2016)

Intranasal Delivery of Granulocyte Colony-Stimulating Factor Enhances Its Neuroprotective Effects Against Ischemic Brain Injury in Rats - Bao-liang Sun; Mei-qing He; Xiang-yu Han; Jing-yi Sun; Ming-feng Yang; Hui Yuan; Cun-dong Fan; Shuai Zhang; Lei-lei Mao; Da-wei Li; Zong-yong Zhang; Cheng-bi Zheng; et al. (Molecular Neurobiology, 2016)

Myeloid-Specific Blockade of Notch Signaling by RBP-J Knockout Attenuates Spinal Cord Injury Accompanied by Compromised Inflammation Response in Mice - Bei-Yu Chen; Min-Hua Zheng; Yan Chen; Yan-Ling Du; Xiao-Long Sun; Xing Zhang; Li Duan; Fang Gao; Liang Liang; Hong-Yan Qin; Zhuo-Jing Luo; Hua Han (Molecular Neurobiology, 2015)

Analysis of additive and epistatic quantitative trait loci underlying fatty acid concentrations in soybean seeds across multiple environments - Shengxu Fan; Bin Li; Fukuan Yu; Fenxia Han; Shurong Yan; Lianzheng Wang; Junming Sun (Euphytica, 2015)
Soybean is one of the most important oilseed crops in the world. The soybean oil contains various fatty acids. Their concentrations determine the quality and nutritional value of soybean oil. On the other hand, quantitative trait loci (QTL) mapping for the concentrations of soybean predominant fatty acids could provide the genetic basis for soybean fatty acid composition. In this study, a soybean genetic linkage map was constructed based on 161 polymorphic SSR markers in recombinant inbred lines (RILs) derived from a cross of cv. Luheidou2 × Nanhuizao. By using this map, 35 additive QTLs underlying individual fatty acid concentrations were identified in single environment, while 17 additive QTLs were identified underlying specific fatty acids across multiple environments or underlying multiple fatty acids. Fifteen of the 52 loci were found to be novel loci, explaining 5–24 % of phenotypic variation. Moreover, 25 epistatic QTLs were identified and explained a high phenotypic variation for the fatty acid concentrations, suggesting an essential role of epistatic effect for fatty acid concentrations. The identification of additive and epistatic QTLs suggested a complex network for soybean fatty acid concentrations, and will facilitate the understanding for fatty acid accumulation.

Application of a weak magnetic field to improve microbial fuel cell performance - Zhong-Hua Tong; Han-Qing Yu; Wen-Wei Li; Yun-Kun Wang; Min Sun; Xian-Wei Liu; Guo-Ping Sheng (Ecotoxicology, 2015)

The role of N-Glycan modification of TNFR1 in inflammatory microglia activation - Lijian Han; Dongmei Zhang; Tao Tao; Xiaolei Sun; Xiaojuan Liu; Guizhou Zhu; Zhiwei Xu; Liang Zhu; Yu Zhang; Wangrui Liu; Kaifu Ke; Aiguo Shen (Glycoconjugate Journal, 2015)

TsMIP6 enhances the tolerance of transgenic rice to salt stress and interacts with target proteins - Linlin Sun; Guohong Yu; Xiaori Han; Shichao Xin; Xiaojing Qiang; Linlin Jiang; Shuhui Zhang; Xianguo Cheng (Journal of Plant Biology, 2015)

A Potent Multi-functional Neuroprotective Derivative of Tetramethylpyrazine - Hai-Yun Chen; Da-Ping Xu; Guo-Lian Tan; Wei Cai; Gao-Xiao Zhang; Wei Cui; Jin-Zhao Wang; Cheng Long; Ye-Wei Sun; Pei Yu; Karl Wahkeung Tsim; Zai-Jun Zhang; et al. (Journal of Molecular Neuroscience, 2015)

DLEC1, a 3p tumor suppressor, represses NF-κB signaling and is methylated in prostate cancer - Lian Zhang; Qian Zhang; LiLi Li; Zhaohui Wang; Jianming Ying; Yu Fan; Qun He; Tianjing LV; Wenke Han; Jun Li; Yang Yang; Ben Xu; et al. (Journal of Molecular Medicine, 2015)

The aflatoxin-detoxifizyme specific expression in mouse parotid gland - Li-zeng Guan; Yu-ping Sun; Jin-shun Cai; Han-dong Wu; Long-zheng Yu; Yong-liang Zhang; Qian-yun Xi (Transgenic Research, 2015)

Characterization and high expression of recombinant Ustilago maydis xylanase in Pichia pastoris - Hongjuan Han; Shuang You; Bo Zhu; Xiaoyan Fu; Baihui Sun; Jin Qiu; Chengye Yu; Lei Chen; Rihe Peng; Quanhong Yao (Biotechnology Letters, 2015)

Gelsolin: Role of a Functional Protein in Mitigating Radiation Injury - Mingjuan Li; Fengmei Cui; Ying Cheng; Ling Han; Jia Wang; Ding Sun; Yu-long Liu; Ping-kun Zhou; Rui Min (Cell Biochemistry and Biophysics, 2015)

Phytoplankton and chlorophyll a relationships with ENSO in Prydz Bay, East Antarctica - HaiSheng Zhang; ZhengBing Han; Jun Zhao; PeiSong Yu; ChuanYu Hu; WeiPing Sun; Dan Yang; GenHai Zhu; Bing Lu; Hans-UIrich Peter; Walter Vetter (Science China Earth Sciences, 2014)

Post-stroke pain hypersensitivity induced by experimental thalamic hemorrhage in rats is region-specific and demonstrates limited efficacy of gabapentin - Fei Yang; Han Fu; Yun-Fei Lu; Xiao-Liang Wang; Yan Yang; Fan Yang; Yao-Qing Yu; Wei Sun; Jia-Shuang Wang; Michael Costigan; Jun Chen (Neuroscience Bulletin, 2014)

Isolation and characterization of novel Glu-St1 alleles from Pseudoroegneria spicata and Pd. strigosa - Shu-Bin Wang; Hua-Nan Han; Yu Liang; Lei Sun; Guang-Min Xia; Shu-Wei Liu (Genetica, 2014)

Metabolomic approach to optimizing and evaluating antibiotic treatment in the axenic culture of cyanobacterium Nostoc flagelliforme - Pei-pei Han; Shi-ru Jia; Ying Sun; Zhi-lei Tan; Cheng Zhong; Yu-jie Dai; Ning Tan; Shi-gang Shen (World Journal of Microbiology and Biotechnology, 2014)

Varied metal-binding properties of lipoprotein PsaA in Streptococcus pneumoniae - Nan Li; Xiao-Yan Yang; Zhong Guo; Jing Zhang; Kun Cao; Junlong Han; Gong Zhang; Langxia Liu; Xuesong Sun; Qing-Yu He (JBIC Journal of Biological Inorganic Chemistry, 2014)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

Characterization of the immunogenicity and pathogenicity of malate dehydrogenase in Brucella abortus - Xiangan Han; Yongliang Tong; Mingxing Tian; Xiaoqing Sun; Shaohui Wang; Chan Ding; Shengqing Yu (World Journal of Microbiology and Biotechnology, 2014)

Vanillin derivatives as the selective small molecule inhibitors of FtsZ - Juan Sun; Ming-Hui Li; Xin-Yi Wang; Yang Zhang; Rong-Ju Yuan; Han-Yu Liu; Hai-Liang Zhu (Medicinal Chemistry Research, 2014)

The Protective Effect of Vanadium Against Diabetic Cataracts in Diabetic Rat Model - Lei Sun; De-Jing Shi; Xiang-Chun Gao; Shu-Yong Mi; Ying Yu; Qing Han (Biological Trace Element Research, 2014)

Fluid inclusion and isotope geochemistry of the Yangla copper deposit, Yunnan, China - Xi-An Yang; Jia-Jun Liu; Long-Bo Yang; Si-Yu Han; Xiao-Ming Sun; Huan Wang (Mineralogy and Petrology, 2014)

Neuronal cell differentiation of mesenchymal stem cells originating from canine amniotic fluid - Eun Young Kim; Kyung-Bon Lee; Jung Yu; Ji Hye Lee; Keun Jung Kim; Kil-Woo Han; Kang-Sun Park; Dong-Soo Lee; Min Kyu Kim (Human Cell, 2014)

High dose of extracellular ATP switched autophagy to apoptosis in anchorage-dependent and anchorage-independent hepatoma cells - Qing Wei; Ying Zhang; Lei Sun; Xiaoqing Jia; Wanwan Huai; Chengcheng Yu; Zhengkun Wan; Lihui Han (Purinergic Signalling, 2013)

Distinct Expression of Mas1-Related G-Protein-Coupled Receptor B4 in Dorsal Root and Trigeminal Ganglia—Implications for Altered Behaviors in Acid-Sensing Ion Channel 3-Deficient Mice - Ya-Han Huang; Chin-Yu Chang; Chih-Cheng Chen; Chih-Dong Yang; Wei-Hsin Sun (Journal of Molecular Neuroscience, 2013)

Small interfering RNA targeting Rac1 sensitizes colon cancer to dihydroartemisinin-induced cell cycle arrest and inhibited cell migration by suppressing NFκB activity - Peng Han; Ying Luan; Yanlong Liu; Zhiwei Yu; Jingwen Li; Zicheng Sun; Gang Chen; Binbin Cui (Molecular and Cellular Biochemistry, 2013)

Effects of microbial elicitor on production of hypocrellin by Shiraia bambusicola - Wen Du; Zongqi Liang; Xiao Zou; Yanfeng Han; Jiandong Liang; Jianping Yu; Wanhao Chen; Yurong Wang; Chunlong Sun (Folia Microbiologica, 2013)

Occurrence of several main antibiotic residues in raw milk in 10 provinces of China - Nan Zheng; Jiaqi Wang; Rongwei Han; Xiaomin Xu; Yunpeng Zhen; Xueyin Qu; Peng Sun; Songli Li; Zhongnuo Yu (Food Additives & Contaminants Part B-Surveillance, 2013)

Quantitative evaluation of Candia antarctica lipase B displayed on the cell surface of a Pichia pastoris based on an FS anchor system - Xing-xiang Liang; Bei-bei Wang; Yu-fei Sun; Ying Lin; Shuang-yan Han; Sui-ping Zheng; Tang-bing Cui (Biotechnology Letters, 2013)

An in vivo molecular imaging probe 18F-Annexin B1 for apoptosis detection by PET/CT: preparation and preliminary evaluation - Ming-Wei Wang; Fang Wang; Yu-Jia Zheng; Ying-Jian Zhang; Yong-Ping Zhang; Qing Zhao; Clifton Kwang-Fu Shen; Yue Wang; Shu-Han Sun (Apoptosis, 2013)

The Diagnostic Value of Treadmill Exercise Test Parameters for Coronary Artery Disease - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2013)

Effects of Ibutilide on Canine Cardiac Pacing Threshold and on Induction Rates of Atrial Fibrillation - Jian-ling Sun; Rong Han; Ji-hong Guo; Xiao-ying Li; Xian-lin Ma; Chong-yu Wang (Cell Biochemistry and Biophysics, 2012)

Antibacterial activity of hypocrellin A against Staphylococcus aureus - Wen Du; Chunlong Sun; Zongqi Liang; Yanfeng Han; Jianping Yu (World Journal of Microbiology and Biotechnology, 2012)

Effect of Ibutilide on the Canine Cardiac Conduction System - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2012)

Initial validation of GOCI water products against in situ data collected around Korean peninsula for 2010–2011 - Jeong-Eon Moon; Young-Je Park; Joo-Hyung Ryu; Jong-Kuk Choi; Jae-Hyun Ahn; Jee-Eun Min; Young-Baek Son; Sun-Ju Lee; Hee-Jeong Han; Yu-Hwan Ahn (Ocean Science Journal, 2012)

Analysis of Aztreonam-Inducing Proteome Changes in Nondividing Filamentous Helicobacter pylori - Chunhong Shao; Yabin Zhou; Yundong Sun; Hongyan Wang; Wei Qu; Han Yu; Chunyan Chen; Jihui Jia (Current Microbiology, 2012)

The calcium-sensing receptor promotes adipocyte differentiation and adipogenesis through PPARγ pathway - Yong-Han He; Ying He; Xi-Lu Liao; Yu-Cun Niu; Guan Wang; Chen Zhao; Liang Wang; Ming-Jie Tian; Ying Li; Chang-Hao Sun (Molecular and Cellular Biochemistry, 2012)

Co-delivery of Adenovirus and Carmustine by Anionic Liposomes with Synergistic Anti-tumor Effects - Zhirong Zhong; Yu Wan; Sanjun Shi; Jianfeng Han; Zhirong Zhang; Xun Sun (Pharmaceutical Research, 2012)

Regulation of auxin response by miR393-targeted transport inhibitor response protein 1 is involved in normal development in Arabidopsis - Zhe-Hao Chen; Mao-Lin Bao; Yu-Zhe Sun; Yan-Jun Yang; Xiao-Hong Xu; Jun-Hui Wang; Ning Han; Hong-Wu Bian; Mu-Yuan Zhu (Plant Molecular Biology, 2011)

Effects of SLCO1B1 polymorphisms on the pharmacokinetics and pharmacodynamics of repaglinide in healthy Chinese volunteers - Jiake He; Zhixia Qiu; Ning Li; Yang Yu; Yang Lu; Deen Han; Tingting Li; Di Zhao; Wei Sun; Fang Fang; Jianheng Zheng; Hongwei Fan; et al. (European Journal of Clinical Pharmacology, 2011)

Residues and Dissipation of the Herbicide Fenoxaprop-P-ethyl and Its Metabolite in Wheat and Soil - Xiaoxu Chen; Shuang Yu; Lijun Han; Shujun Sun; Yanan Zhi; Wenming Li (Bulletin of Environmental Contamination and Toxicology, 2011)

Soybean oil content QTL mapping and integrating with meta-analysis method for mining genes - Zhao-ming Qi; Qiong Wu; Xue Han; Ya-nan Sun; Xiang-yu Du; Chun-yan Liu; Hong-wei Jiang; Guo-hua Hu; Qing-shan Chen (Euphytica, 2011)

A Novel Cytoplasmic Isopentenyl Diphosphate Isomerase Gene from Tomato (Solanum lycopersicum): Cloning, Expression, and Color Complementation - Jin Sun; Yu-Yang Zhang; Hui Liu; Zhe Zou; Chan-Juan Zhang; Xiao-Hui Zhang; Han-Xia Li; Zhi-Biao Ye (Plant Molecular Biology Reporter, 2010)

Effects of Repeated Seafood Consumption on Urinary Excretion of Arsenic Species by Volunteers - Byung-Sun Choi; Seong-Jin Choi; Dong-Won Kim; Mingai Huang; Na-Young Kim; Kyung-Su Park; Choong-Yong Kim; Hyo-Min Lee; Young-Na Yum; Eui-Sik Han; Tae-Seok Kang; Il-Je Yu; et al. (Archives of Environmental Contamination and Toxicology, 2010)

Molecular Cloning and Characterization of a Gene Encoding Eukaryotic Initiation Factor iso4E in Tomato (Solanum lycopersicum) - Yu-Yang Zhang; Mei-Fang Qi; Jin Sun; Xiao-Hui Zhang; He-Li Shi; Han-Xia Li; Zhi-Biao Ye (Plant Molecular Biology Reporter, 2009)

Temporal analysis of population genetic composition in the overexploited Japanese eel Anguilla japonica - Yu-San Han; Yu-Liang Sun; Yi-Fen Liao; I-Chiu Liao; Kang-Ning Shen; Wann-Nian Tzeng (Marine Biology, 2008)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

A collection of 10,096 indica rice full-length cDNAs reveals highly expressed sequence divergence between Oryza sativa indica and japonica subspecies - Xiaohui Liu; Tingting Lu; Shuliang Yu; Ying Li; Yuchen Huang; Tao Huang; Lei Zhang; Jingjie Zhu; Qiang Zhao; Danlin Fan; Jie Mu; Yingying Shangguan; et al. (Plant Molecular Biology, 2007)

Involvement of MGr1-Ag/37LRP in the vincristine-induced HIF-1 expression in gastric cancer cells - Lili Liu; Xiaoxuan Ning; Li Sun; Yongquan Shi; Shuang Han; Changcun Guo; Yu Chen; Shiren Sun; Fang Yin; Kaichun Wu; Daiming Fan (Molecular and Cellular Biochemistry, 2007)

A novel cryptic plasmid pBMB175 from Bacillus thuringiensis subsp. tenebrionis YBT-1765 - Junyan Huang; Dongmei Han; Ziniu Yu; Ming Sun (Archives of Microbiology, 2007)

Enhanced brain targeting efficiency of intranasally administered plasmid DNA: an alternative route for brain gene therapy - In-Kwon Han; Mi Young Kim; Hyang-Min Byun; Tae Sun Hwang; Jung Mogg Kim; Kwang Woo Hwang; Tae Gwan Park; Woon-Won Jung; Taehoon Chun; Gil-Jae Jeong; Yu-Kyoung Oh (Journal of Molecular Medicine, 2006)

Complete assignment of the chromosomes of Gossypium hirsutum L. by translocation and fluorescence in situ hybridization mapping - Kai Wang; Xianliang Song; Zhiguo Han; Wangzhen Guo; John Z. Yu; Jing Sun; Jiaju Pan; Russell J. Kohel; Tianzhen Zhang (Theoretical and Applied Genetics, 2006)

Agrobacterium-mediated transformation of Perilla (Perilla frutescens) - Byoung-Kyu Lee; Seung-Hee Yu; Yul-Ho Kim; Byung-Ohg Ahn; Han-Sun Hur; Sang-Chul Lee; Zhanyuan Zhang; Jang-Yong Lee (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Net water vapour exchange over a mixed needle and broad-leaved forest in Changbai Mountain during autumn - Wen Xuefa; Yu Guirui; Sun Xiaomin; Li Qingkang; Ren Chuanyou; Han Shijie (Journal of Geographical Sciences, 2003)

Palaeovegetation of China: a pollen data‐based synthesis for the mid‐Holocene and last glacial maximum - G. Yu; X. Chen; J. Ni; R. Cheddadi; J. Guiot; H. Han; S. P. Harrison; C. Huang; M. Ke; Z. Kong; S. Li; W. Li; et al. (Journal of Biogeography, 2000)
Pollen data from China for 6000 and 18,000 14 C yr bp were compiled and used to reconstruct palaeovegetation patterns, using complete taxon lists where possible and a biomization procedure that entailed the assignment of 645 pollen taxa to plant functional types. A set of 658 modern pollen samples spanning all biomes and regions provided a comprehensive test for this procedure and showed convincing agreement between reconstructed biomes and present natural vegetation types, both geographically and in terms of the elevation gradients in mountain regions of north‐eastern and south‐western China. The 6000 14 C yr bp map confirms earlier studies in showing that the forest biomes in eastern China were systematically shifted northwards and extended westwards during the mid‐Holocene. Tropical rain forest occurred on mainland China at sites characterized today by either tropical seasonal or broadleaved evergreen/warm mixed forest. Broadleaved evergreen/warm mixed forest occurred further north than today, and at higher elevation sites within the modern latitudinal range of this biome. The northern limit of temperate deciduous forest was shifted c. 800 km north relative to today. The 18,000 14 C yr bp map shows that steppe and even desert vegetation extended to the modern coast of eastern China at the last glacial maximum, replacing today’s temperate deciduous forest. Tropical forests were excluded from China and broadleaved evergreen/warm mixed forest had retreated to tropical latitudes, while taiga extended southwards to c . 43°N.

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Interleukin-13 increases prostaglandin E2 (PGE2) production by normal human polymorphonuclear neutrophils by enhancing cyclooxygenase 2 (COX-2) gene expression - C.-L. Yu; M.-H. Huang; Y.-Y. Kung; C.-Y. Tsai; Y.-Y. Tsai; S.-T. Tsai; D.-F. Huang; K.-H. Sun; S.-H. Han; H.-S. Yu (Inflammation Research, 1998)

Random sequence analysis of genomic DNA of a hyperthermophile: Aquifex pyrophilus - In-Geol Choi; Sang Suk Kim; Jae-Ryeon Ryu; Ye Sun Han; Won-Gi Bang; Sung-Hou Kim; Yeon Gyu Yu (Extremophiles, 1997)